Effects of Cholesterol and Solution pH on Daptomycin-bilayer Interactions - Samuel R. Pennock; Maggie Cortes; Megha D. Salecha; Neil X. Sevilla; Nicole R. Rementer; Kevin Rana; Luke C. Hicks; Emmaleigh Fox; Ahmed Grine; Patience S. Hammel; Timothy D. Vaden; Benjamin R. Carone; et al. (The Journal of Membrane Biology, 2026)

A novel splice site variant in DEGS1 leads to aberrant splicing and loss of DEGS1 enzyme activity, a VUS resolved - Holly C. Beale; Victor Tse; Joanna Y. Lee; Jon Akutagawa; Yusuph Mavura; Brandon Saint-John; Allison Cheney; Dennis R. Mulligan; Guillermo Chacaltana; Martin Gutierrez; Jessica Tenney; Joseph T. Shieh; et al. (Human Genetics, 2026)
Pathogenic DEGS1 variants have been reported in individuals with autosomal recessive hypomyelinating leukodystrophy 18 (HLD18; MIM# 618404). Here we describe three participants with HLD features and a previously unreported homozygous DEGS1 5′ splice site variant, c.825+4_825 + 5delAGinsTT (NM_003676.4). We used next-generation DNA and transcriptome sequencing, cell-based splicing assays, and tandem mass spectrometry to detect and characterize the variant’s impact on DEGS1 expression. We then performed RNA structure probing and conventional antisense oligonucleotide screening to investigate molecular mechanisms for potential therapeutic intervention. We show that the splice site variant: (1) was sufficient to induce exon two skipping in most detected transcripts; (2) resulted in structural changes to the 5′ and 3′ splice site regions using RNA structure probing; and (3) corresponds to plasma sphingolipid profiles consistent with loss of sphingolipid delta(4)-desaturase activity. Our RNA and lipidomic evidence proved that the DEGS1 variant c.825+4_825 + 5delAGinsTT is pathogenic and suggested a mechanistic model that explains how exon two skipping is induced.

Probing soy protein-aldehyde binding by inverse liquid chromatography on protein-packed columns - Mincong Liu; Neil C. Da Costa; Bo Chen; Bauke Albada; Hans-Gerd Janssen (Food Chemistry, 2026)

Triazine and other herbicides in sediments of lower Laurentian Great Lakes – pre- and post-depositional mobility and in-situ degradation - Shanshan Zhou; Huan He; Tian Lin; Jiehong Guo; Xiusen Yang; Xinyue Jia; Neil C. Sturchio; Karl J. Rockne; John P. Giesy; An Li (Environmental Pollution, 2026)

A framework for identifying paper parks - Jessica L. Stewart; Naomi Kingston; Natasha Ali; Heather C. Bingham; Zoe G. Davies; Nigel Dudley; Charlie J. Gardner; Jonas Geldmann; Diego Juffe-Bignoli; Thomas Pienkowski; Rachel E. Sykes; Neil D. Burgess; et al. (Biological Conservation, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

Sensitivity analysis of modeled soil water dynamics within variable rate irrigation zones for winter wheat - Elisa A. Flint; Jeffrey D. Svedin; Austin P. Hopkins; Ruth Kerry; Ryan Jensen; Matt A. Yost; Alon Ben-Gal; Bryan G. Hopkins; Neil C. Hansen (Irrigation Science, 2026)
Understanding within-field and season variability of soil water supply and crop water stress is critical for successful variable-rate irrigation (VRI) management. The objectives of this study were to (1) assess within-field variability of field capacity (FC), wilting point (WP), total available water (TAW), and initial soil volumetric water content (VWC init ); (2) validate a water balance model based on the American Society of Civil Engineers (ASCE) standardized Penman-Monteith estimation of reference evapotranspiration (ET 0 ) using measured within-field VWC; and (3) evaluate the model sensitivity to FC, WP, VWC init , and crop coefficients. A 22-ha field of winter wheat ( Triticum aestivum L.) near Grace, Idaho, United Sates of America was delineated into zones and managed with VRI. Spatial variability of soil water characteristics among 102 sites was measured in the field: FC (355–488 mm), WP (103–153 mm), TAW (230–361 mm), and VWC init (325–464 mm) in a 1.2 m soil profile. Model validation against measured VWC resulted in root mean square error (RMSE) values of 23.2–61.3 mm for different sampling dates. These RMSE values showed the ability to model within-field spatially variable soil water dynamics and crop water stress. The model showed high sensitivity of predicted ET and soil water depletion output values to FC and VWC init inputs, but lower sensitivity to WP. The sensitivity analysis also suggested spatially variable crop coefficients improve prediction of spatially variable ET rates. The model validation highlights opportunities for a spatially variable modelling approach, while the model’s sensitivity to soil and crop parameters highlights practical limitations to scheduling VRI.

Targeted Profiling of Signaling Molecules in Papaver rhoeas L. Reveals that Onset and Control of Benzylisoquinoline Alkaloid Biosynthesis Corresponds with Cytokinins, Independent of Light - Zeynab Azimychetabi; Anna B. Kisiala; Erin N. Morrison; Scott C. Farrow; R. J. Neil Emery (Journal of Plant Growth Regulation, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Mercury speciation and stable isotope signatures in marine sediments of Honda Bay (the Philippines) impacted by abandoned mercury mine - Jessie O. Samaniego; Cris Reven L. Gibaga; Alexandria M. Tanciongco; Rico Neil M. Quierrez; Lota A. Creencia; Rachelle Clien G. Reyes; John Henry C. Gervasio; Fern Rose A. Peregrino (Marine Pollution Bulletin, 2026)

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Lung function and inflammation in healthy young adults after 6.6 hours of 0.07 ppm ozone exposure - Edward R. Pennington; Jairus C. Pulczinski; Martin W. Case; Jacob S. Griffin; Neil E. Alexis; Ilona Jaspers; Carole Robinette; Ann Chelminski; Andrea Davis; Neena Miller; David B. Peden; Andrew J. Ghio; et al. (Environmental Research, 2026)

Evaluating the empirical basis for threat attribution in the IUCN Red List - Ena Humphries; Isaac M. Smith; Mark Ziebell; Charlotte M. Probst; Neil Carter; Brian C. Weeks (Conservation Biology, 2026)
Understanding the impacts of different threats on species is key to successful conservation interventions and policies. The International Union for Conservation of Nature (IUCN) assesses threats to species, and the organization's Red List of Threatened Species is a key conservation tool. We quantified the degree to which threats in IUCN assessments for 3 vertebrate groups (birds, amphibians, and ray‐finned fishes) were based on species‐specific quantitative empirical data. To do this, for 2142 IUCN species assessments, all listed references were reviewed to determine whether they contained species‐specific quantitative data linking a listed threat and the assessed species. Only 7.5% of listed threats across all taxa and categories were based on species‐specific quantitative data. For species with at least one threat listed, only 12.5% of species had species‐specific quantitative data underlying at least one threat. There were more data on threats for some taxa, and there was a trend toward having more information on threats that are generally considered less predictable, such as “invasive/problematic” species and climate change. Understanding how a lack of species‐specific data may affect understanding of extinction processes is crucial for continued improvement of conservation outcomes.

Isotope composition of groundwater and surface waters at the vicinity of abandoned mercury mine in Puerto Princesa City, The Philippines - Jessie O. Samaniego; Norman D. S. Mendoza; Charles Darwin T. Racadio; Cris Reven L. Gibaga; Alexandria M. Tanciongco; Rico Neil M. Quierrez; Fern Rose A. Peregrino; Rachelle Clien G. Reyes; John Henry C. Gervasio (Isotopes in Environmental and Health Studies, 2026)

The Scotland–Canada overturning array (SCOTIA): twenty years of meridional overturning in the subpolar North Atlantic - Alan D. Fox; Neil J. Fraser; Kristin Burmeister; Sam C. Jones; Stuart A. Cunningham; Lewis A. Drysdale; Ahmad Fehmi Dilmahamod; Johannes Karstensen (Ocean Science, 2026)
The Atlantic meridional overturning circulation (AMOC) is expected to decline dramatically over the 21st century, with severe impacts for Northern Hemisphere climate. After 20 years of sustained monitoring in the subtropics, a detectable AMOC weakening trend is now beginning to emerge. However, continuous observations at subpolar latitudes are currently too short-lived to determine any weakening signal above the large-amplitude interannual variability. Here, we introduce a new subpolar observing configuration, SCOTIA (Scotland–Canada overturning array), combining parts of the existing OSNAP mooring array with scattered CTD and Argo data, to extend the record of subpolar AMOC backward in time to cover the subtropical monitoring period, 2004–2024. SCOTIA facilitates a rigorous comparison of the decadal-scale variability in transports and overturning at subpolar and subtropical latitudes. Our results show subpolar AMOC varies on pentadal to decadal timescales with an amplitude comparable to that observed in the subtropics. Anomalously high overturning during 2016–2020 was driven by increased southward transports in the density classes associated with Labrador Sea Water. We find no statistically significant trend in subpolar AMOC during the period 2004–2024.

Deep drawdown of the Mediterranean during the Messinian Salinity Crisis inferred from Nile Canyon 3D seismic reflection data near Cairo, Egypt - William Bosworth; Neil C. Mitchell (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Men's exposure to ambient air pollution and in vitro fertilization outcomes among an infertility treatment population - Lindsey M. Russo; J. Richard Pilsner; Timothy P. Canty; Neil J. Perkins; Pauline Mendola; Karen Schliep; May Shaaban; Rachael B. Hemmert; Akanksha Singh; Allison M. Ring; James A. Vanderslice; C. Matthew Peterson; et al. (International Journal of Hygiene and Environmental Health, 2026)

Correction: Hereditary gynecological cancer management in women with Lynch syndrome: a survey across Europe - Kevin J. J. Kwinten; Joanne A. de Hullu; Helen Bolton; Monique M. A. Brood-van Zanten; Valentina Chiappa; Stefan Cosyns; Sergi Fernandez-Gonzalez; Angelique Flöter Rådestad; Sophie Frank; Rieke Gellner; Susanne Housmans; Nina Kovacevic; et al. (Familial Cancer, 2026)

Crevice corrosion of CuNi 90/10 under simulated macrofouling in temperate and tropical Australian marine environments - M. A. Javed; R. Piola; W. C. Neil; S. A. Wade (Biofouling, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Corrigendum to “Isotope effects (Cl, O, C) of heterogeneous electrochemistry induced by Martian dust activities” [Earth and Planetary Science Letters 676 (2026) 119784] - Neil C. Sturchio; Hao Yan; Alian Wang; W. Andrew Jackson; Huiming Bao; Chuck Y.C. Yan; Linnea J. Heraty; Yu Wei; Quincy H.K. Qu; Kevin S. Olsen (Earth and Planetary Science Letters, 2026)

Comparative efficacy of electrokinetic and static leaching for selective metal recovery and nutrient release from porphyry Cu tailings - Yujie Yan; Gawen R.T. Jenkin; Andrew P. Abbott; Alexandria Tanciongco; Carlo A. Arcilla; Cris Reven L. Gibaga; Daniel J. Smith; Djoan Kate Tungpalan; Jonathan E. Chambers; John Henry C. Gervasio; James Symons; Justine Perry T. Domingo; et al. (Chemical Engineering Journal, 2026)

Genomic Signatures of Microgeographic Adaptation in Anopheles coluzzii Across Urban, Rural, and Forested Environments in Gabon - Josquin Daron; Lemonde Bouafou; Jacob A. Tennessen; Nil Rahola; Loic Talignani; Boris Makanga; Ousman Akone‐Ella; Marc F. Ngangue; Neil M. Longo Pendy; Christophe Paupy; Daniel E. Neafsey; Michael C. Fontaine; et al. (Molecular Ecology, 2026)
Species distributed across heterogeneous environments often evolve locally adapted populations, but understanding how these persist in the presence of homogenizing gene flow remains puzzling. In Gabon, Anopheles coluzzii, a major African malaria mosquito, is found in various ecological settings, including urban areas, remote rural villages, and forested environments away from any human presence. This study investigates the genomic signatures of local adaptation in populations from distinct environments including the urban area of Libreville, and two proximate sites 10 km apart in the La Lopé National Park (LLP), a village and its sylvatic neighbourhood. Whole genome re‐sequencing of 96 mosquitoes unveiled 5.9 million high‐quality single nucleotide polymorphisms. Coalescent‐based demographic analyses suggest an ∼ 12,000‐year‐old divergence between Libreville and La Lopé populations, followed by a secondary contact ( ∼ 4000 ybp) resulting in asymmetric effective gene flow. The urban population displayed reduced effective size, evidence of inbreeding, and strong selection pressures likely associated to insecticides or pollution present in urban settings, as suggested by the hard selective sweeps detected in genes involved in detoxification and insecticide resistance. In contrast, the two geographically proximate LLP populations showed larger effective sizes, and distinctive selective signals, notably soft‐selective sweeps on the standing genetic variation. Although presumably neutral loci failed to discriminate between LLP populations, our findings support that microgeographic adaptation can swiftly emerge through selection on standing genetic variation despite gene flow. This study contributes to the growing understanding of evolution of populations in heterogeneous environments amid ongoing gene flow and how major malaria mosquitoes adapt to humans and its environment.

Success of restoration strategies in preventing extirpation of 2 critically endangered coral species - Erinn M. Muller; Mark C. Ladd; Richard Karp; Phanor H. Montoya‐Maya; Ilsa B. Kuffner; Andrew C. Baker; Erich Bartels; Amanda Bourque; Abigail S. Clark; Nikkie Cox; Martine D'Alessandro; Ben Daughtry; et al. (Conservation Biology, 2026)
An unprecedented marine heatwave in 2023 caused widespread coral bleaching and mortality throughout the Caribbean. In the Florida Keys (USA), 2 foundation species, elkhorn coral ( Acropora palmata ) and staghorn coral ( Acropora cervicornis ), were severely affected. These species have been the primary focus of reef restoration in Florida for decades. Substantial losses of these species occurred in outplanted populations, in ocean‐based nurseries, and among remnant wild colonies, leading to uncertainty over their future in the Florida Keys, given recent observed trends in climate conditions. However, the past 2 decades of restoration activity created a community of experts, a network of ocean‐based and land‐based coral‐rearing infrastructure, and 2 independent land‐based coral gene banks that prevented regional extirpation and preserved much of the genetic richness of these critically endangered coral species. Without the past decades of effort and the emergency response associated with the 2023 bleaching event, Florida acroporids would largely have been lost. This outcome afforded by the restoration network in Florida demonstrates the value of proactively establishing resources prior to major disturbances. We identified several critical strategies that, in the context of existing climate change, are preventing the extirpation of coral species in Florida, including extending collaborative restoration efforts to solidify a network of trained experts; establishing trust‐focused relationships among management agencies and restoration groups; testing direct interventions to reduce light and temperature stress early during thermal anomalies; developing redundant ocean‐based and land‐based nurseries; and establishing living coral gene banks prior to major threats to prevent the extirpation of coral species.

Hereditary gynecological cancer management in women with Lynch syndrome: a survey across Europe - Kevin J. J. Kwinten; Joanne A. de Hullu; Helen Bolton; Monique M. A. Brood-van Zanten; Valentina Chiappa; Stefan Cosyns; Sergi Fernandez-Gonzalez; Angelique Flöter Rådestad; Sophie Frank; Rieke Gellner; Susanna Housmans; Nina Kovacevic; et al. (Familial Cancer, 2026)
We aim to compare clinical practices in the gynecological management of women with Lynch syndrome across Europe and assess the need for multidisciplinary gynecological care for this high-risk population. European gynecologists involved in the clinical care of women with Lynch syndrome were invited to complete a cross-sectional survey regarding their clinical practices and organization of care. All participating gynecologists were based in hospitals that are members of the European Reference Network on Genetic Tumour Risk Syndromes (ERN GENTURIS). A total of 33 gynecologists (57%) from 25 unique hospitals across 12 countries participated in the survey. National guidelines on the gynecological management of women with Lynch syndrome were absent in a significant number of European countries. Local multidisciplinary team meetings were available in 61% of hospitals. Considerable heterogeneity was reported in the organization of care, as well as in surveillance, prevention, and treatment strategies. Standardized European guidelines for the gynecological care of women with Lynch syndrome are warranted to promote uniformity. Gynecologists specialized in hereditary cancer should take the lead in developing and implementing these guidelines. Hospitals managing women with Lynch syndrome should have the resources to organize multidisciplinary team meetings, which are crucial for the effective implementation of these guidelines and the improvement of personalized care.

High nitrogen fixation and Braarudosphaera presence in the North Sea - Kendra Turk‐Kubo; Claire Mahaffey; Jo Hopkins; Ruth Hawley; Louisa Norman; Lewis Wrightson; Ben Fisher; Stefanie Rynders; Clive Neil; Maryam Ilyas; Maeve C. Lohan (Limnology and Oceanography, 2026)
Nitrogen fixation, the microbial conversion of dinitrogen gas to ammonia, is a key nitrogen source and critical for sustaining marine productivity. We investigated the diversity and activity of nitrogen‐fixers in surface waters of the North Sea and Norwegian coast during July 2023. We detected, for the first time, the presence of Braarudosphaera /UCYN‐A (up to 10 4 nifH copies L −1 ) and measurable nitrogen fixation rates (up to 110 nM d −1 ) throughout the North Sea. Nitrogen‐fixing organisms may be transported from the northeast Atlantic across the northern North Sea by southward current systems, via Baltic Sea inflow or be a persistent but overlooked component of the phytoplankton community. We estimate nitrogen fixation may support between 4% and 24% of summertime net primary production. Nitrogen fixation is currently neglected in numerical models of shelf seas, yet may play a critical role in sustaining shelf sea productivity in the contemporary and future ocean.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Application of in vitro insecticide selection pressure to a susceptible strain of the sheep blowfly reveals different rates of resistance development and cross-resistance patterns - Andrew C. Kotze; Neil H. Bagnall; Angela P. Ruffell; Nicholas M. Rolls (Veterinary Parasitology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Isotope effects (Cl, O, C) of heterogeneous electrochemistry induced by Martian dust activities - Neil C. Sturchio; Hao Yan; Alian Wang; W. Andrew Jackson; Huiming Bao; Chuck Y.C. Yan; Linnea J. Heraty; Yu Wei; Quincy H.K. Qu; Kevin S. Olsen (Earth and Planetary Science Letters, 2026)

Biological invasions in the Philippines: Challenges and priorities in a megadiverse country - Neil Angelo Abreo; Antonín Kouba; Emerson Y. Sy; Darren C.J. Yeo; Benjamin M. Vallejo; Krizler C. Tanalgo; Lief Erikson Gamalo; Aaron Froilan Raganas; Brian Sabanal; Dale Anthony L. To; Lorenzo Vilizzi; Ismael Soto; et al. (Biological Conservation, 2026)

Heterogeneity, Productivity, and Migration Drive Continental Evenness Patterns of Bird Assemblages - Neil A. Gilbert; Natalie Queally; Jacob C. Cooper; Harold N. Eyster; Peter J. Williams (Global Ecology and Biogeography, 2026)
Aim Evenness quantifies similarities in abundances among species in an assemblage and may influence processes such as species coexistence and the supply of ecosystem services. Previous work has failed to identify generalised patterns of how productivity and habitat heterogeneity influence evenness and moreover has not considered seasonal variation in evenness arising from migration. Therefore, our goal was to quantify the interplay of productivity, habitat heterogeneity, and migration on evenness patterns of bird assemblages. Location Contiguous United States. Time Period Contemporary. Group Birds (613 species). Methods Using relative abundance maps from eBird, we computed evenness of bird assemblages for 27 × 27 km grid cells at weekly temporal resolution. We used generalized linear mixed‐effects models to evaluate the influences of productivity (normalized difference vegetation index), habitat heterogeneity (Shannon diversity of land cover), and the dominance of migratory species on evenness. Results Productivity and heterogeneity interacted to influence evenness such that there was a positive productivity–evenness relationship in high‐heterogeneity landscapes but no relationship in low‐heterogeneity landscapes. Evenness was highest during the pre‐breeding and breeding seasons when migratory taxa were present, but a high dominance of migrants reduced evenness and generally dampened evenness–productivity relationships. Main Conclusions Evenness increased with productivity in high‐heterogeneity—but not low‐heterogeneity—landscapes, indicating that hypotheses relating to energy availability and niche partitioning should be considered jointly. Higher evenness during the growing season likely reflects the presence of low‐abundance migrant taxa, whereas the negative effects of migrant dominance on evenness are likely driven by one or few high‐abundance species. The dampening effect of migrant dominance on evenness–productivity relationships in many situations supports the notion that migrants concentrate in high‐productivity landscapes.

Climate Change Challenges Grey Wolf Resilience: Insights From Dental Microwear - Amanda A. Burtt; Neil F. Adams; Sabina Nowak; Robert W. Mysłajek; Michal Figura; Mark A. Purnell; Angela L. Lamb; Danielle C. Schreve (Ecology Letters, 2026)
The grey wolf exemplifies ecological resilience, having survived major climatic fluctuations since the Middle Pleistocene. Once the world's most widely distributed mammal, its range has been drastically reduced by human‐driven habitat loss, persecution and competition for resources. Although listed as of Least Concern globally by the IUCN, the omission of climate change as a threat raises critical questions about its future persistence. This study examines dietary flexibility in European grey wolves ( Canis lupus ) using dental microwear texture analysis (DMTA). We compare British Pleistocene wolves from the Last Interglacial (MIS 5e) and the penultimate interglacial (MIS 7a–c) and contemporary wolves from Poland. Results suggest that during periods of elevated global temperatures, wolves exhibit evidence of increased durophagy. These data demonstrate deep‐time dietary plasticity and recurrent behavioural shifts, indicating that while the grey wolf is resilient, future warming winters may significantly reshape wolf diets in the mid‐latitude ecosystems.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

A decade of continuous Rockall Trough transport observations using moorings and gliders - Kristin Burmeister; Sam C. Jones; Neil J. Fraser; Alan D. Fox; Stuart A. Cunningham; Lewis A. Drysdale; Mark E. Inall; Tiago S. Dotto; N. Penny Holliday (Ocean Science, 2026)
The Rockall Trough, northwest of Scotland and Ireland, is a key conduit for the North Atlantic Current (NAC) and European Slope Current (ESC) transporting heat and salt toward the Nordic Seas and Arctic Ocean while mediating exchanges between the open ocean and the European shelf. We present a decade-long record of Rockall Trough circulation from the Ellett Array providing the first continuous estimates of heat and freshwater transport between 2014 and 2024. We develop a methodology that combines the high spatial resolution of gliders with the high temporal resolution of moorings and ocean reanalysis output producing continuous eastern boundary velocity fields of the ESC for integration into the full Rockall Trough transport product. This approach improves the mean structure of the ESC, capturing the southward undercurrent previously unresolved and enhancing the ability to reproduce extreme, likely mesoscale, transport events. The Rockall Trough transport is dominated by the NAC flowing through the mid basin, exhibiting multi-year variability consistent with changes in the subpolar gyre and the mid-2010s cold freshwater anomaly. The ESC acts as a secondary driver, is not correlated with the NAC and is influenced by along-slope wind stress. Since 2022, warmer and saltier conditions, amplified by the 2023 extreme North Atlantic marine heatwave, have strengthened northward volume, heat, and salt transport through the Ellett Array. Our results highlight the value of sustained glider-based boundary current observations for Atlantic climate monitoring and demonstrate that the combined mooring–glider framework provides a robust and transferable approach for long-term ocean transport monitoring.

Methyl-processing metabolisms play central roles in methane cycling during rice cultivation - Raegan Paul; Emily K. Bechtold; Jared Ellenbogen; Reed Woyda; Thomas Holloway; Neil Carter; George Heslop-Harrison; Kelly C. Wrighton; Michael J. Wilkins (Agriculture, Ecosystems & Environment, 2026)

Marimo for monitoring and filtering of aquatic environments - Neil Phillips; Thomas C. Draper; Andrew P. Geary; Kathryn Lamb-Riddell; Darren M. Reynolds; Joshua A. C Steven; Freya Radford; Abdul R. Farooq; Andrew Adamatzky (Environmental Science and Pollution Research, 2025)
Aegagropila linnaei (commonly known as “Marimo”) forms dense spheres of intertwined algae filaments capable of capturing and retaining a wide range of particles and microorganisms (up to 2 mm in length) from freshwater environments. This study explores the potential of Marimo as a sustainable tool for environmental monitoring and water filtration. We present a novel, non-destructive method for extracting entrapped materials (including microplastics, sediments, and indicator species) and evaluate various analytical techniques for characterising the extracted content. A prototype Marimo-based filtration system was developed, demonstrating significant reductions in microbial contaminants within a recirculating water system. These findings highlight the advantages of using Marimo as a low-cost, eco-friendly solution for long-term aquatic ecosystem monitoring and remediation.

Bridging the Gap: Enhancing Prostate Cancer Survivorship and Advocacy Among Ethnically Diverse Black Men Through Community Town Halls - Motolani E. Ogunsanya; Ernest Kaninjing; Sara M. DeForge; Daniel J. Morton; Perry Cole; Patrick Beckford; Donald Reese; Thomas Mitchell; Everett Montgomery; Roland Odeleye; Erick Y. Miró-Rivera; Kaitlin Roberts; et al. (Journal of Cancer Education, 2025)
We present findings from town hall meetings held with ethnically diverse Black prostate cancer (CaP) survivors in 2022 and 2023. Four town halls (total participants, N = 265) focused on diagnosis, treatment, psychosocial support, and overall survivorship. Moderated by a long-term CaP survivor, each session featured a panel that included medical providers (urologic oncologists and clinical psychologists), as well as CaP survivors of American, Caribbean, and African origin and their spouses. Surveys captured demographic data, clinical information, CaP-specific details (for survivors only), and perceptions of the town halls. The meetings highlighted three interrelated themesinfluencing decision-making: access to comprehensive information, the strength of support networks, and the availability of culturally competent care. These town halls revealed important educational and support opportunities for ethnically diverse Black men with CaP, promoting informed decision-making throughout the cancer journey and improving quality of life while reducing decisional regret during survivorship.

Nubia-Arabia separation: Clues from oceanic spreading fabric in the Red Sea - Neil C. Mitchell; A.Y. Izzeldin; Ian C.F. Stewart (Gondwana Research, 2025)

Structural behaviour of indeterminate continuous reinforced concrete beams with shear reinforcement and asymmetric loading - Jacob Yager; Neil A. Hoult; Evan C. Bentz; Joshua E. Woods (Engineering Structures, 2025)

Comparative exo-proteomics of solid and submerged state fermentation using the lignocellulose degrading Ascomycete Parascedosporium putredinis NO1 - Daniel R. Leadbeater; Alexander T. Setchfield; Adam A. Dowle; Neil C. Bruce (Bioresource Technology, 2025)

Knowledge of Sugar Content Among College Students: Variation by Primary Campus Dining Beverage Choice - M. SOTO; A. Brown; P. Policastro; C. Neil (Journal of the Academy of Nutrition and Dietetics, 2025)

Halogenated flame retardants in the sediments of the lower Great Lakes and region-wide discoveries - Tian Lin; Shanshan Zhou; Huan He; Jiehong Guo; Neil C. Sturchio; Karl J. Rockne; John P. Giesy; An Li (Journal of Hazardous Materials, 2025)

Beyond maximum density: multi-parameter insights into Scots pine climate sensitivity - Inga K. Homfeld; Frederick Reinig; Edurne Martinez del Castillo; Max C. A. Torbenson; Oliver Konter; Rob Wilson; Paul J. Krusic; Neil J. Loader; Hakan Grudd; Emily Reid; Kayleigh Letherbarrow; Jan Esper (Trees, 2025)
Key message Climate sensitivity of Pinus sylvestris has changed in minimum density while maximum density remains mostly stable, suggesting the use of additional density parameters could help detect response changes. Abstract As one of Eurasia's most widely distributed conifer species, Pinus sylvestris L. is frequently used in dendroclimatological reconstructions based on tree-ring width (TRW) and maximum latewood density (MXD). However, the climatic signals of additional parameters such as earlywood/latewood density (EWD/LWD) or minimum density (MND) are often overlooked, leaving their skill unexplored. Here, we investigate the growth responses of multiple P. sylvestris tree-ring parameters to ongoing climate change at two sites with contrasting climatic conditions using well-replicated density data from Scotland and Sweden. Correlations with mean, minimum, and maximum temperatures are strongest for LWD and MXD at both sites, with coefficients ranging from 0.5 to 0.7 for July, August, and the June–August season ( p < 0.05). A significant ( p < 0.05) negative correlation between MND and July temperatures was identified in the Swedish Torneträsk (TOR) data ( p < 0.05), which diminished since the late twentieth century. A comparable inverse MND temperature signal and change into the twenty-first century is not reflected in northern Scotland’s overall wetter and warmer site, suggesting a fundamental physiological change in tree-ring formation under global warming. A shift in the sensitivity of tree growth at northern European sites could reduce the effectiveness of proxies from such locations, posing implications for high-resolution climate reconstructions.

Stacking and Intersecting Nitrogen 4Rs on Potato: Economic Analysis - Samuel H. Stapley; Christopher S. McIntosh; Matt A. Yost; Neil C. Hansen; Ryan C. Christensen; Bryan G. Hopkins (American Journal of Potato Research, 2025)
The 4Rs of nutrient management is an initiative to balance economics with sustainability. The objective was to evaluate individual and stacked 4R practices on potato ( Solanum tuberosum L.) profitability. Treatments included all combinations of two nitrogen (N) sources (urea or polymer coated urea [PCU]), two rates (82 or 100%), and/or two timing/placements (at emergence or split-applied). Gross income and net profit were determined using yields, market sale data, and costs. Total gross income was greatest for PCU split applied and PCU at emergence in 2020 and 2023, respectively. Gross income and net profit were higher for the full rate for PCU compared to urea. The detrimental effect of the reduced rate disappeared with PCU, but not urea. A reduced rate of PCU was similar to a full rate of split applied urea. These data suggest that PCU is a profitable N source for potato even at reduced rates.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Speciation of cesium in a radiocesium-bearing microparticle emitted from Unit 1 during the Fukushima nuclear accident by XANES spectroscopy using transition edge sensor - Yoshio Takahashi; Hikaru Miura; Shinya Yamada; Oki Sekizawa; Kiyofumi Nitta; Tadashi Hashimoto; Takumi Yomogida; Akiko Yamaguchi; Shinji Okada; Takaaki Itai; Hiroki Suga; Teruhiko Kashiwabara; et al. (Journal of Hazardous Materials, 2025)

Quantifying CO2 plume stabilization at carbon storage projects, North Dakota, USA - Matthew E. Burton-Kelly; John E. Hunt; Neil W. Dotzenrod; John A. Templeton; Joshua G. Regorrah; Chantsalmaa Dalkhaa; Amanda J. Livers-Douglas; Wesley D. Peck; Kevin C. Connors; Nicholas A. Azzolina (International Journal of Greenhouse Gas Control, 2025)

Calibration is required for use of electromagnetic soil moisture sensors to accurately measure the water content of tree stems and sawdust - Jiaming Wang; Neil C. Turner; Hailong He (Plant and Soil, 2025)

Subsurface manifestation of marine heat waves in the southwestern Indian Ocean - Clea B. Welch; Neil Malan; Daneeja Mawren; Tamaryn Morris; Janet Sprintall; Juliet C. Hermes (Ocean Science, 2025)
Marine heat waves (MHWs) are extreme events of prolonged, anomalously warm ocean temperatures. Globally, marine heat waves are increasing in frequency and intensity and are responsible for long-term impacts on marine ecosystems, which have devastating socio-economic consequences. A key gap in our understanding of MHWs is how they manifest in the subsurface. This paper uses satellite sea surface temperature (SST) data and in situ subsurface temperature observations from expendable bathythermographs (XBTs) to investigate the anomalous water temperature characteristics associated with surface-identified MHWs in the southwestern Indian Ocean (SWIO) and how they progress through the water column. We find that (1) regions of high eddy activity in the Mozambique Channel and southeast of Madagascar, where eddy kinetic energy is high and SST variability is low, are primarily characterised by the occurrence of abrupt and intense MHWs and that (2) the frequency, duration and intensity of these events are largely associated with mesoscale activity. In these eddy corridors, surface-detected MHW case studies demonstrate a strong, deep-reaching subsurface temperature anomaly signal with a maximum intensity below the surface. The majority of these MHWs are associated with anticyclonic eddies, which provide a possible mechanism for the deep extent of the surface MHWs. Improving our understanding of the interaction between mesoscale features and subsurface MHW characteristics will benefit the prediction of MHWs and management of the regions' biodiversity.

Synthetic cytotoxicity profiling of cohesin mutants highlights recombination-based dependencies - Rafaela Horbach Marodin; Ecaterina Cozma; Sivan Reytan-Miron; Nigel J. O’Neil; Peter C. Stirling; Philip Hieter (DNA Repair, 2025)

Rising Heat, Rising Risks: Understanding the Nexus of Marine Heatwaves, Fishing Dependence, and Vulnerability to Coastal Communities - Sally C. Dowd; Ingrid van Putten; Lisa L. Colburn; Gretta T. Pecl; Bridget Mullany; Neil J. Holbrook; Alistair J. Hobday; Janet A. Nye (Global Change Biology, 2025)
Marine heatwaves are increasing in frequency, intensity, and duration as a result of climate change, and their biological impacts can in turn influence coastal communities. Despite advances in our knowledge of the physical drivers of marine heatwaves and their biological impacts, there has been limited work linking these extreme events to subsequent impacts on social systems. Describing risk to well‐being in coastal communities from marine heatwaves requires the consideration of the severity of marine heatwaves, impacted systems, and social vulnerability. We compared potential risk to well‐being, or quality of life, from 2012 to 2016 in coastal communities in the United States and Australia by considering marine heatwave total cumulative intensity, fishing dependence, and vulnerability indices. We extended a social indicators framework for the United States to develop vulnerability indices for coastal communities in Australia. Our approach revealed different spatial patterns in risk to well‐being and its drivers between the two countries. Marine heatwaves as the hazard were a key driver of risk in both countries, and vulnerability for the United States and fishing employment for Australia were also influential. Our study demonstrates that risk does not necessarily equal the hazard, and there is non‐transferability of risk results between countries despite similar physical oceanography and socioeconomic status. Identifying regions of high risk with our broad approach can help prioritize higher resolution community‐level work to mitigate risk and develop adaptation pathways.

Specificity database for bacterial pesticidal proteins against invertebrate targets - Colin Berry; Victoria Valby; Ruchir Mishra; Bryony C. Bonning; Leopoldo Palma; Neil Crickmore (Journal of Invertebrate Pathology, 2025)

Effects of calcareous marine algae on performance, rumen fermentation and methane emissions of high-yielding dairy cows - Philip C. Garnsworthy; Neil Saunders; Jennifer R. Goodman; Shane O’Connell (Animal Feed Science and Technology, 2025)

Setting the limit: cold rather than hot temperatures limit intertidal distribution of a coastal foundation species - Kerstin Wasson; Kim Cressman; Kathryn Beheshti; Erin C. Herder; Charlie Endris; Christopher D.G. Harley; Alicia Abadía-Cardoso; Rodrigo Beas-Luna; Joachim Carolsfeld; Andrew L. Chang; Jeffrey A. Crooks; Matthew C. Ferner; et al. (Marine Environmental Research, 2025)

Let the fish do the cropping: identifying fish grazers to improve coral aquaculture - Rachel C. Neil; Andrew Heyward; David G. Bourne; Craig Humphrey (Coral Reefs, 2025)
Controlling the growth of fouling organisms in coral aquaculture is a recognised approach to enhance survival during grow-out of recruits. Herbivorous fish can reduce algae growth, though indiscriminate grazing by the fish pose a risk to the early life stages of corals. To identify a suitable age or size to introduce fish to coral recruit culture, settlement tiles with 1-week-old, single-polyp and 1-month-old, multi-polyp Acropora millepora, Acropora kenti and Goniastrea retiformis were exposed to “brusher”, “cropper” and “concealed cropper” fish grazers for 24 h, in addition to a manual aquarist cleaned treatment and a control uncleaned treatment for comparison. In general, acroporid recruits displayed lower mortality than Goniastrea recruits across all types of grazing, and younger, smaller recruits were more vulnerable to grazing, with the “brusher” fish functional group more likely to cause mortality. Morality was low in the uncleaned controls for all corals, whilst single-polyp recruits generally saw slightly elevated mortality under manual aquarist cleaning. Grazing by the “brusher” Ctenochaetus binotatus resulted in the highest mortality across all treatments with week old, single-polyp recruits experiencing 2.5% and 8.6% mortality for A. millepora and A. kenti , respectively, and as high as 88.9% mortality for G. retiformis . In contrast, month old acroporids that were 2–7 polyps in size displayed < 1% probability of mortality when exposed to the same C. binotatus grazing. Grazing intensity of the fish also played a role, as fish belonging to the same functional group with higher bite rates caused higher recruit mortality. Overall, “cropper” Acanthurus nigrofuscus represented the best trade-off between minimising recruit mortality whilst reducing algae coverage on the settlement tiles. Based on our results and knowledge of coral recruit growth, coral grow-out operations would gain the most benefit by introducing fish grazers once corals reach the multi-polyp stage at > 1 month old for acroporids and other fast growing species, and later for smaller, slower growing species such as G. retiformis .

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Biodiversity monitoring in remote marine environments: Advancing environmental DNA/RNA sampling workflows - Michelle Scriver; Anastasija Zaiko; Xavier Pochon; Jo-Ann L. Stanton; Olga Belonovich; Gert-Jan Jeunen; Austen C. Thomas; Neil J. Gemmell; Ulla von Ammon (Marine Environmental Research, 2025)

Seabed stability inferred from the 2019–2020 earthquake swarm under a volcanic cone field and slopes of Condor Seamount, Azores - Neil C. Mitchell; Fernando Tempera; Thomas A. Morrow; Joaquim Luis; Christian Hübscher; Telmo Morato (Journal of Volcanology and Geothermal Research, 2025)

Extreme heat risk and the potential implications for the scheduling of football matches at the 2026 FIFA World Cup - Donal Mullan; Iestyn Barr; Neil Brannigan; Nuala Flood; Oliver R. Gibson; Catherine Hambly; Alan T. Kennedy-Asser; Aimée C. Kielt; Tom Matthews; Madeleine Orr (International Journal of Biometeorology, 2025)
Climate change is making extreme heat events more frequent and intense. This negatively impacts many aspects of society, including organised sport. As the world’s most watched sporting event, the FIFA World Cup commands particular attention around the threat of extreme heat. The 2022 tournament in Qatar was moved from summer to winter in response to this threat, and now attention turns to the 2026 tournament in North America with extreme heat risk across many of the 16 host locations. We examine this risk by modelling wet bulb globe temperature (WBGT) – a widely used measure of heat stress – for the host locations using hourly meteorological data for the period 2003–2022. Our results show that 14 out of 16 host locations exceed WBGTs of 28 °C, with four (nine) exceeding this threshold more than half the time during afternoons across the mean (hottest year) of the 20 year record. This threshold is important as the level beyond which some football governing bodies recommend match delay or postponement. A climatically sound argument is therefore presented to reschedule kick-off times outside the hottest afternoon hours for the host locations with highest heat risk at which no indoor air conditioned environment exists – primarily Miami and Monterrey, but also Philadelphia, Kansas City, Boston and New York. This study highlights the need to carefully assess heat risk ahead of major sporting events to help inform any potential interventions needed in the scheduling of matches and competitions in a warming climate.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Developmental exposure to legacy environmental contaminants, medial temporal lobe volumes and spatial navigation memory in late adolescents - Kevin Bastien; Gina Muckle; Pierre Ayotte; Neil C. Dodge; Joseph L. Jacobson; Sandra W. Jacobson; Dave Saint-Amour (Environmental Research, 2025)

Nipah virus G attachment protein inhibitors from Streptomyces spp. and optimization of a lead peptide scaffold through in silico approaches - Albert Neil G. Dulay; John Christian C. de Guzman; Nyzar Mabeth O. Odchimar; Fredmoore L. Orosco (Biologia, 2025)

Environmental drivers of tropospheric bromine and mercury variability in coastal East Antarctica - Neil C. Page; Jenny A. Fisher; Stephen R. Wilson; Robyn Schofield; Robert G. Ryan; Sean Gribben; Andrew R. Klekociuk; Grant C. Edwards; Anthony Morrison (Atmospheric Environment, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Demonstrating a biobased concept for the production of sustainable bacterial cellulose from mixed textile, agricultural and municipal wastes - Alexandra Lanot; Shivam Tiwari; Philip Purnell; Abdalla M. Omar; Miriam Ribul; Daniel J. Upton; Heather Eastmond; Ishrat J. Badruddin; Hannah F. Walker; Angharad Gatenby; Sharon Baurley; Paulo J.D.S. Bartolo; et al. (Journal of Cleaner Production, 2025)

Incidence and effects of anomalies and hybridization on Alabama freshwater fish index of biotic integrity results - Justin C. Bagley; Alicia K. Phillips; Sarah Buchanon; Patrick E. O’Neil; Elizabeth S. Huff (Environmental Monitoring and Assessment, 2024)

Genome-wide association study of drought tolerance in wheat (Triticum aestivum L.) identifies SNP markers and candidate genes - Sina Nouraei; Md Sultan Mia; Hui Liu; Neil C. Turner; Guijun Yan (Molecular Genetics and Genomics, 2024)
Drought stress poses a severe threat to global wheat production, necessitating an in-depth exploration of the genetic basis for drought tolerance associated traits. This study employed a 90 K SNP array to conduct a genome-wide association analysis, unravelling genetic determinants of key traits related to drought tolerance in wheat, namely plant height, root length, and root and shoot dry weight. Using the mixed linear model (MLM) method on 125 wheat accessions subjected to both well-watered and drought stress treatments, we identified 53 SNPs significantly associated with stress susceptibility (SSI) and tolerance indices (STI) for the targeted traits. Notably, chromosomes 2A and 3B stood out with ten and nine associated markers, respectively. Across 17 chromosomes, 44 unique candidate genes were pinpointed, predominantly located on the distal ends of 1A, 1B, 1D, 2A, 3A, 3B, 4A, 6A, 6B, 7A, 7B, and 7D chromosomes. These genes, implicated in diverse functions related to plant growth, development, and stress responses, offer a rich resource for future investigation. A clustering pattern emerged, notably with seven genes associated with SSI for plant height and four genes linked to both STI of plant height and shoot dry weight, converging on specific regions of chromosome arms of 2AS and 3BL. Additionally, shared genes encoding polygalacturonase, auxilin-related protein 1, peptide deformylase, and receptor-like kinase underscored the interconnectedness between plant height and shoot dry weight. In conclusion, our findings provide insights into the molecular mechanisms governing wheat drought tolerance, identifying promising genomic loci for further exploration and crop improvement strategies. Graphical Abstract (1) A diverse panel of wheat genotypes was cultivated under both well-watered and drought stress conditions; (2) Phenotyping involved washing, scanning, drying and weighing plants to evaluate the stress susceptibility (SSI) and stress tolerance (STI) indices for four drought tolerance-related traits; (3) Genotyping was performed by extracting DNA and using the wheat 90 K Illumina iSelect array; (4) Phenotypic and genotypic data were utilized in a genome-wide association analysis (GWAS) using a mixed linear model (MLM); (5) Population structure assessment, principal component analysis (PCA), and kinship analysis were conducted; (6) Candidate genes were identified, and (7) their molecular functions were analysed and discussed.

The 2020 Mw 6.6 Vernadsky transform earthquake sequence: rupture and Coulomb stress changes surrounding an oceanic core complex - Guilherme W. S. de Melo; Neil C. Mitchell; Sergey Y. Sokolov (Marine Geophysical Research, 2024)
Oceanic core complexes (OCCs) are upwards-convex areas of outcropping lower crustal or upper mantle rocks raised to the seabed by normal faults, commonly associated with weak lithologies such as serpentinites. They are common adjacent to transform valleys of slow-spreading ridges. In this paper, we analyse the September 2020, Mw 6.6 strike-slip earthquake and its two-week long aftershock sequence within the Vernadsky transform valley, using recordings from regional seismic stations. The aftershocks occurred in two phases. During the first four days, ∼ 131 events occurred east and northeast of the mainshock, overlapping an adjacent OCC complex along the northern flank of the transform valley. During the following nine days, 20 aftershocks occurred, including a Mw 5.8 event close to the OCC. To refine the locations of aftershocks, the spatial spread of the events (clustering) was refined by double-difference relocating 114 events, and five with teleseismic relative relocation. Modeling of static Coulomb stresses was carried out, based on a mainshock rupture length compatible with the 26–30 km horizontal extent of aftershocks. This revealed that the aftershocks occurred mainly in areas where static Coulomb stresses decreased, not increased. Other researchers have suggested that changes in fault strength can arise from dynamic stresses during major earthquakes, leading to seismicity in areas of decreased Coulomb stress. We explore this idea in the context of OCCs.

One-Stop-Shop Cancer Screening Clinic: Acceptability Testing - Jeannie M. Au; Jamilia R. Sly; Leah C. Savage; Matthew Beyrouty; Neil S. Calman; Michaela Frazier; Jay Musella; Francesca Minardi; Lina H. Jandorf; Ellerie Weber; Saborny Mahmud; Sarah J. Miller (Journal of Cancer Education, 2024)

The added value of using convective-permitting regional climate model simulations to represent cloud band events over South America - Marcia T. Zilli; Murilo Ruv Lemes; Neil C. G. Hart; Kate Halladay; Ron Kahana; Gilberto Fisch; Andreas Prein; Kyoko Ikeda; Changhai Liu (Climate Dynamics, 2024)
Climate science has long explored whether higher resolution regional climate models (RCMs) provide improved simulation of regional climates over global climate models (GCMs). The advent of convective-permitting RCMs (CPRCMs), where sufficiently fine-scale grids allow explicitly resolving rather than parametrising convection, has created a clear distinction between RCM and GCM formulations. This study investigates the simulation of tropical-extratropical (TE) cloud bands in a suite of pan-South America convective-permitting Met Office Unified Model (UM) and Weather Research and Forecasting (WRF) climate simulations. All simulations produce annual cycles in TE cloud band frequency within 10–30% of observed climatology. However, too few cloud band days are simulated during the early summer (Nov–Dec) and too many during the core summer (Jan–Feb). Compared with their parent forcing, CPRCMs simulate more dry days but systematically higher daily rainfall rates, keeping the total rain biases low. During cloud band systems, the CPRCMs correctly reproduced the observed changes in tropical rain rates and their importance to climatology. Circulation analysis suggests that simulated lower subtropical rain rates during cloud bands systems, in contrast to the higher rates in the tropics, are associated with weaker northwesterly moisture flux from the Amazon towards southeast South America, more evident in the CPRCMs. Taken together, the results suggest that CPRCMs tend to be more effective at producing heavy daily rainfall rates than parametrised simulations for a given level of near-surface moist energy. The extent to which this improves or degrades biases present in the parent simulations is strongly region-dependent.

Assessment of potentially toxic element contamination in wetland sediments of Boracay Island, Philippines - Cris Reven L. Gibaga; Jessie O. Samaniego; Alexandria M. Tanciongco; Rico Neil M. Quierrez; John Henry C. Gervasio; Rachelle Clien G. Reyes (Marine Pollution Bulletin, 2024)

Comparing Wetland Elevation Change Using a Surface Elevation Table, Digital Level, and Total Station - James C. Lynch; Neil Winn; Katya Kovalenko; Glenn Guntenspergen (Estuaries and Coasts, 2024)
The surface elevation table (SET) approach and two survey instruments, a digital level (DL) and a total station (TS), were used to evaluate elevation change at a 1-ha, micro-tidal, back-barrier salt marsh at Assateague Island National Seashore (Berlin, MD, USA) from 2016 to 2022. SET data were collected at 3 sampling stations along the perimeter of the plot, 36 pins per station, and the DL and TS data were collected adjacent to 36 stakes, four readings per stake, throughout the plot. The average elevation range of the marsh surface measurements at the SET stations was 2 cm, while the range was considerably greater within the larger 1-ha DL and TS sampling area (24 cm). The average elevation of the marsh surface only varied by 2 cm among the three methods. Elevation change trends of the three methods ranged from 2.8 to 3.5 mm year −1 and were not significantly different from each other. Despite differences in sample size and spatial distribution of measurements, these methods provided comparable measures of long-term trends in marsh surface elevation probably because the marsh at this site was structurally homogeneous with low topographic relief.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Distribution of total mercury in coastal sediments of Honda Bay, Palawan Island, the Philippines - Jessie O. Samaniego; Cris Reven L. Gibaga; Alexandria M. Tanciongco; Rico Neil M. Quierrez; Rachelle Clien G. Reyes; John Henry C. Gervasio (Marine Pollution Bulletin, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Contourite-like deposits suggest stronger-than-present circulation in the Plio-Pleistocene Red Sea - Neil C. Mitchell; Marco Ligi; Jonas Preine; Diederik Liebrand; Moamen Ali; Alessandro Decarlis (Global and Planetary Change, 2024)

Integrated modeling of nature’s role in human well-being: A research agenda - Rebecca Chaplin-Kramer; Stephen Polasky; Rob Alkemade; Neil D. Burgess; William W.L. Cheung; Ingo Fetzer; Mike Harfoot; Thomas W. Hertel; Samantha L.L. Hill; Justin Andrew Johnson; Jan H. Janse; Patrick José v. Jeetze; et al. (Global Environmental Change, 2024)

Formation of zinc carbonate phases on dissolving calcite, aragonite, and vaterite in acidic aqueous solutions - YoungJae Kim; Sang Soo Lee; Bektur Abdilla; Viktor Nikitin; Neil C. Sturchio; Paul Fenter (Geochimica et Cosmochimica Acta, 2024)

Making Global Climate Action work for nature and people: Priorities for Race to Zero and Race to Resilience - Idil Boran; Nathalie Pettorelli; Alexandre C. Köberle; Ricardo Aguiar Borges; Adriana De Palma; Deborah Delgado; Andrew Deneault; Alexandra Deprez; Pablo Imbach; Neil R. Jennings; Anke Manuela Salzmann; Oscar Widerberg; et al. (Environmental Science & Policy, 2024)

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

A framework for evaluating the value of agricultural pest management decision support systems - Joseph C. Helps; Frank van den Bosch; Neil Paveley; Lise Nistrup Jørgensen; Niels Holst; Alice E. Milne (European Journal of Plant Pathology, 2024)
Disease management decision support systems (DSS) are typically prediction algorithms that help farmers assess the risk of an epidemic, to guide whether, and to what extent, fungicide treatment is needed. However, there is frequently little information presented to quantify the value of using the DSS, i.e. the likely increased profit or reduced impact to the environment, and the risks of failing to control the pest. Validation of DSS is often limited to a small number of sites and seasons, as extensive field testing is prohibitively expensive. It would therefore be beneficial to have a method to estimate the value of a DSS using existing data sets gathered for other purposes. We present a theoretical framework for evaluating the value of DSS, and then describe how this can be applied in practice using four case studies of contrasting DSS under different data constraints. The four case studies include DSS that guide (i) the total dose of pesticide applied; (ii) the number of sprays required; (iii) the timing of the first fungicide application in a spray programme; and (iv) infection risk alerts. We demonstrate how our theoretical framework can be used to evaluate DSS, using existing field and literature data to infer the benefits and risks associated with their use. The limitations of using existing data are explored.

Evaluation of a novel palm-free fat supplement to reduce the carbon footprint of diets for dairy cows - Philip C. Garnsworthy; Neil Saunders; Jennifer R. Goodman (Animal Feed Science and Technology, 2024)

Asymmetric effects of hydroclimate extremes on eastern US tree growth: Implications on current demographic shifts and climate variability - Justin T. Maxwell; Tsun Fung Au; Steven A. Kannenberg; Grant L. Harley; Matthew P. Dannenberg; Darren L. Ficklin; Scott M. Robeson; Macarena Férriz; Michael C. Benson; Benjamin R. Lockwood; Kimberly A. Novick; Richard P. Phillips; et al. (Global Change Biology, 2024)
Forests around the world are experiencing changes due to climate variability and human land use. How these changes interact and influence the vulnerability of forests are not well understood. In the eastern United States, well‐documented anthropogenic disturbances and land‐use decisions, such as logging and fire suppression, have influenced forest species assemblages, leading to a demographic shift from forests dominated by xeric species to those dominated by mesic species. Contemporarily, the climate has changed and is expected to continue to warm and produce higher evaporative demand, imposing stronger drought stress on forest communities. Here, we use an extensive network of tree‐ring records from common hardwood species across ~100 sites and ~1300 trees in the eastern United States to examine the magnitude of growth response to both wet and dry climate extremes. We find that growth reductions during drought exceed the positive growth response to pluvials. Mesic species such as Liriodendron tulipifera and Acer saccharum , which are becoming more dominant, are more sensitive to drought than more xeric species, such as oaks ( Quercus ) and hickory ( Carya ), especially at moderate and extreme drought intensities. Although more extreme droughts produce a larger annual growth reduction, mild droughts resulted in the largest cumulative growth decreases due to their higher frequency. When using global climate model projections, all scenarios show drought frequency increasing substantially (3–9 times more likely) by 2100. Thus, the ongoing demographic shift toward more mesic species in the eastern United States combined with drier conditions results in larger drought‐induced growth declines, suggesting that drought will have an even larger impact on aboveground carbon uptake in the future in the eastern United States.

Transboundary movements of porbeagle sharks support need for continued cooperative research and management approaches - Jenny R. Bortoluzzi; Grace E. McNicholas; Andrew L. Jackson; C. Antonia Klöcker; Keno Ferter; Claudia Junge; Otte Bjelland; Adam Barnett; Austin J. Gallagher; Neil Hammerschlag; William K. Roche; Nicholas L. Payne (Fisheries Research, 2024)

Next Generation Risk Assessment approaches for advanced nanomaterials: Current status and future perspectives - Danail Hristozov; Elena Badetti; Paolo Bigini; Andrea Brunelli; Susan Dekkers; Luisa Diomede; Shareen H. Doak; Wouter Fransman; Agnieszka Gajewicz-Skretna; Elisa Giubilato; Laura Gómez-Cuadrado; Roland Grafström; et al. (NanoImpact, 2024)

Global mercury concentrations in biota: their use as a basis for a global biomonitoring framework - David C. Evers; Joshua T. Ackerman; Staffan Åkerblom; Dominique Bally; Nil Basu; Kevin Bishop; Nathalie Bodin; Hans Fredrik Veiteberg Braaten; Mark E. H. Burton; Paco Bustamante; Celia Chen; John Chételat; et al. (Ecotoxicology, 2024)
An important provision of the Minamata Convention on Mercury is to monitor and evaluate the effectiveness of the adopted measures and its implementation. Here, we describe for the first time currently available biotic mercury (Hg) data on a global scale to improve the understanding of global efforts to reduce the impact of Hg pollution on people and the environment. Data from the peer-reviewed literature were compiled in the Global Biotic Mercury Synthesis (GBMS) database (>550,000 data points). These data provide a foundation for establishing a biomonitoring framework needed to track Hg concentrations in biota globally. We describe Hg exposure in the taxa identified by the Minamata Convention: fish, sea turtles, birds, and marine mammals. Based on the GBMS database, Hg concentrations are presented at relevant geographic scales for continents and oceanic basins. We identify some effective regional templates for monitoring methylmercury (MeHg) availability in the environment, but overall illustrate that there is a general lack of regional biomonitoring initiatives around the world, especially in Africa, Australia, Indo-Pacific, Middle East, and South Atlantic and Pacific Oceans. Temporal trend data for Hg in biota are generally limited. Ecologically sensitive sites (where biota have above average MeHg tissue concentrations) have been identified throughout the world. Efforts to model and quantify ecosystem sensitivity locally, regionally, and globally could help establish effective and efficient biomonitoring programs. We present a framework for a global Hg biomonitoring network that includes a three-step continental and oceanic approach to integrate existing biomonitoring efforts and prioritize filling regional data gaps linked with key Hg sources. We describe a standardized approach that builds on an evidence-based evaluation to assess the Minamata Convention’s progress to reduce the impact of global Hg pollution on people and the environment.

In vitro insecticide resistance patterns in field strains of the sheep blowfly, Lucilia cuprina - Andrew C. Kotze; Neil H. Bagnall; Sarah D. George; Nicholas M. Rolls (Veterinary Parasitology, 2024)

Experimental modification of African wild dog movement and behavior using translocated conspecific scent - K. Whitney Hansen; Neil R. Jordan; Megan J. Claase; Justin P. Suraci; John W. McNutt; Aanya Dhruv; Christopher C. Wilmers (Biological Conservation, 2024)

Evidence for cryptic molting behavior in the trilobite Toxochasmops vormsiensis from the Upper Ordovician Katian Kõrgessaare Formation, Estonia - Russell D. C. Bicknell; Ernesto E. Vargas-Parra; Neil H. Landman; Helje Pärnaste (The Science of Nature, 2024)
Documentation of cryptic trilobite behavior has presented important insights into the paleoecology of this fully extinct arthropod group. One such example is the preservation of trilobites inside the remains of larger animals. To date, evidence for trilobites within cephalopods, gastropods, hyoliths, and other trilobites has been presented. Importantly, most of these interactions show trilobite molts, suggesting that trilobites used larger animals for protection during molting. To expand the record of molted trilobites within cephalopods, we present a unique case of a Toxochasmops vormsiensis trilobite within the body chamber of a Gorbyoceras textumaraneum nautiloid from the Upper Ordovician Kõrgessaare Formation of Estonia. By examining this material, we present new insights into the ecology of pterygometopid trilobites, highlighting how these forms used large cephalopods as areas to successfully molt.

Modeling wildland fire burn severity in California using a spatial Super Learner approach - Nicholas Simafranca; Bryant Willoughby; Erin O’Neil; Sophie Farr; Brian J. Reich; Naomi Giertych; Margaret C. Johnson; Madeleine A. Pascolini-Campbell (Environmental and Ecological Statistics, 2024)

Genome analysis of gyroviruses identified in waterfowl in Arizona (USA) - Shawnpreet Sahnan; Diego Olivo; Joy M. Custer; Rohan A. Bandoo; Danny Jackson; Michael C. Lund; Hannah McGraw; Melanie Regney; Victor Aguiar de Souza Penha; Julia Neil; Dean Drake; Kevin McGraw; et al. (Archives of Virology, 2024)

A quasi-geostrophic analysis of summertime southern African linear-regime westerly waves - Thando Ndarana; Tsholanang S. Rammopo; Mary-Jane M. Bopape; Neil C. G. Hart; Chris J. C. Reason; Hector Chikoore (Climate Dynamics, 2024)
Linear-regime westerly waves that propagate across the South African domain are often linked to well-known rainfall producing systems such as tropical temperate troughs and synoptic scale tropical low-pressure systems, and ridging South Atlantic Ocean anticyclones at the surface. It is accepted that the baroclinic waves that propagate across the domain provide the lifting mechanism that causes the required vertical motion for rainfall to occur. This study shows that there exists a jet streak embedded in these waves that is located downstream of the trough axis, to the east of which vertically upward motion is expected to occur. The entrance of the jet streak passes just south of the country, as the waves propagate past the domain. The study further shows that for this class of waves, the vertical motion that causes rainfall to occur is induced by the thermally direct transverse ageostrophic circulation that is located at this jet entrance. This is instead of the conventional upper air divergence that is located at the inflection point east of the trough axis. Using a method of decomposing the Q -vector into its transverse ( $${Q}_n$$ Q n ) and shear ( $${Q}_s$$ Q s ) components, the divergence fields of which are used to decompose the vertical motion into the corresponding components, i.e $$ω _n$$ ω n and $$ω _s$$ ω s , respectively; it was shown that the vertical motion over South Africa is explained more by the former than the latter. Therefore, the uplift over the country and that located at the infection point east of the trough are dynamically distinct processes. Taking the limitations of the quasi-geostrophic framework into consideration, the study concludes that during the passage of linear-regime waves vertical motion that might lead to rainfall is caused by the circulation at the jet entrance and not the divergence in the baroclinic wave.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Rethinking atoll futures: local resilience to global challenges - Sebastian Steibl; Paul S. Kench; Hillary S. Young; Alex S. Wegmann; Nick D. Holmes; Nancy Bunbury; Teurumereariki Hinano Teavai-Murphy; Neil Davies; Frank Murphy; James C. Russell (Trends in Ecology & Evolution, 2024)

Mapping the cellular landscape of Atlantic salmon head kidney by single cell and single nucleus transcriptomics - Adriana M.S. Andresen; Richard S. Taylor; Unni Grimholt; Rose Ruiz Daniels; Jianxuan Sun; Ross Dobie; Neil C. Henderson; Samuel A.M. Martin; Daniel J. Macqueen; Johanna H. Fosse (Fish & Shellfish Immunology, 2024)

Correction to: A stakeholder-guided marine heatwave hazard index for fisheries and aquaculture - Jules B. Kajtar; Neil J. Holbrook; Anna Lyth; Alistair J. Hobday; Craig N. Mundy; Sarah C. Ugalde (Climatic Change, 2024)

Size matters: Microherbivores make a big impact in coral aquaculture - Rachel C. Neil; Jonathan A. Barton; Winona Dougan; Symon Dworjanyn; Andrew Heyward; Benjamin Mos; David G. Bourne; Craig Humphrey (Aquaculture, 2024)

Aging of the sea urchin Centrostephanus rodgersii using demi-pyramid microstructure - Craig Blount; Duncan G. Worthington; Maria Byrne; Rowan C. Chick; Neil L. Andrew (Fisheries Research, 2024)

Inter-colony variation in predation, mercury burden and adult survival in a declining seabird - Anna M. Calvert; Sarah E. Gutowsky; David A. Fifield; Neil M. Burgess; Rachel Bryant; Gail S. Fraser; Carina Gjerdrum; April Hedd; Patricia L. Jones; Robert A. Mauck; Laura McFarlane Tranquilla; William A. Montevecchi; et al. (Science of The Total Environment, 2024)

Comment on: “Insights on the tectonic styles of the Red Sea rift using gravity and magnetic data” by Saada et al. (2021) - Neil C. Mitchell; Ian C.F. Stewart (Marine and Petroleum Geology, 2024)

Cross-adaptation from heat stress to hypoxia: A systematic review and exploratory meta-analysis - Ashley G.B. Willmott; Alicia G. Diment; Henry C. Chung; Carl A. James; Neil S. Maxwell; Justin D. Roberts; Oliver R. Gibson (Journal of Thermal Biology, 2024)

Cell atlas of the Atlantic salmon spleen reveals immune cell heterogeneity and cell-specific responses to bacterial infection - Jianxuan Sun; Rose Ruiz Daniels; Adam Balic; Adriana M.S. Andresen; Håvard Bjørgen; Ross Dobie; Neil C. Henderson; Erling Olaf Koppang; Samuel A.M. Martin; Johanna Hol Fosse; Richard S. Taylor; Daniel J. Macqueen (Fish & Shellfish Immunology, 2024)

Microplastic pollution on historic facades: Hidden ‘sink' or urban threat? - Katrin Wilhelm; Sam Woor; Michelle Jackson; Dania Albini; Neil Young; Phani Karamched; Miriam C. Policarpo Wright; Josep Grau-Bove; Scott Allan Orr; Jack Longman; Tim de Kock (Environmental Pollution, 2024)

A stakeholder-guided marine heatwave hazard index for fisheries and aquaculture - Jules B. Kajtar; Neil J. Holbrook; Anna Lyth; Alistair J. Hobday; Craig N. Mundy; Sarah C. Ugalde (Climatic Change, 2024)
Marine heatwaves pose an increasing threat to fisheries and aquaculture around the world under climate change. However, the threat has not been estimated for the coming decades in a form that meets the needs of these industries. Tasmanian fisheries and aquaculture in southeast Australia have been severely impacted by marine heatwaves in recent years, especially the oyster, abalone, and salmon industries. In a series of semi-structured interviews with key Tasmanian fishery and aquaculture stakeholders, information was gathered about the following: (i) the impacts they have experienced to date from marine heatwaves, (ii) their planning for future marine heatwaves, and (iii) the information that would be most useful to aid planning. Using CMIP6 historical and future simulations of sea surface temperatures around Tasmania, we developed a marine heatwave hazard index guided by these stakeholder conversations. The region experienced a severe marine heatwave during the austral summer of 2015/16, which has been used here as a reference point to define the index. Our marine heatwave hazard index shows that conditions like those experienced in 2015/16 are projected to occur approximately 1-in-5 years by the 2050s under a low emissions scenario (SSP1-2.6) or 1-in-2 years under a high emissions scenario (SSP5-8.5). Increased frequency of marine heatwaves will likely reduce productivity by both direct (mortality) and in-direct (ecosystem change, greater incidence of disease) impacts on target species. The illustrative hazard index is one step towards a marine heatwave risk index, which would also need to consider aspects of exposure and vulnerability to be of greater utility to stakeholders.

A Genome Wide Association Study (GWAS) Identifies SNPs Associated with Resistance to Tobacco Rattle Virus (TRV) and Potato Mop-Top Virus (PMTV) in a Tetraploid Mapping Population of Potato - Noelle L. Anglin; Shashi K. R. Yellarreddygari; Neil C. Gudmestad; Vidyasagar Sathuvalli; Charles R. Brown; Max Feldman; Walter S. De Jong; David S. Douches; Richard G. Novy; Joseph J. Coombs (American Journal of Potato Research, 2024)

Weather conditions and seasonal variability of limited surface visibility at Greenland coastal locations - Neil F. Laird; Caitlin C. Crossett; Gabrielle A. Keaton; Leah N. Hopson (International Journal of Climatology, 2024)
Adverse weather has been shown to be spatially and temporally variable across high‐latitude locations. The current study provides a unique investigation of limited surface visibility time periods at five coastal Greenland locations from 1979 to 2018 and identifies the coincident adverse weather, as well as the local and large‐scale atmospheric conditions during limited surface visibility time periods. Locations on the east coast of Greenland have the largest percentage of hours with limited visibility each month with maxima during February. Western and southern coastal locations have fewer occurrences of limited visibility. Warm‐season maxima are present in the northern locations, while warm‐season minima occur at all other locations. Fog is reported during each month at all five stations, however, a substantial increase of hours occurs at the northern and eastern stations during the typical melt season on Greenland. There is a seasonal difference in the percent of limited visibility hours linked to precipitation with a minimum in the warm season and maximum across the cold season. Limited visibility attributed to precipitation generally has the largest percentage of hours each month except for the northern and eastern locations during the melt season. The location and number of cyclonic circulations, as well as the spatial scale of troughs, across northeastern Canada and the North Atlantic Ocean greatly influence the adverse weather linked to prolonged limited surface visibility events. Limited visibility events at Thule, Greenland during both the warm and cold seasons are largely influenced by the presence and intensity of a cyclone over northeastern Canada. At Danmarkshavn, Greenland limited visibility events in both seasons generally have a cyclone positioned to the east, an area of higher pressure over Greenland and a cyclone positioned to the west of Greenland.

Towards a combined human-natural system approach in the Northern Red Sea Region: Ecological challenges, sustainable development, and community engagement - Ahmed Eladawy; Neil C. Mitchell; Takashi Nakamura; Momen El-Husseiny; Yuta A. Takagi; Nabil Elhady; Brook Muller; Sara Abdel-Hamid; Asmaa Mohammed; Kazuo Nadaoka; J.P. Walsh (Marine Policy, 2024)

Corrigendum to “Oceanic seismotectonics from regional earthquake recordings: The 4–5°N Mid-Atlantic Ridge” [de Melo, G. W., Mitchell, N. C., Zahradnik, J., Dias, F., & do Nascimento, A. F. (2021). Tectonophysics, 819, 229063]. - G.W.S. de Melo; Neil C. Mitchell; Jiri Zahradnik (Tectonophysics, 2024)

Measuring the 3-30-300 rule to help cities meet nature access thresholds - M.H.E.M. Browning; D.H. Locke; C. Konijnendijk; S.M. Labib; A. Rigolon; R. Yeager; M. Bardhan; A. Berland; P. Dadvand; M. Helbich; F. Li; H. Li; et al. (Science of The Total Environment, 2024)

Tunnel valley formation beneath deglaciating mid-latitude ice sheets: Observations and modelling - James D. Kirkham; Kelly A. Hogan; Robert D. Larter; Neil S. Arnold; Jeremy C. Ely; Chris D. Clark; Ed Self; Ken Games; Mads Huuse; Margaret A. Stewart; Dag Ottesen; Julian A. Dowdeswell (Quaternary Science Reviews, 2024)

Root aphid (Aploneura lentisci) population size on perennial ryegrass is determined by drought and endophyte strain - Katrin G. Hewitt; Rainer W. Hofmann; Oliver J. Ball; Neil Cox; Racheal H. Bryant; Sarah C. Finch; Alison J. Popay (Journal of Pest Science, 2024)
Climate change is anticipated to lead to an increase in the occurrence and intensity of drought and fluctuations in insect cycles that will challenge modern pasture systems. Feeding by root aphids such as Aploneura lentisci Pass. can be a significant challenge to pastures. These below-ground living aphids are commonly found in New Zealand and Australia, feeding year-round on the roots of graminaceous plants such as perennial ryegrass ( Lolium perenne L.). Some strains of the fungal endophyte Epichloë festucae var. lolii in perennial ryegrass can provide protection against root aphids and greater resilience under drought, contributing to higher persistency and growth than endophyte-free plants. However, the interaction between insect pressure and drought is not understood. This study examined the effect of drought on root aphid populations and plant performance in perennial ryegrass plants relative to endophyte status (±) and endophyte strain (AR37, NZ CT ) in a glasshouse experiment. Plants were cloned across the drought and well-watered treatments, and half of the plants were inoculated with root aphids, whilst half of the plants were treated with insecticide. Endophyte infection with strain NZ CT and AR37 reduced root aphid numbers. Aphid populations were significantly higher in drought-stressed than in well-watered plants in both endophyte-infected and endophyte-free treatments. Under drought conditions, root aphid populations were increased 4-fold in NZ CT and 8-fold in AR37 and endophyte-free plants in comparison with their well-watered counterparts. Root aphids reduced shoot dry weight by 16% in drought-exposed and 26% in well-watered plants in comparison with their insecticide-treated counterparts whilst reducing root biomass by 49%. Our results suggest that root aphids are likely able to exploit the higher availability of amino acids in the plant sap of drought-exposed plants. This study provides evidence that climate change-mediated impacts of root aphids could reduce production in perennial ryegrass-dominant pastures. However, field trials would be necessary to determine whether this effect is seen in situ, where numerous additional factors will be operating at the same time.

The ocean-continent transition in the Western Central Red Sea - Neil C. Mitchell; Jonas Preine; Oke I. Okwokwo; A.Y. Izzeldin; Nico Augustin; Ian C.F. Stewart (Journal of African Earth Sciences, 2023)

Distinct patterns of inheritance shape life‐history traits in steelhead trout - Anne K. Beulke; Alicia Abadía‐Cardoso; Devon E. Pearse; Laura C. Goetz; Neil F. Thompson; Eric C. Anderson; John Carlos Garza (Molecular Ecology, 2023)
Life‐history variation is the raw material of adaptation, and understanding its genetic and environmental underpinnings is key to designing effective conservation strategies. We used large‐scale genetic pedigree reconstruction of anadromous steelhead trout ( Oncorhynchus mykiss ) from the Russian River, CA, USA, to elucidate sex‐specific patterns of life‐history traits and their heritability. SNP data from adults returning from sea over a 14‐year period were used to identify 13,474 parent–offspring trios. These pedigrees were used to determine age structure, size distributions and family sizes for these fish, as well as to estimate the heritability of two key life‐history traits, spawn date and age at maturity (first reproduction). Spawn date was highly heritable ( h 2 = 0.73) and had a cross‐sex genetic correlation near unity. We provide the first estimate of heritability for age at maturity in ocean‐going fish from this species and found it to be highly heritable ( h 2 from 0.29 to 0.62, depending on sex and method), with a much lower genetic correlation across sexes. We also evaluated genotypes at a migration‐associated inversion polymorphism and found sex‐specific correlations with age at maturity. The significant heritability of these two key reproductive traits in these imperiled fish, and their patterns of inheritance in the two sexes, is consistent with predictions of both natural and sexually antagonistic selection (sexes experience opposing selection pressures). This emphasizes the importance of anthropogenic factors, including hatchery practices and ecosystem modifications, in shaping the fitness of this species, thus providing important guidance for management and conservation efforts.

Increased grain yield in modern genotypes of spring wheat for dryland cultivation in northwest China is associated with the decreased allocation of carbon to roots - Tao Feng; Yong-He Zhu; Ning Chai; Xin-Tan Zhang; Yan-Lei Du; Neil C. Turner; Pengzhen Du; Feng-Min Li (Field Crops Research, 2023)

Constraining the eruption history of Rangitoto volcano, New Zealand, using palaeomagnetic data - Megan L. Allington; Andreas Nilsson; Mimi J. Hill; Neil Suttie; Dimitra Daniil; Ingeborg Hjorth; Linda Aulin; Paul C. Augustinus; Phil Shane (Quaternary Geochronology, 2023)

Anatomy of fractures: Quantifying fracture geometry utilizing X-ray computed tomography in a chalk-marl reservoir; the Lower Cretaceous Valdemar Field (Danish Central Graben) - Aslaug C. Glad; Armin Afrough; Frédéric Amour; Carlos A.S. Ferreira; Neil Price; Ole R. Clausen; Hamidreza M. Nick (Journal of Structural Geology, 2023)

A novel use of a handheld elemental scanner for authenticating prawn provenance - Jasmin C. Martino; Jagoda Crawford; Patricia Gadd; Jesmond Sammut; Neil Saintilan; Debashish Mazumder (Food Control, 2023)

Interspecific differences in drought and pluvial responses for Quercus alba and Quercus rubra across the eastern United States - Ben R. Lockwood; Justin T. Maxwell; Sander O. Denham; Scott M. Robeson; David C. LeBlanc; Neil Pederson; Kimberly A. Novick; Tsun Fung Au (Agricultural and Forest Meteorology, 2023)

Parasite manipulation of host phenotypes inferred from transcriptional analyses in a trematode‐amphipod system - David M. Rand; Joaquin C. B. Nunez; Shawn Williams; Stephen Rong; John T. Burley; Kimberly B. Neil; Adam N. Spierer; Wilson McKerrow; David S. Johnson; Yevgeniy Raynes; Thomas J. Fayton; Nicholas Skvir; et al. (Molecular Ecology, 2023)
Manipulation of host phenotypes by parasites is hypothesized to be an adaptive strategy enhancing parasite transmission across hosts and generations. Characterizing the molecular mechanisms of manipulation is important to advance our understanding of host–parasite coevolution. The trematode ( Levinseniella byrdi ) is known to alter the colour and behaviour of its amphipod host ( Orchestia grillus ) presumably increasing predation of amphipods which enhances trematode transmission through its life cycle. We sampled 24 infected and 24 uninfected amphipods from a salt marsh in Massachusetts to perform differential gene expression analysis. In addition, we constructed novel genomic tools for O. grillus including a de novo genome and transcriptome. We discovered that trematode infection results in upregulation of amphipod transcripts associated with pigmentation and detection of external stimuli, and downregulation of multiple amphipod transcripts implicated in invertebrate immune responses, such as vacuolar ATPase genes. We hypothesize that suppression of immune genes and the altered expression of genes associated with coloration and behaviour may allow the trematode to persist in the amphipod and engage in further biochemical manipulation that promotes transmission. The genomic tools and transcriptomic analyses reported provide new opportunities to discover how parasites alter diverse pathways underlying host phenotypic changes in natural populations.

Planning and licensing for marine aquaculture - Lynne Falconer; Karl Cutajar; Amalia Krupandan; Elisa Capuzzo; Richard A. Corner; Tim Ellis; Keith Jeffery; Eirik Mikkelsen; Heather Moore; Francis X. O'Beirn; Pauline O'Donohoe; Neil M. Ruane; et al. (Reviews in Aquaculture, 2023)
Marine aquaculture has the potential to increase its contribution to the global food system and provide valuable ecosystem services, but appropriate planning, licensing and regulation systems must be in place to enable sustainable development. At present, approaches vary considerably throughout the world, and several national and regional investigations have highlighted the need for reforms if marine aquaculture is to fulfil its potential. This article aims to map and evaluate the challenges of planning and licensing for growth of sustainable marine aquaculture. Despite the range of species, production systems and circumstances, this study found a number of common themes in the literature; complicated and fragmented approaches to planning and licensing, property rights and the licence to operate, competition for space and marine spatial planning, emerging species and diversifying marine aquaculture production (seaweed production, Integrated Multi‐Trophic Aquaculture [IMTA], nutrient and carbon offsetting with aquaculture, offshore aquaculture and co‐location and multiuse platforms), and the need to address knowledge gaps and use of decision‐support tools. Planning and licensing can be highly complicated, so the UK is used as a case study to show more detailed examples that highlight the range of challenges and uncertainty that industry, regulators and policymakers face across interacting jurisdictions. There are many complexities, but this study shows that many countries have undergone, or are undergoing, similar challenges, suggesting that lessons can be learned by sharing knowledge and experiences, even across different species and production systems, rather than having a more insular focus.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Correction to: Distinguishing science from pseudoscience in commercial respiratory interventions: an evidence-based guide for health and exercise professionals - Camilla R. Illidi; Lee M. Romer; Michael A. Johnson; Neil C. Williams; Harry B. Rossiter; Richard Casaburi; Nicholas B. Tiller (European Journal of Applied Physiology, 2023)

Distinguishing science from pseudoscience in commercial respiratory interventions: an evidence-based guide for health and exercise professionals - Camilla R. Illidi; Lee M. Romer; Michael A. Johnson; Neil C. Williams; Harry B. Rossiter; Richard Casaburi; Nicholas B. Tiller (European Journal of Applied Physiology, 2023)

Cerebrospinal fluid levels of 5-HIAA and dopamine in people with HIV and depression - Rong Fu; Hyder Jinnah; J. Lucas Mckay; Andrew H. Miller; Jennifer C. Felger; Eugene W. Farber; Sanjay Sharma; Neil Whicker; Raeanne C. Moore; Donald Franklin; Scott L. Letendre; Albert M. Anderson (Journal of NeuroVirology, 2023)

Herbaceous vegetation responses to experimental fire in savannas and forests depend on biome and climate - Zachary J. Gold; Adam F. A. Pellegrini; Tyler K. Refsland; Romina J. Andrioli; Marlin L. Bowles; Dale G. Brockway; Neil Burrows; Augusto C. Franco; Steve W. Hallgren; Sarah E. Hobbie; William A. Hoffmann; Kevin P. Kirkman; et al. (Ecology Letters, 2023)
Fire–vegetation feedbacks potentially maintain global savanna and forest distributions. Accordingly, vegetation in savanna and forest ecosystems should have differential responses to fire, but fire response data for herbaceous vegetation have yet to be synthesized across biomes. Here, we examined herbaceous vegetation responses to experimental fire at 30 sites spanning four continents. Across a variety of metrics, herbaceous vegetation increased in abundance where fire was applied, with larger responses to fire in wetter and in cooler and/or less seasonal systems. Compared to forests, savannas were associated with a 4.8 (±0.4) times larger difference in herbaceous vegetation abundance for burned versus unburned plots. In particular, grass cover decreased with fire exclusion in savannas, largely via decreases in C 4 grass cover, whereas changes in fire frequency had a relatively weak effect on grass cover in forests. These differential responses underscore the importance of fire for maintaining the vegetation structure of savannas and forests.

Broad-scale benthic habitat classification of the South Atlantic - Kirsty A. McQuaid; Amelia E.H. Bridges; Kerry L. Howell; Tiago B.R. Gandra; Vitor de Souza; Jock C. Currie; Oliver T. Hogg; Tabitha R.R. Pearman; James B. Bell; Lara J. Atkinson; Diane Baum; Jarbas Bonetti; et al. (Progress in Oceanography, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Earthquake, floods and changing land use history: A 200-year overview of environmental changes in Selenga River basin as indicated by n-alkanes and related proxies in sediments from shallow lakes - César C. Martins; Jennifer K. Adams; Handong Yang; Alexander A. Shchetnikov; Maikon Di Domenico; Neil L. Rose; Anson W. Mackay (Science of The Total Environment, 2023)

Hydrologic restoration of anthropoentically altered springs in the Sheldon National Wildlife Refuge in the Great Basin, USA - Leah N. Knighton; Steven L. Petersen; Gail H. Collins; Loreen Allphin; Neil C. Hansen; Haley B. Johnston; Russell B. Rader (Journal of Arid Environments, 2023)

Comparison of machine learning methods emulating process driven crop models - David B. Johnston; Keith G. Pembleton; Neil I. Huth; Ravinesh C. Deo (Environmental Modelling & Software, 2023)

Geothermal energy production adversely affects a sensitive indicator species within sagebrush ecosystems in western North America - Peter S. Coates; Brian G. Prochazka; Shawn T. O'Neil; Sarah C. Webster; Shawn Espinosa; Mark A. Ricca; Steven R. Mathews; Michael Casazza; David J. Delehanty (Biological Conservation, 2023)

Maternal Undernutrition Induces Cell Signalling and Metabolic Dysfunction in Undifferentiated Mouse Embryonic Stem Cells - Pooja Khurana; Andrew Cox; Barira Islam; Judith J. Eckert; Sandrine Willaime-Morawek; Joanna M. Gould; Neil R. Smyth; Patrick C. McHugh; Tom P. Fleming (Stem Cell Reviews and Reports, 2023)
Peri-conceptional environment can induce permanent changes in embryo phenotype which alter development and associate with later disease susceptibility. Thus, mouse maternal low protein diet (LPD) fed exclusively during preimplantation is sufficient to lead to cardiovascular, metabolic and neurological dysfunction in adult offspring. Embryonic stem cell (ESC) lines were generated from LPD and control NPD C57BL/6 blastocysts and characterised by transcriptomics, metabolomics, bioinformatics and molecular/cellular studies to assess early potential mechanisms in dietary environmental programming. Previously, we showed these lines retain cellular and epigenetic characteristics of LPD and NPD embryos after several passages. Here, three main changes were identified in LPD ESC lines. First, their derivation capacity was reduced but pluripotency marker expression was similar to controls. Second, LPD lines had impaired Mitogen-activated protein kinase (MAPK) pathway with altered gene expression of several regulators (e.g., Maff , Rassf1 , JunD ), reduced ERK1/2 signalling capacity and poorer cell survival characteristics which may contribute to reduced derivation. Third, LPD lines had impaired glucose metabolism comprising reduced upstream enzyme expression (e.g., Gpi, Mpi ) and accumulation of metabolites (e.g., glucose-6-P, fructose-6-P) above the phosphofructokinase (PFK) gateway with PFK enzyme activity reduced. ESC lines may therefore permit investigation of peri-conceptional programming mechanisms with reduced need for animal experimentation. Graphical Abstract

Absolute quantification of cellular levels of photosynthesis-related proteins in Synechocystis sp. PCC 6803 - Philip J. Jackson; Andrew Hitchcock; Amanda A. Brindley; Mark J. Dickman; C. Neil Hunter (Photosynthesis Research, 2023)
Quantifying cellular components is a basic and important step for understanding how a cell works, how it responds to environmental changes, and for re-engineering cells to produce valuable metabolites and increased biomass. We quantified proteins in the model cyanobacterium Synechocystis sp. PCC 6803 given the general importance of cyanobacteria for global photosynthesis, for synthetic biology and biotechnology research, and their ancestral relationship to the chloroplasts of plants. Four mass spectrometry methods were used to quantify cellular components involved in the biosynthesis of chlorophyll, carotenoid and bilin pigments, membrane assembly, the light reactions of photosynthesis, fixation of carbon dioxide and nitrogen, and hydrogen and sulfur metabolism. Components of biosynthetic pathways, such as those for chlorophyll or for photosystem II assembly, range between 1000 and 10,000 copies per cell, but can be tenfold higher for CO 2 fixation enzymes. The most abundant subunits are those for photosystem I, with around 100,000 copies per cell, approximately 2 to fivefold higher than for photosystem II and ATP synthase, and 5–20 fold more than for the cytochrome b 6 f complex. Disparities between numbers of pathway enzymes, between components of electron transfer chains, and between subunits within complexes indicate possible control points for biosynthetic processes, bioenergetic reactions and for the assembly of multisubunit complexes.

Observation-based estimates of volume, heat, and freshwater exchanges between the subpolar North Atlantic interior, its boundary currents, and the atmosphere - Sam C. Jones; Neil J. Fraser; Stuart A. Cunningham; Alan D. Fox; Mark E. Inall (Ocean Science, 2023)
The Atlantic Meridional Overturning Circulation (AMOC) transports heat and salt between the tropical Atlantic and Arctic oceans. The interior of the North Atlantic subpolar gyre (SPG) is responsible for the much of the water mass transformation in the AMOC, and the export of this water to intensified boundary currents is crucial for projecting air–sea interaction onto the strength of the AMOC. However, the magnitude and location of exchange between the SPG and the boundary remains unclear. We present a novel climatology of the SPG boundary using quality-controlled CTD (conductivity–temperature–depth) and Argo hydrography, defining the SPG interior as the oceanic region bounded by 47∘ N and the 1000 m isobath. From this hydrography we find geostrophic flow out of the SPG around much of the boundary with minimal seasonality. The horizontal density gradient is reversed around western Greenland, where the geostrophic flow is into the SPG. Surface Ekman forcing drives net flow out of the SPG in all seasons with pronounced seasonality, varying between 2.45 ± 0.73 Sv in the summer and 7.70 ± 2.90 Sv in the winter. We estimate heat advected into the SPG to be between 0.14 ± 0.05 PW in the winter and 0.23 ± 0.05 PW in the spring, and freshwater advected out of the SPG to be between 0.07 ± 0.02 Sv in the summer and 0.15 ± 0.02 Sv in the autumn. These estimates approximately balance the surface heat and freshwater fluxes over the SPG domain. Overturning in the SPG varies seasonally, with a minimum of 6.20 ± 1.40 Sv in the autumn and a maximum of 10.17 ± 1.91 Sv in the spring, with surface Ekman the most likely mediator of this variability. The density of maximum overturning is at 27.30 kg m−3, with a second, smaller maximum at 27.54 kg m−3. Upper waters (σ0 27.54 kg m−3) exiting to the south. Our results support the present consensus that the formation and pre-conditioning of Subpolar Mode Water in the north-eastern Atlantic is a key determinant of AMOC strength.

Species portfolio effects dominate seasonal zooplankton stabilization within a large temperate lake - Reilly F. O'Connor; Bailey C. McMeans; Neil Rooney; Matthew M. Guzzo; Joelle D. Young; Kevin S. McCann (Ecology, 2023)
Portfolio effects (PEs) in ecology refer to the suite of phenomenon where the temporal variation of aggregate ecosystem properties (i.e., abundance) is lower than that of their ecosystem components. An example of this is where differential responses of species to environmental variation generate stability at higher levels of ecological organization (e.g., local community, metapopulation, metacommunity). Most of the research examining such PEs has focused on spatial or interannual variation of ecosystems; however, as global change continues to alter seasonality and ecosystem functioning, understanding the underlying food web structures that help maintain stability at multiple spatial and temporal scales is critical to managing ecological systems. Recent advances investigating diversity‐stability relationships has led to the development of frameworks that incorporate a metacommunity perspective which allows for the partitioning of PEs across organizational scales (i.e., local community, metapopulation, cross‐community, metacommunity) from local population dynamics (total). This partitioning yields insights into the mechanisms that generate observed PEs in nature. Here, we employed one of these recently developed frameworks on a temporally (1986–1999, 2008–2019) and spatially (five sampling stations, local communities) extensive data set of zooplankton abundance (e.g., density) within a large temperate lake to investigate how temporal (seasonal) and spatial (among site) PEs influence stability within the zooplankton metacommunity. We found that seasonal asynchrony of different zooplankton species within local communities and across communities generated the vast majority of stabilization, while spatial (i.e., metapopulation) dynamics were more synchronous and contributed little to overall system stability. Furthermore, significantly positive diversity‐asynchrony relationships at the total, local‐ and cross‐community scales were found as asynchrony was positively correlated with local Shannon diversity. Last, a comparison of PEs over the time periods, during which significant local and global changes (i.e., climate warming, invasive species) have occurred suggests that PEs may be eroding, as increasingly synchronous dynamics and declining diversity in recent years have led to a rise in metacommunity variability. We end by arguing for the critical importance of understanding seasonally driven stabilizing mechanisms as local and global changes threaten to fundamentally alter seasonal signals with potentially strong implications for the structures that lend stability to ecosystems.

High temporal resolution records of outdoor and indoor airborne microplastics - Lucy C. Boakes; Ian R. Patmore; Chiara E. P. Bancone; Neil L. Rose (Environmental Science and Pollution Research, 2023)
There is increasing concern regarding airborne microplastics, but to date, studies have typically used coarse interval sampling (a day or longer) to generate deposition and concentration estimates. In this proof-of-concept study, we used a Burkard volumetric spore trap (intake 10 L min −1 ; recording airborne particulates onto an adhesive-coated tape moving at 2 mm hr −1 ) to assess whether this approach has potential to record airborne microplastics at an hourly resolution, thereby providing detailed diurnal patterns. Simultaneous sampling at outdoor and indoor locations at rural and urban sites showed clear daily and weekly patterns in microplastic concentrations which may be related to people and vehicle movement. Indoor residential concentrations of suspected microplastics were the highest (reaching hourly concentrations of 40–50 m −3 ), whilst rural outdoor concentrations were very low (typically 1–2 m −3 h −1 ). Whilst the approach shows great potential for high resolution data generation, further development is required for spectroscopic analysis and hence chemical confirmation of visual microplastic identification.

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Probabilistic inversion of audio-frequency magnetotelluric data and application to cover thickness estimation for mineral exploration in Australia - Wenping Jiang; Ross C. Brodie; Jingming Duan; Ian Roach; Neil Symington; Anandaroop Ray; James Goodwin (Journal of Applied Geophysics, 2023)

Conceptualizing a probabilistic risk and loss assessment framework for wildfires - Negar Elhami-Khorasani; Hamed Ebrahimian; Lawrence Buja; Susan L. Cutter; Branko Kosovic; Neil Lareau; Brian J. Meacham; Eric Rowell; Ertugrul Taciroglu; Matthew P. Thompson; Adam C. Watts (Natural Hazards, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Juvenile age and available coral species modulate transition probability from herbivory to corallivory in Acanthaster cf. solaris (Crown-of-Thorns Seastar) - Rachel C. Neil; Maria Gomez Cabrera; Sven Uthicke (Coral Reefs, 2022)
Prior to transitioning to a coral diet, juvenile Acanthaster cf. solaris , the Crown-of-Thorns Seastar (COTS), feed on crustose coralline algae. Although a detailed understanding of juvenile ecology is crucial to predict and prevent outbreaks, the exact timing of the transition is unresolved. Two experiments were conducted to measure time and size of COTS at the transition, and investigate potential modulating effects of different coral species. COTS began early transitions at similar sizes (7.5–8.5 mm), and these first transitions were observed around 136–145 d. Between 175 and 191 d, a 50% transition in the presence of Acropora tenuis was measured. After 175d, the percentage of COTS cohorts that had transitioned was significantly lower in A. millepora (38%) and Stylophora pistillata (7%) compared to A. tenuis (51%). These data fill important knowledge gaps in juvenile ecology, and the influence of coral species on transition suggests an undescribed feedback mechanism between prey and predator.

A stochastic model for estimating sustainable limits to wildlife mortality in a changing world - Oliver Manlik; Robert C. Lacy; William B. Sherwin; Hugh Finn; Neil R. Loneragan; Simon J. Allen (Conservation Biology, 2022)
Human‐caused mortality of wildlife is a pervasive threat to biodiversity. Assessing the population‐level impact of fisheries bycatch and other human‐caused mortality of wildlife has typically relied upon deterministic methods. However, population declines are often accelerated by stochastic factors that are not accounted for in such conventional methods. Building on the widely applied potential biological removal (PBR) equation, we devised a new population modeling approach for estimating sustainable limits to human‐caused mortality and applied it in a case study of bottlenose dolphins affected by capture in an Australian demersal otter trawl fishery. Our approach, termed sustainable anthropogenic mortality in stochastic environments (SAMSE), incorporates environmental and demographic stochasticity, including the dependency of offspring on their mothers. The SAMSE limit is the maximum number of individuals that can be removed without causing negative stochastic population growth. We calculated a PBR of 16.2 dolphins per year based on the best abundance estimate available. In contrast, the SAMSE model indicated that only 2.3–8.0 dolphins could be removed annually without causing a population decline in a stochastic environment. These results suggest that reported bycatch rates are unsustainable in the long term, unless reproductive rates are consistently higher than average. The difference between the deterministic PBR calculation and the SAMSE limits showed that deterministic approaches may underestimate the true impact of human‐caused mortality of wildlife. This highlights the importance of integrating stochasticity when evaluating the impact of bycatch or other human‐caused mortality on wildlife, such as hunting, lethal control measures, and wind turbine collisions. Although population viability analysis (PVA) has been used to evaluate the impact of human‐caused mortality, SAMSE represents a novel PVA framework that incorporates stochasticity for estimating acceptable levels of human‐caused mortality. It offers a broadly applicable, stochastic addition to the demographic toolbox to evaluate the impact of human‐caused mortality on wildlife.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Susceptibility of Caribbean Brain Coral Recruits to Stony Coral Tissue Loss Disease (SCTLD) - Olivia M. Williamson; Caroline E. Dennison; Keri L. O’Neil; Andrew C. Baker (Frontiers in Marine Science, 2022)
Stony coral tissue loss disease (SCTLD) has devastated coral populations along Florida’s Coral Reef and beyond. Although widespread infection and mortality of adult colonies have been documented, no studies have yet investigated the susceptibility of recruits to this disease. Here, we subjected eight-month-old Diploria labyrinthiformis recruits and four-month-old Colpophyllia natans recruits to two sequential exposures to SCTLD in the laboratory to track infection and assess potential resilience. Both species began to develop lesions as early as 48 h after exposure began. During the first exposure, 59.6% of C. natans recruits lost all tissue (died) within two to eight days of developing lesions, whereas D. labyrinthiformis recruits experienced slower tissue loss and minimal eventual mortality. In C. natans , larger recruits and those fused into groups of multiple genets (chimeras) exhibited the highest survivorship. In contrast, smaller and/or single (ungrouped) recruits had the lowest survivorship (9.9 - 24.8%). After 20 days, a second SCTLD exposure was delivered to further test resistance in remaining recruits, and all recruits of both species succumbed within six days. Although no recruits showed absolute resistance to SCTLD following repeated exposures, our results provide evidence that interactions between size and chimerism can impact relative resistance in C. natans . This study represents the first report of SCTLD in Caribbean coral recruits and carries implications for natural species recovery and reef restoration efforts. Additional research on the susceptibility of coral juveniles to SCTLD is urgently needed, to include different species, locations, parents, and algal symbionts, with the goals of assessing relative susceptibility and identifying potential sources of resilience for this critical life history stage.

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

From Surface Water to the Deep Sea: A Review on Factors Affecting the Biodegradation of Spilled Oil in Marine Environment - Hernando Pactao Bacosa; Sheila Mae B. Ancla; Cris Gel Loui A. Arcadio; John Russel A. Dalogdog; Dioniela Mae C. Ellos; Heather Dale A. Hayag; Jiza Gay P. Jarabe; Ahl Jimhar T. Karim; Carl Kenneth P. Navarro; Mae Princess I. Palma; Rodolfo A. Romarate; Kaye M. Similatan; et al. (Journal of Marine Science and Engineering, 2022)
Over the past century, the demand for petroleum products has increased rapidly, leading to higher oil extraction, processing and transportation, which result in numerous oil spills in coastal-marine environments. As the spilled oil can negatively affect the coastal-marine ecosystems, its transport and fates captured a significant interest of the scientific community and regulatory agencies. Typically, the environment has natural mechanisms (e.g., photooxidation, biodegradation, evaporation) to weather/degrade and remove the spilled oil from the environment. Among various oil weathering mechanisms, biodegradation by naturally occurring bacterial populations removes a majority of spilled oil, thus the focus on bioremediation has increased significantly. Helping in the marginal recognition of this promising technique for oil-spill degradation, this paper reviews recently published articles that will help broaden the understanding of the factors affecting biodegradation of spilled oil in coastal-marine environments. The goal of this review is to examine the effects of various environmental variables that contribute to oil degradation in the coastal-marine environments, as well as the factors that influence these processes. Physico-chemical parameters such as temperature, oxygen level, pressure, shoreline energy, salinity, and pH are taken into account. In general, increase in temperature, exposure to sunlight (photooxidation), dissolved oxygen (DO), nutrients (nitrogen, phosphorous and potassium), shoreline energy (physical advection—waves) and diverse hydrocarbon-degrading microorganisms consortium were found to increase spilled oil degradation in marine environments. In contrast, higher initial oil concentration and seawater pressure can lower oil degradation rates. There is limited information on the influences of seawater pH and salinity on oil degradation, thus warranting additional research. This comprehensive review can be used as a guide for bioremediation modeling and mitigating future oil spill pollution in the marine environment by utilizing the bacteria adapted to certain conditions.

The evolutionary pathways for local adaptation in mountain hares - Iwona Giska; João Pimenta; Liliana Farelo; Pierre Boursot; Klaus Hackländer; Hannes Jenny; Neil Reid; W. Ian Montgomery; Paulo A. Prodöhl; Paulo C. Alves; José Melo‐Ferreira (Molecular Ecology, 2022)
Understanding the evolution of local adaptations is a central aim of evolutionary biology and key for the identification of unique populations and lineages of conservation relevance. By combining RAD sequencing and whole‐genome sequencing, we identify genetic signatures of local adaptation in mountain hares ( Lepus timidus ) from isolated and distinctive habitats of its wide distribution: Ireland, the Alps and Fennoscandia. Demographic modelling suggested that the split of these mountain hares occurred around 20 thousand years ago, providing the opportunity to study adaptive evolution over a short timescale. Using genome‐wide scans, we identified signatures of extreme differentiation among hares from distinct geographic areas that overlap with area‐specific selective sweeps, suggesting targets for local adaptation. Several identified candidate genes are associated with traits related to the uniqueness of the different environments inhabited by the three groups of mountain hares, including coat colour, ability to live at high altitudes and variation in body size. In Irish mountain hares, a variant of ASIP , a gene previously implicated in introgression‐driven winter coat colour variation in mountain and snowshoe hares ( L . americanus ), may underlie brown winter coats, reinforcing the repeated nature of evolution at ASIP moulding adaptive seasonal colouration. Comparative genomic analyses across several hare species suggested that mountain hares’ adaptive variants appear predominantly species‐specific. However, using coalescent simulations, we also show instances where the candidate adaptive variants have been introduced via introgressive hybridization. Our study shows that standing adaptive variation, including that introgressed from other species, was a crucial component of the post‐glacial dynamics of species.

Phylogenetics of tobacco rattle virus isolates from potato (Solanum tuberosum L.) in the USA: a multi-gene approach to evolutionary lineage - Lindani Moyo; Gaurav Raikhy; Aflaq Hamid; Ipsita Mallik; Neil C. Gudmestad; Stewart Gray; Hanu R. Pappu (Virus Genes, 2022)

Can a key boreal Calanus copepod species now complete its life-cycle in the Arctic? Evidence and implications for Arctic food-webs - Geraint A. Tarling; Jennifer J. Freer; Neil S. Banas; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn B. Cook; Finlo R. Cottier; Malin Daase; Magnus L. Johnson; Kim S. Last; Penelope K. Lindeque; et al. (Ambio, 2022)
The changing Arctic environment is affecting zooplankton that support its abundant wildlife. We examined how these changes are influencing a key zooplankton species, Calanus finmarchicus , principally found in the North Atlantic but expatriated to the Arctic. Close to the ice-edge in the Fram Strait, we identified areas that, since the 1980s, are increasingly favourable to C. finmarchicus . Field-sampling revealed part of the population there to be capable of amassing enough reserves to overwinter. Early developmental stages were also present in early summer, suggesting successful local recruitment. This extension to suitable C. finmarchicus habitat is most likely facilitated by the long-term retreat of the ice-edge, allowing phytoplankton to bloom earlier and for longer and through higher temperatures increasing copepod developmental rates. The increased capacity for this species to complete its life-cycle and prosper in the Fram Strait can change community structure, with large consequences to regional food-webs.

Biogeochemical consequences of a changing Arctic shelf seafloor ecosystem - Christian März; Felipe S. Freitas; Johan C. Faust; Jasmin A. Godbold; Sian F. Henley; Allyson C. Tessin; Geoffrey D. Abbott; Ruth Airs; Sandra Arndt; David K. A. Barnes; Laura J. Grange; Neil D. Gray; et al. (Ambio, 2022)
Unprecedented and dramatic transformations are occurring in the Arctic in response to climate change, but academic, public, and political discourse has disproportionately focussed on the most visible and direct aspects of change, including sea ice melt, permafrost thaw, the fate of charismatic megafauna, and the expansion of fisheries. Such narratives disregard the importance of less visible and indirect processes and, in particular, miss the substantive contribution of the shelf seafloor in regulating nutrients and sequestering carbon. Here, we summarise the biogeochemical functioning of the Arctic shelf seafloor before considering how climate change and regional adjustments to human activities may alter its biogeochemical and ecological dynamics, including ecosystem function, carbon burial, or nutrient recycling. We highlight the importance of the Arctic benthic system in mitigating climatic and anthropogenic change and, with a focus on the Barents Sea, offer some observations and our perspectives on future management and policy.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

An Early Pleistocene hippopotamus from Westbury Cave, Somerset, England: support for a previously unrecognized temperate interval in the British Quaternary record - Neil F. Adams; Ian Candy; Danielle C. Schreve (Journal of Quaternary Science, 2022)
Although fossil assemblages from the late Early Pleistocene are very rare in Britain, the site of Westbury Cave in Somerset, England, has the potential to address this gap. The mammal fossils recovered previously from the Siliceous Member in Westbury Cave, though few in number, have hinted at an age for the deposits that is as yet unparalleled in Britain. Here, we describe the first bona fide occurrence of Hippopotamus in the British Early Pleistocene, discovered during recent reinvestigation of the Siliceous Member. The hippo fossil indicates a refined biochronological age of ca. 1.5–1.07 Ma for the Siliceous Member and a palaeoclimate that was warm and humid, which accords well with previous palaeoenvironmental inferences. A synthesis of late Early Pleistocene hippo occurrences suggests that the Siliceous Member hippo may have been part of an early colonization of north‐west Europe by these megaherbivores, possibly during MIS (Marine Oxygen Isotope Stage) 31. Alternatively, it evidences a currently cryptic northward migration during an even earlier temperate phase. In either case, the Siliceous Member is likely to represent a warm period that has not been recognized previously in the British Quaternary record.

Fishing for health: Do the world’s national policies for fisheries and aquaculture align with those for nutrition? - John Zachary Koehn; Edward H Allison; Karen Villeda; Zelin Chen; Marisa Nixon; Emily Crigler; Lily Zhao; Michelle Chow; Bapu Vaitla; Shakuntala H Thilsted; Joeri Scholtens; Christina C Hicks; et al. (Fish and Fisheries, 2022)
Aquatic foods are rich in micronutrients essential to human health, and fisheries and aquaculture are increasingly recognized for their capacity to contribute to reducing global micronutrient deficiencies and diet‐based health risks. Whether fisheries and aquaculture sector and public health nutrition policies align to meet this goal, however, is unclear. Do fisheries and aquaculture policies have explicit nutrition and public health objectives? Do public health nutrition policies recognize the contribution of aquatic foods? Using content analysis, we assessed the alignment of objectives in national fisheries and public health nutrition policies. We further determined conditions associated with varying levels of cohesion among policies in these sectors or domains. We found that 77 of 158 national fisheries policies identified nutrition as a key objective in the sector, and 68 of 165 public health nutrition policies identified the importance of fish and shellfish consumption as key objectives. More recent policies were associated with improved coherence among sectors. International organization presence in policy development was also associated with greater coherence. Countries with higher overweight prevalence had fisheries and public health nutrition policies that were not aligned. There has been a promising recent trend for improved alignment of objectives between fisheries and public health nutrition policies, but more targeted and systematic policy approaches are needed to realize the potential contribution of nutrient‐rich fish and shellfish to healthier food systems.

Evolution of the “world’s only alpine parrot”: Genomic adaptation or phenotypic plasticity, behaviour and ecology? - Denise Martini; Nicolas Dussex; Bruce C. Robertson; Neil J. Gemmell; Michael Knapp (Molecular Ecology, 2021)
Climate warming, in particular in island environments, where opportunities for species to disperse are limited, may become a serious threat to cold adapted alpine species. In order to understand how alpine species may respond to a warming world, we need to understand the drivers that have shaped their habitat specialisation and the evolutionary adaptations that allow them to utilize alpine habitats. The endemic, endangered New Zealand kea ( Nestor notabilis ) is considered the only alpine parrot in the world. As a species commonly found in the alpine zone it may be highly susceptible to climate warming. But is it a true alpine specialist? Is its evolution driven by adaptation to the alpine zone, or is the kea an open habitat generalist that simply uses the alpine zone to, for example, avoid lower lying anthropogenic landscapes? We use whole genome data of the kea and its close, forest adapted sister species, the kākā ( Nestor meridionalis ) to reconstruct the evolutionary history of both species and identify the functional genomic differences that underlie their habitat specialisations. Our analyses do not identify major functional genomic differences between kea and kākā in pathways associated with high‐altitude. Rather, we found evidence that selective pressures on adaptations commonly found in alpine species are present in both Nestor species, suggesting that selection for alpine adaptations has not driven their divergence. Strongly divergent demographic responses to past climate warming between the species nevertheless highlight potential future threats to kea survival in a warming world.

From tides to nucleotides: Genomic signatures of adaptation to environmental heterogeneity in barnacles - Joaquin C. B. Nunez; Stephen Rong; David A. Ferranti; Alejandro Damian‐Serrano; Kimberly B. Neil; Henrik Glenner; Rebecca G. Elyanow; Bianca R. P. Brown; Magnus Alm Rosenblad; Anders Blomberg; Kerstin Johannesson; David M. Rand (Molecular Ecology, 2021)
The northern acorn barnacle ( Semibalanus balanoides ) is a robust system to study the genetic basis of adaptations to highly heterogeneous environments. Adult barnacles may be exposed to highly dissimilar levels of thermal stress depending on where they settle in the intertidal (i.e., closer to the upper or lower tidal boundary). For instance, barnacles near the upper tidal limit experience episodic summer temperatures above recorded heat coma levels. This differential stress at the microhabitat level is also dependent on the aspect of sun exposure. In the present study, we used pool‐seq approaches to conduct a genome wide screen for loci responding to intertidal zonation across the North Atlantic basin (Maine, Rhode Island, and Norway). Our analysis discovered 382 genomic regions containing SNPs which are consistently zonated (i.e., SNPs whose frequencies vary depending on their position in the rocky intertidal) across all surveyed habitats. Notably, most zonated SNPs are young and private to the North Atlantic. These regions show high levels of genetic differentiation across ecologically extreme microhabitats concomitant with elevated levels of genetic variation and Tajima's D , suggesting the action of non‐neutral processes. Overall, these findings support the hypothesis that spatially heterogeneous selection is a general and repeatable feature for this species, and that natural selection can maintain functional genetic variation in heterogeneous environments.

Hares in the long grass: increased aircraft related mortality of the Irish hare (Lepus timidus hibernicus) over a 30-year period at Ireland’s largest civil airport - Samantha Ball; Fidelma Butler; Anthony Caravaggi; Neil E. Coughlan; Gerry Keogh; Michael J. A. O’Callaghan; Ricky Whelan; Thomas C. Kelly (European Journal of Wildlife Research, 2021)
Collisions between wildlife and aircraft are a serious and growing threat to aviation safety. Understanding the frequency of these collisions, the identity of species involved, and the potential damage that can be inflicted on to aircraft aid mitigation efforts by airfield managers. A record of all animal carcasses recovered from Dublin International Airport, Ireland’s largest civil aviation airport, has been maintained since 1990 where strikes with the endemic Irish hare ( Lepus timidus hibernicus ), a protected subspecies of mountain hare, are of particular concern despite substantial management efforts from the airfield authority. The first strike event with a hare was recorded in 1997, and strike events have substantially increased since then, with a sharp increase recorded in 2011. Over a 30-year period, a total of 320 strike events with the Irish hare have been recorded at the airfield. To date, no strike event with a hare has resulted in damage to an aircraft. However, carcasses can present as a major attraction to avian scavenger species in addition to posing as a risk of causing foreign object damage in the event of an undetected carcass. Hare strikes are discussed in the context of the rate of civil aircraft movements, possible direct and indirect damage to aircraft, and airfield wildlife hazard management. Here, we demonstrate that not only are strike events increasing by 14% on an annual basis, but that the kinetic energy of such an event has the potential to cause significant damage to an aircraft.

One of the least disturbed marine coastal ecosystems on Earth: Spatial and temporal persistence of Darwin’s sub‐Antarctic giant kelp forests - Alejandra Mora‐Soto; Austin Capsey; Alan M. Friedlander; Mauricio Palacios; Paul E. Brewin; Neil Golding; Paul Dayton; Brigitta Van Tussenbroek; Américo Montiel; Whitney Goodell; Catalina Velasco‐Charpentier; Tom Hart; et al. (Journal of Biogeography, 2021)
Aim Marine habitats and their dynamics are difficult to systematically monitor, particularly those in remote locations. This is the case with the sub‐Antarctic ecosystem of the giant kelp Macrocystis pyrifera , which was already noted by Charles Darwin in his accounts on the Voyage of the Beagle and recorded on the nautical charts made during that expedition. We combined these and other nautical charts from the 19th and early 20th centuries with surveys conducted in the 1970s and 1980s and satellite detection algorithms from 1984 to 2019, to analyse kelp distribution through time and the factors that correlate with it. Location Marine ecoregions of Channels and Fjords of Southern Chile, Falkland Islands (Malvinas), and the island of South Georgia. Taxon Macrocystis pyrifera . Methods We characterised 309 giant kelp forests by their coastal geospatial attributes. Statistically significant variables were included in a conditional inference tree to predict kelp forest size. Sea surface temperature (SST) records were analysed to confirm temperature ranges over the last four decades. Nautical charts, historical surveys, aerial photogrammetry, unmanned aerial vehicle (UAV) surveys and satellite imagery were overlaid to assess spatial distribution of kelp forest canopies, spanning the period 1829–2020. Results Considering the extensive natural and human caused changes over the last two centuries, this diverse kelp ecosystem is remarkably persistent. We found that the ocean currents and wave exposure, combined with the geomorphological settings of the coastline are the most critical factors predicting the extent of the kelp forests. Main conclusions We have described the long‐term ecological persistence of the kelp forests in this vastly under‐studied region that offers a conceptual biogeographical model supporting the global importance proposed by Charles Darwin 200 years ago (Darwin, 1845). In the current context of global change, the need for conservation of this persistent and well‐preserved marine ecosystem has never been more important.

A new approach for estimating and delineating within-field crop water stress zones with satellite imagery - Ryan Smith; Lindi Oyler; Colin Campbell; Elisa A. Woolley; Bryan G. Hopkins; Ruth Kerry; Neil C. Hansen (International Journal of Remote Sensing, 2021)

Potato Nitrogen Response and Soil Microbial Activity as Affected by Fumigation - James E. Crants; Linda L. Kinkel; José Pablo Dundore-Arias; Andrew P. Robinson; Neil C. Gudmestad; Carl J. Rosen (American Journal of Potato Research, 2021)

Regime shift tipping point in hare population collapse associated with climatic and agricultural change during the very early 20th century - Neil Reid; Jon E. Brommer; Nils C. Stenseth; Ferdia Marnell; Robbie A. McDonald; W. Ian Montgomery (Global Change Biology, 2021)
Animal populations at northern latitudes may have cyclical dynamics that are degraded by climate change leading to trophic cascade. Hare populations at more southerly latitudes are characterized by dramatic declines in abundance associated with agricultural intensification. We focus on the impact of historical climatic and agricultural change on a mid‐latitude population of mountain hares, Lepus timidus hibernicus . Using game bag records from multiple sites throughout Ireland, the hare population index exhibited a distinct regime shift. Contrary to expectations, there was a dynamical structure typical of northern latitude hare populations from 1853 to 1908, during which numbers were stable but cyclic with a periodicity of 8 years. This regime was replaced by dynamics more typical of southern latitude hare populations from 1909 to 1970, in which cycles were lost and numbers declined dramatically. Destabilization of the autumn North Atlantic Oscillation (NAO) led to the collapse of similar cycles in the hare population, coincident with the onset of agricultural intensification (a shift from small‐to‐large farms) in the first half of the 20th century. Similar, but more recent regime shifts have been observed in Arctic ecosystems and attributed to anthropogenic climate change. The present study suggests such shifts may have occurred at lower latitudes more than a century ago during the very early 20th century. It seems likely that similar tipping points in the population collapse of other farmland species may have occurred similarly early but went undocumented. As northern systems are increasingly impacted by climate change and probable expansion of agriculture, the interaction of these processes is likely to disrupt the pulsed flow of resources from cyclic populations impacting ecosystem function.

Advancing Social Equity in and Through Marine Conservation - Nathan J. Bennett; Laure Katz; Whitney Yadao-Evans; Gabby N. Ahmadia; Scott Atkinson; Natalie C. Ban; Neil M. Dawson; Asha de Vos; Juno Fitzpatrick; David Gill; Mael Imirizaldu; Naia Lewis; et al. (Frontiers in Marine Science, 2021)
Substantial efforts and investments are being made to increase the scale and improve the effectiveness of marine conservation globally. Though it is mandated by international law and central to conservation policy, less attention has been given to how to operationalize social equity in and through the pursuit of marine conservation. In this article, we aim to bring greater attention to this topic through reviewing how social equity can be better integrated in marine conservation policy and practice. Advancing social equity in marine conservation requires directing attention to: recognition through acknowledgment and respect for diverse peoples and perspectives; fair distribution of impacts through maximizing benefits and minimizing burdens; procedures through fostering participation in decision-making and good governance; management through championing and supporting local involvement and leadership; the environment through ensuring the efficacy of conservation actions and adequacy of management to ensure benefits to nature and people; and the structural barriers to and institutional roots of inequity in conservation. We then discuss the role of various conservation organizations in advancing social equity in marine conservation and identify the capacities these organizations need to build. We urge the marine conservation community, including governments, non-governmental organizations and donors, to commit to the pursuit of socially equitable conservation.

Pattern, style and timing of British–Irish Ice Sheet advance and retreat over the last 45 000 years: evidence from NW Scotland and the adjacent continental shelf - Tom Bradwell; Derek Fabel; Chris D. Clark; Richard C. Chiverrell; David Small; Rachel K. Smedley; Margot H. Saher; Steven G. Moreton; Dayton Dove; S. Louise Callard; Geoff A. T. Duller; Alicia Medialdea; et al. (Journal of Quaternary Science, 2021)
Predicting the future response of ice sheets to climate warming and rising global sea level is important but difficult. This is especially so when fast‐flowing glaciers or ice streams , buffered by ice shelves, are grounded on beds below sea level. What happens when these ice shelves are removed? And how do the ice stream and the surrounding ice sheet respond to the abruptly altered boundary conditions? To address these questions and others we present new geological, geomorphological, geophysical and geochronological data from the ice‐stream‐dominated NW sector of the last British–Irish Ice Sheet (BIIS). The study area covers around 45 000 km 2 of NW Scotland and the surrounding continental shelf. Alongside seabed geomorphological mapping and Quaternary sediment analysis, we use a suite of over 100 new absolute ages (including cosmogenic‐nuclide exposure ages, optically stimulated luminescence ages and radiocarbon dates) collected from onshore and offshore, to build a sector‐wide ice‐sheet reconstruction combining all available evidence with Bayesian chronosequence modelling. Using this information we present a detailed assessment of ice‐sheet advance/retreat history, and the glaciological connections between different areas of the NW BIIS sector, at different times during the last glacial cycle. The results show a highly dynamic, partly marine, partly terrestrial, ice‐sheet sector undergoing large size variations in response to sub‐millennial‐scale climatic (Dansgaard–Oeschger) cycles over the last 45 000 years. Superimposed on these trends we identify internally driven instabilities, operating at higher frequency, conditioned by local topographic factors, tidewater dynamics and glaciological feedbacks during deglaciation. Specifically, our new evidence indicates extensive marine‐terminating ice‐sheet glaciation of the NW BIIS sector during Greenland Stadials 12 to 9 – prior to the main ‘Late Weichselian’ ice‐sheet glaciation. After a period of restricted glaciation, in Greenland Interstadials 8 to 6, we find good evidence for rapid renewed ice‐sheet build‐up in NW Scotland, with the Minch ice‐stream terminus reaching the continental shelf edge in Greenland Stadial 5, perhaps only briefly. Deglaciation of the NW sector took place in numerous stages. Several grounding‐zone wedges and moraines on the mid‐ and inner continental shelf attest to significant stabilizations of the ice‐sheet grounding line, or ice margin, during overall retreat in Greenland Stadials 3 and 2, and to the development of ice shelves. NW Lewis was the first substantial present‐day land area to deglaciate, in the first half of Greenland Stadial 3 at a time of globally reduced sea‐level c. 26 ka bp , followed by Cape Wrath at c. 24 ka bp. The topographic confinement of the Minch straits probably promoted ice‐shelf development in early Greenland Stadial 2, providing the ice stream with additional support and buffering it somewhat from external drivers. However, c. 20–19 ka bp , as the grounding‐line migrated into shoreward deepening water, coinciding with a marked change in marine geology and bed strength, the ice stream became unstable. We find that, once underway, grounding‐line retreat proceeded in an uninterrupted fashion with the rapid loss of fronting ice shelves – first in the west, then the east troughs – before eventual glacier stabilization at fjord mouths in NW Scotland by ~17 ka bp. Around the same time, ~19–17 ka bp , ice‐sheet lobes readvanced into the East Minch – possibly a glaciological response to the marine‐instability‐triggered loss of adjacent ice stream (and/or ice shelf) support in the Minch trough. An independent ice cap on Lewis also experienced margin oscillations during mid‐Greenland Stadial 2, with an ice‐accumulation centre in West Lewis existing into the latter part of Heinrich Stadial 1. Final ice‐sheet deglaciation of NW mainland Scotland was punctuated by at least one other coherent readvance at c. 15.5 ka bp , before significant ice‐mass losses thereafter. At the glacial termination, c. 14.5 ka bp , glaciers fed outwash sediment to now‐abandoned coastal deltas in NW mainland Scotland around the time of global Meltwater Pulse 1A. Overall, this work on the BIIS NW sector reconstructs a highly dynamic ice‐sheet oscillating in extent and volume for much of the last 45 000 years. Periods of expansive ice‐sheet glaciation dominated by ice‐streaming were interspersed with periods of much more restricted ice‐cap or tidewater/fjordic glaciation. Finally, this work indicates that the role of ice streams in ice‐sheet evolution is complex but mechanistically important throughout the lifetime of an ice sheet – with ice streams contributing to the regulation of ice‐sheet health but also to the acceleration of ice‐sheet demise via marine ice‐sheet instabilities.

Influence of the MJO on daily surface air temperature over Iran - Farnaz Pourasghar; Eric C. J. Oliver; Neil J. Holbrook (International Journal of Climatology, 2021)
The influence of the Madden‐Julian Oscillation (MJO) on surface air temperature over Iran is examined using daily data from meteorological stations from 1979 to 2015. Composites of daily surface air temperature anomalies are positive in MJO phases 1 and 8 and negative in MJO phases 3–4 with broader region positive tendencies also in MJO phases 2 and 7, and negative tendencies in MJO phases 5–6. This variability is associated with horizontal temperature advection, whereby the southerly (northward) winds act to heat and the northerly (southward) winds cool Iran, in association with the MJO. Further, we find that daily minimum surface air temperatures respond more strongly to the MJO than do daily maximum surface temperatures. These signals correspond to cloudy and humid conditions.

The Southern Hemisphere lampreys (Geotriidae and Mordaciidae) - Allison K. Miller; Cindy Baker; Jane C. Kitson; Jonah L. Yick; Pedro E. Inalaf Manquel; Alana Alexander; Neil J. Gemmell (Reviews in Fish Biology and Fisheries, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

A strategy for the next decade to address data deficiency in neglected biodiversity - Axel Hochkirch; Michael J. Samways; Justin Gerlach; Monika Böhm; Paul Williams; Pedro Cardoso; Neil Cumberlidge; P. J. Stephenson; Mary B. Seddon; Viola Clausnitzer; Paulo A. V. Borges; Gregory M. Mueller; et al. (Conservation Biology, 2021)
Measuring progress toward international biodiversity targets requires robust information on the conservation status of species, which the International Union for Conservation of Nature (IUCN) Red List of Threatened Species provides. However, data and capacity are lacking for most hyperdiverse groups, such as invertebrates, plants, and fungi, particularly in megadiverse or high‐endemism regions. Conservation policies and biodiversity strategies aimed at halting biodiversity loss by 2020 need to be adapted to tackle these information shortfalls after 2020. We devised an 8‐point strategy to close existing data gaps by reviving explorative field research on the distribution, abundance, and ecology of species; linking taxonomic research more closely with conservation; improving global biodiversity databases by making the submission of spatially explicit data mandatory for scientific publications; developing a global spatial database on threats to biodiversity to facilitate IUCN Red List assessments; automating preassessments by integrating distribution data and spatial threat data; building capacity in taxonomy, ecology, and biodiversity monitoring in countries with high species richness or endemism; creating species monitoring programs for lesser‐known taxa; and developing sufficient funding mechanisms to reduce reliance on voluntary efforts. Implementing these strategies in the post‐2020 biodiversity framework will help to overcome the lack of capacity and data regarding the conservation status of biodiversity. This will require a collaborative effort among scientists, policy makers, and conservation practitioners.

Aufeis fields as novel groundwater‐dependent ecosystems in the arctic cryosphere - Alexander D. Huryn; Michael N. Gooseff; Patrick J. Hendrickson; Martin A. Briggs; Ken D. Tape; Neil C. Terry (Limnology and Oceanography, 2021)
River aufeis (ow′ fīse) are widespread features of the arctic cryosphere. They form when river channels become locally restricted by ice, resulting in cycles of water overflow and freezing and the accumulation of ice, with some aufeis attaining areas of ~ 25 + km 2 and thicknesses of 6+ m. During winter, unfrozen sediments beneath the insulating ice layer provide perennial groundwater‐habitat that is otherwise restricted in regions of continuous permafrost. Our goal was to assess whether aufeis facilitate the occurrence of groundwater invertebrate communities in the Arctic. We focused on a single aufeis ecosystem (~ 5 km 2 by late winter) along the Kuparuk River in arctic Alaska. Subsurface invertebrates were sampled during June and August 2017 from 50 3.5‐cm diameter PVC wells arranged in a 5 × 10 array covering ~ 40 ha. Surface invertebrates were sampled using a quadrat approach. We documented a rich assemblage of groundwater invertebrates (49 [43–54] taxa, [95% confidence limits]) that was distributed below the sediment surface to a mean depth of ~ 69 ± 2 cm ( ± 1 SE) throughout the entire well array. Although community structure differed significantly between groundwater and surface habitats, the taxa richness from wells and surface sediments (43 [35–48] taxa) did not differ significantly, which was surprising given lower richness in subsurface habitats of large, riverine gravel‐aquifer systems shown elsewhere. This is the first demonstration of a rich and spatially extensive groundwater fauna in a region of continuous permafrost. Given the geographic extent of aufeis fields, localized groundwater‐dependent ecosystems may be widespread in the Arctic.

A genome‐wide investigation of adaptive signatures in protein‐coding genes related to tool behaviour in New Caledonian and Hawaiian crows - Nicolas Dussex; Verena E. Kutschera; R. Axel W. Wiberg; Darren J. Parker; Gavin R. Hunt; Russell D. Gray; Kim Rutherford; Hideaki Abe; Robert C. Fleischer; Michael G. Ritchie; Christian Rutz; Jochen B. W. Wolf; et al. (Molecular Ecology, 2021)
Very few animals habitually manufacture and use tools. It has been suggested that advanced tool behaviour co‐evolves with a suite of behavioural, morphological and life history traits. In fact, there are indications for such an adaptive complex in tool‐using crows (genus Corvus species). Here, we sequenced the genomes of two habitually tool‐using and ten non‐tool‐using crow species to search for genomic signatures associated with a tool‐using lifestyle. Using comparative genomic and population genetic approaches, we screened for signals of selection in protein‐coding genes in the tool‐using New Caledonian and Hawaiian crows. While we detected signals of recent selection in New Caledonian crows near genes associated with bill morphology, our data indicate that genetic changes in these two lineages are surprisingly subtle, with little evidence at present for convergence. We explore the biological explanations for these findings, such as the relative roles of gene regulation and protein‐coding changes, as well as the possibility that statistical power to detect selection in recently diverged lineages may have been insufficient. Our study contributes to a growing body of literature aiming to decipher the genetic basis of recently evolved complex behaviour.

Geomorphological and ecological change in a coastal foreland dune system, Sandscale haws, Cumbria, UK: the management challenges posed by climate change - Kenneth Pye; Simon J. Blott; Neil Forbes; Lindsay C. Maskell (Journal of Coastal Conservation, 2020)

Optical Properties and Photochemical Transformation of the Dissolved Organic Matter Released by Sargassum - Leanne C. Powers; Rossana Del Vecchio; Neil V. Blough; Natasha McDonald; Philippe Schmitt-Kopplin; Michael Gonsior (Frontiers in Marine Science, 2020)

Towards understanding interactions between Sustainable Development Goals: the role of environment–human linkages - Jörn P. W. Scharlemann; Rebecca C. Brock; Nicholas Balfour; Claire Brown; Neil D. Burgess; Miriam K. Guth; Daniel J. Ingram; Richard Lane; Juliette G. C. Martin; Sylvia Wicander; Valerie Kapos (Sustainability Science, 2020)
Only 10 years remain to achieve all Sustainable Development Goals (SDGs) globally, so there is a growing need to increase the effectiveness and efficiency of action by targeting multiple SDGs. The SDGs were conceived as an ‘indivisible whole’, but interactions between SDGs need to be better understood. Several previous assessments have begun to explore interactions including synergies and possible conflicts between the SDGs, and differ widely in their conclusions. Although some highlight the role of the more environmentally-focused SDGs in underpinning sustainable development, none specifically focuses on environment–human linkages. Assessing interactions between SDGs, and the influence of environment on them can make an important contribution to informing decisions in 2020 and beyond. Here, we review previous assessments of interactions among SDGs, apply an influence matrix to assess pairwise interactions between all SDGs, and show how viewing these from the perspective of environment–human linkages can influence the outcome. Environment, and environment–human linkages, influence most interactions between SDGs. Our action-focused assessment enables decision makers to focus environmental management to have the greatest impacts and to identify opportunities to build on synergies and reduce trade-offs between particular SDGs. It may enable sectoral decision makers to seek support from environment managers for achieving their goals. We explore cross-cutting issues and the relevance and potential application of our approach in supporting decision making for progress to achieve the SDGs.

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

Wildfire and the ecological niche: Diminishing habitat suitability for an indicator species within semi‐arid ecosystems - Shawn T. O’Neil; Peter S. Coates; Brianne E. Brussee; Mark A. Ricca; Shawn P. Espinosa; Scott C. Gardner; David J. Delehanty (Global Change Biology, 2020)
Globally accelerating frequency and extent of wildfire threatens the persistence of specialist wildlife species through direct loss of habitat and indirect facilitation of exotic invasive species. Habitat specialists may be especially prone to rapidly changing environmental conditions because their ability to adapt lags behind the rate of habitat alteration. As a result, these populations may become increasingly susceptible to ecological traps by returning to suboptimal breeding habitats that were dramatically altered by disturbance. We demonstrate a multistage modeling approach that integrates habitat selection and survival during the key nesting life‐stage of a bird species of high conservation concern, the greater sage‐grouse ( Centrocercus urophasianus ; hereafter, sage‐grouse). We applied these spatially explicit models to a spatiotemporally robust dataset of sage‐grouse nest locations and fates across wildfire‐altered sagebrush ecosystems of the Great Basin ecoregion, western United States. Female sage‐grouse exhibited intricate habitat selection patterns that varied across regional gradients of ecological productivity among sagebrush communities, but often selected nest sites that disproportionately resulted in nest failure. For example, 23% of nests occurred in wildfire‐affected habitats characterized by reduced sagebrush cover and greater composition of invasive annual grasses. We found survival of nests was negatively associated with wildfire‐affected areas, but positively associated with higher elevations with increased ruggedness and overall shrub cover. Strong site fidelity likely drove sage‐grouse to continue nesting in habitats degraded by wildfire. Hence, increasing frequency and extent of wildfire may contribute disproportionately to reduced reproductive success by creating ecological traps that act as population sinks. Identifying such habitat mismatches between selection and survival facilitates deeper understanding of the mechanisms driving reduced geographic niche space and population decline at broad spatiotemporal scales, while guiding management actions to areas that would be most beneficial to the species.

Simulated Estuary-Wide Response of Seagrass (Zostera marina) to Future Scenarios of Temperature and Sea Level - Cara R. Scalpone; Jessie C. Jarvis; James M. Vasslides; Jeremy M. Testa; Neil K. Ganju (Frontiers in Marine Science, 2020)

A magnetic resonance spectroscopy investigation in symptomatic former NFL players - Michael L. Alosco; Yorghos Tripodis; Benjamin Rowland; Alicia S. Chua; Huijun Liao; Brett Martin; Johnny Jarnagin; Christine E. Chaisson; Ofer Pasternak; Sarina Karmacharya; Inga K. Koerte; Robert C. Cantu; et al. (Brain Imaging and Behavior, 2020)

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Characteristic atmospheric states during mid-summer droughts over Central America and Mexico - Zijie Zhao; Neil J. Holbrook; Eric C. J. Oliver; Daniel Ballestero; J. Mauro Vargas-Hernandez (Climate Dynamics, 2020)

Description and distribution of Desmacella hyalina sp. nov. (Porifera, Desmacellidae), a new cryptic demosponge in glass sponge reefs from the western coast of Canada - Lauren K. Law; Henry M. Reiswig; Bruce S. Ott; Neil McDaniel; Amanda S. Kahn; Keenan C. Guillas; Curtis Dinn; Sally P. Leys (Marine Biodiversity, 2020)

Sub‐lethal temperature thresholds indicate acclimation and physiological limits in brook trout Salvelinus fontinalis - Scott M. Morrison; Theresa E. Mackey; Travis Durhack; Jennifer D. Jeffrey; Lilian M. Wiens; Neil J. Mochnacz; Caleb T. Hasler; Eva C. Enders; Jason R. Treberg; Ken M. Jeffries (Journal of Fish Biology, 2020)
The upper thermal tolerance of brook trout Salvelinus fontinalis was estimated using critical thermal maxima (CT max ) experiments on fish acclimated to temperatures that span the species' thermal range (5–25°C). The CT max increased with acclimation temperature but plateaued in fish acclimated to 20, 23 and 25°C. Plasma lactate was highest, and the hepato‐somatic index ( I H ) was lowest at 23 and 25°C, which suggests additional metabolic costs at those acclimation temperatures. The results suggest that there is a sub‐lethal threshold between 20 and 23°C, beyond which the fish experience reduced physiological performance.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Carotenoid-to-(bacterio)chlorophyll energy transfer in LH2 antenna complexes from Rba. sphaeroides reconstituted with non-native (bacterio)chlorophylls - Dariusz M. Niedzwiedzki; David J. K. Swainsbury; C. Neil Hunter (Photosynthesis Research, 2020)

A systematic review of reviews identifying UK validated dietary assessment tools for inclusion on an interactive guided website for researchers: www.nutritools.org - Jozef Hooson (Jzh); Jayne Hutchinson (Jyh); Marisol Warthon-Medina; Neil Hancock; Katharine Greathead; Bethany Knowles; Elisa Vargas-Garcia; Lauren E. Gibson; Linda A. Bush; Barrie Margetts; Sian Robinson; Andy Ness; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Role of ocean mesoscale structures in shaping the Angola-Low pressure system and the southern Africa rainfall - Fabien Desbiolles; Emma Howard; Ross C. Blamey; Rondrotiana Barimalala; Neil C. G. Hart; Chris J. C. Reason (Climate Dynamics, 2020)

Editorial - C. Neil Roberts (Journal of Quaternary Science, 2020)

A new model study species: high accuracy of discrimination between individual freckled hawkfish ( Paracirrhites forsteri ) using natural markings - Mark G. McInnes; Neil M. Burns; Charlotte R. Hopkins; Guy P. Henderson; Deborah C. McNeill; David M. Bailey (Journal of Fish Biology, 2020)
Variations between distinct natural markings of freckled hawkfish ( Paracirrhites forsteri ) could allow in situ identification of individuals from underwater photography. Receiver operating characteristic analysis was used to assess the ability of the Interactive Individual Identification System (I 3 S) software to assist in discriminating between images of P. forsteri individuals. This study's results show the high discriminant ability of I 3 S to differentiate between unlike individuals and identify images of the same individual. The ability to use automatic computer‐aided assistance in the study of this species will enable future research to explore behaviour and movements of individuals in the wild.

Computer‐aided photo‐identification of a rare stingray, Megatrygon microps - Jennifer A. Keeping; Katie E. Reeve‐Arnold; Neil M. Burns; Nilza Catarina; David M. Bailey; Deborah C. McNeill (Journal of Fish Biology, 2020)
A protocol for photo‐identification of individual Megatrygon microps has been defined. One hundred and four identification photographs were taken between 2005 and 2019. Spot patterns on the dorsal surface were used to identify individuals. Unique scarring on eight M. microps re‐observed provided an independent confirmation of pattern stability of up to 761 days. Previous studies lacked statistical testing used to validate this photo‐identification approach. I 3 S photo‐matching software was used to successfully match images, identifying 69 individuals. A photo‐matching software facilitates an open‐source platform for identifying individual M. microps , allowing for better population assessments.

Traces of volcanic ash from the Mediterranean, Iceland and North America in a Holocene record from south Wales, UK - Gwydion Jones; Siwan M. Davies; Richard A. Staff; Neil J. Loader; Sarah J. Davies; Michael J. C. Walker (Journal of Quaternary Science, 2020)
A tephra record is presented for a sediment core from Llyn Llech Owain, south Wales, spanning the early‐ to mid‐Holocene. Seven cryptotephra deposits are discovered with three thought to correlate with known eruptions and the remaining four considered to represent previously undocumented events. One deposit is suggested to correlate with the ~6.9 cal ka bp Lairg A tephra from Iceland, whereas more distant sources are proposed as the origin for two of the tephra deposits. A peak of colourless shards in early‐Holocene sediments is thought to tentatively correlate with the ~9.6 cal ka bp Fondi di Baia tephra (Campi Flegrei) and a second cryptotephra is tentatively correlated with the ~3.6 cal ka bp Aniakchak (CFE) II tephra (Alaska). The Fondi di Baia tephra has never been recorded beyond proximal sites and its discovery in south Wales significantly extends the geographical distribution of ash from this eruption. The remaining four cryptotephra deposits are yet to be correlated with known eruptions, demonstrating that our current understanding of widespread tephra deposits is incomplete. This new tephra record highlights the potential for sites at more southerly and westerly locations in northwest Europe to act as repositories for ash from several volcanic regions.

Projected Marine Heatwaves in the 21st Century and the Potential for Ecological Impact - Eric C. J. Oliver; Michael T. Burrows; Markus G. Donat; Alex Sen Gupta; Lisa V. Alexander; Sarah E. Perkins-Kirkpatrick; Jessica A. Benthuysen; Alistair J. Hobday; Neil J. Holbrook; Pippa J. Moore; Mads S. Thomsen; Thomas Wernberg; et al. (Frontiers in Marine Science, 2019)

Genomic sequence and host range studies reveal considerable variation within the species Arracacha virus B - Roger A. C. Jones; Adrian Fox; Neil Boonham; Ian P. Adams (Archives of Virology, 2019)

Elevated carbon dioxide decreases the adverse effects of higher temperature and drought stress by mitigating oxidative stress and improving water status in Arabidopsis thaliana - Mohammad I. Abo Gamar; Anna Kisiala; R. J. Neil Emery; Edward C. Yeung; Sophia L. Stone; Mirwais M. Qaderi (Planta, 2019)

Does family communication matter? Exploring knowledge of breast cancer genetics in cancer families - Deborah O. Himes; Sarah H. Davis; Jane H. Lassetter; Neil E. Peterson; Margaret F. Clayton; Wendy C. Birmingham; Anita Y. Kinney (Journal of Community Genetics, 2019)

A cofactor consumption screen identifies promising NfsB family nitroreductases for dinitrotoluene remediation - Elsie M. Williams; Abigail V. Sharrock; Elizabeth L. Rylott; Neil C. Bruce; Joanna K. MacKichan; David F. Ackerley (Biotechnology Letters, 2019)

Patterns in fish biodiversity associated with temperate reefs on the southeastern US continental shelf - Nathan M. Bacheler; Zebulon H. Schobernd; Kevan C. Gregalis; Christina M. Schobernd; Bradford Z. Teer; Zachary Gillum; Dawn M. Glasgow; Neil McNeill; Michael Burton; Roldan Muñoz (Marine Biodiversity, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

Symptom Expression of Mainstream and Specialty Potato Cultivars to Bacterial Ring Rot (Clavibacter sepedonicus) and Evaluation of in-Field Detection - Jonathan L. Whitworth; Rachel A. Selstedt; Alan A. G. Westra; Phil Nolte; Kasia Duellman; S. K. R. Yellareddygari; Neil C. Gudmestad (American Journal of Potato Research, 2019)

Modulation of wet‐season rainfall over Iran by the Madden–Julian Oscillation, Indian Ocean Dipole and El Niño–Southern Oscillation - Farnaz Pourasghar; Eric C. J. Oliver; Neil J. Holbrook (International Journal of Climatology, 2019)
The intra‐seasonal variation of precipitation over Iran is examined in terms of the combined effects of the Madden–Julian Oscillation (MJO), Indian Ocean Dipole (IOD) and El Niño–Southern Oscillation (ENSO), using daily observations during the wet season (October–May) from 1961 to 2015. We have examined how the probability of daily rainfall above the upper tercile varies across MJO phases during positive and negative IOD and ENSO states. The results indicate that the response of Iran's wet‐season rainfall to the MJO is affected more by large‐scale atmospheric variations associated with the IOD than by ENSO. The negative (positive) IOD strengthens (suppresses) the MJO–rainfall relationship in the wet and dry MJO phases. The variation in the atmospheric variables (relative humidity and vertical velocity) indicates more (less) humidity and upwards (downwards) motion which increases (decreases) precipitation in wet (dry) MJO phases during the negative IOD. The rainfall relationship with the MJO during the negative IOD is statistically significant, while the relationship during the positive IOD is weak; and no significant relationship is found during either phase of ENSO.

Imposing and maintaining soil water deficits in drought studies in pots - Neil C. Turner (Plant and Soil, 2019)

Crop root system traits cannot be seen as a silver bullet delivering drought resistance - Jairo A. Palta; Neil C. Turner (Plant and Soil, 2019)

Spinal Cord Stimulation for Pain Treatment After Spinal Cord Injury - Qian Huang; Wanru Duan; Eellan Sivanesan; Shuguang Liu; Fei Yang; Zhiyong Chen; Neil C. Ford; Xueming Chen; Yun Guan (Neuroscience Bulletin, 2019)

The Effect of Temperature on the Physiological Condition and Immune-Capacity of European Lobsters (Homarus gammarus) During Long-Term Starvation - Amaya Albalat; Laura Johnson; Christopher J. Coates; Gregory C. Dykes; Fiona Hitte; Bernat Morro; James Dick; Keith Todd; Douglas M. Neil (Frontiers in Marine Science, 2019)

From the Oceans to the Cloud: Opportunities and Challenges for Data, Models, Computation and Workflows - Tiffany C. Vance; Micah Wengren; Eugene Burger; Debra Hernandez; Timothy Kearns; Encarni Medina-Lopez; Nazila Merati; Kevin O’Brien; Jon O’Neil; James T. Potemra; Richard P. Signell; Kyle Wilcox (Frontiers in Marine Science, 2019)

Securing a Just Space for Small-Scale Fisheries in the Blue Economy - Philippa J. Cohen; Edward H. Allison; Neil L. Andrew; Joshua Cinner; Louisa S. Evans; Michael Fabinyi; Len R. Garces; Stephen J. Hall; Christina C. Hicks; Terry P. Hughes; Svein Jentoft; David J. Mills; et al. (Frontiers in Marine Science, 2019)

Genetic modification of western wheatgrass (Pascopyrum smithii) for the phytoremediation of RDX and TNT - Long Zhang; Elizabeth L. Rylott; Neil C. Bruce; Stuart E. Strand (Planta, 2019)

Pancreatic duct-like cell line derived from pig embryonic stem cells: expression of uroplakin genes in pig pancreatic tissue - Neil C. Talbot; Amy E. Shannon; Wesley M. Garrett (In Vitro Cellular & Developmental Biology - Animal, 2019)

Blacktip shark Carcharhinus limbatus presence at fishing piers in South Carolina: association and environmental drivers - Kelsey L. Martin; Dan C. Abel; Derek P. Crane; Neil Hammerschlag; Erin J. Burge (Journal of Fish Biology, 2019)
We tagged 12 Carcharhinus limbatus with acoustic transmitters and monitored their presence at five piers along the north‐east coast of South Carolina, USA in 2016 and four piers in 2017 using acoustic receivers. Data were analysed with pier association indices (PAI), mixed models and fast Fourier transformation analyses to identify potential factors related to residence time and presence at piers and any cyclical patterns in visits to piers. While the majority of monitored C. limbatus were infrequently detected at piers, three (25.0%) were highly associated with piers (PAI ≥ 0.50). Of the C. limbatus that were detected after initial capture, three (25.0%) recorded detection events only at the pier where they were tagged and two individuals (16.7%) recorded at least one detection event at all monitored piers. The best‐fit model explaining C. limbatus residence time at piers included terms for pier location and diel cycle ( w i = 0.88), whereas the best fit model explaining presence–absence of C. limbatus at piers included terms for tidal height, diel cycle, barometric pressure and angler count ( w i = 0.98). Carcharhinus limbatus did not appear to display cyclical patterns in their visits to piers. Along the north‐east coast of South Carolina, association of C. limbatus with piers is a phenomenon for a proportion of mature individuals, but continued research is necessary to understand if this behaviour is driven by attraction to and feeding on angler discards or increased foraging opportunities resulting from the attraction of potential prey to the physical structure provided by piers.

The potential of small ruminant farming as a means of poverty alleviation in rural southern India - Sehr Vanya Lalljee; C. Soundararajan; Yogendra Deep Singh; Neil D. Sargison (Tropical Animal Health and Production, 2019)

Multi-level emulation of complex climate model responses to boundary forcing data - Giang T. Tran; Kevin I. C. Oliver; Philip B. Holden; Neil R. Edwards; András Sóbester; Peter Challenor (Climate Dynamics, 2019)

Overexpressing ovotransferrin and avian β-defensin-3 improves antimicrobial capacity of chickens and poultry products - Caitlin A. Cooper; Mark L. Tizard; Tamsyn Stanborough; Sean C. Moore; P. Scott Chandry; Kristie A. Jenkins; Terry G. Wise; Terri E. O’Neil; Daniel S. Layton; Kirsten R. Morris; Robert J. Moore; Narelle Fegan; et al. (Transgenic Research, 2019)

A statistical seasonal forecast model of North Indian Ocean tropical cyclones using the quasi‐biennial oscillation - Md Wahiduzzaman; Eric C. J. Oliver; Philip J. Klotzbach; Simon J. Wotherspoon; Neil J. Holbrook (International Journal of Climatology, 2019)
Previous studies have shown that the skill of seasonal forecasts of tropical cyclone (TC) activity over the North Indian Ocean (NIO) tends to be poor. This paper investigates the forecast potential of TC formation, trajectories and points of landfall in the NIO region using an index of the stratospheric quasi‐biennial oscillation (QBO) as the predictor variable in a new statistical seasonal forecast model. Genesis was modelled by kernel density estimation, tracks were fitted using a generalized additive model (GAM) approach with an Euler integration step, and landfall location was estimated using a country mask. The model was trained on 30 years of TC observations (1980–2009) from the Joint Typhoon Warning Center and the QBO index at lags from 0 to 6 months. Over this time period, and within each season and QBO phase, the kernel density estimator modelled the distribution of genesis points, and the cyclone trajectories were then fit by the GAM along the observed cyclone tracks as smooth functions of location. Trajectories were simulated from randomly selected genesis points in the kernel density estimates. Ensembles of cyclone paths were traced, taking account of random innovations every 6‐hr along the GAM‐fitted velocity fields, to determine the points of landfall. Lead–lag analysis was used to assess the best predictor timescales for TC forecast potential. We found that the best model utilized the QBO index with a 3‐month lead. Two hindcast validation methods were applied. First, leave‐one‐out cross‐validation was performed where the country of landfall was decided by the majority vote of the simulated tracks. Second, the distances between the landfall locations in the observations and simulations were calculated. Application of seasonal forecast analysis further indicated that including information on the state of the QBO has the potential to improve the skill of TC seasonal forecasts in the NIO region.

Consumer trophic positions respond variably to seasonally fluctuating environments - Bailey C. McMeans; Taku Kadoya; Thomas K. Pool; Gordon W. Holtgrieve; Sovan Lek; Heng Kong; Kirk Winemiller; Vittoria Elliott; Neil Rooney; Pascal Laffaille; Kevin S. McCann (Ecology, 2019)
The effects of environmental seasonality on food web structure have been notoriously understudied in empirical ecology. Here, we focus on seasonal changes in one key attribute of a food web, consumer trophic position. We ask whether fishes inhabiting tropical river–floodplain ecosystems behave as seasonal omnivores, by shifting their trophic positions in relation to the annual flood pulse, or whether they feed at the same trophic position all year, as much empirical work implicitly assumes. Using dietary data from the Tonle Sap Lake, Cambodia, and a literature review, we find evidence that some fishes, especially small piscivores, increased consumption of invertebrates and/or plant material during the wet season, as predicted. However, nitrogen stable isotope (δ 15 N) data for 26 Tonle Sap fishes, spanning a broader range of functional groups, uncovered high variation in seasonal trophic position responses among species (0 to ±0.52 trophic positions). Based on these findings, species respond to the flood pulse differently. Diverse behavioral responses to seasonality, underpinned by spatiotemporal variation at multiple scales, could be central for rerouting matter and energy flow in these dynamic ecosystems. Seasonally flexible foraging behaviors warrant further study given their potential influence on food web dynamics in a range of fluctuating environments.

Prospects and challenges of environmental DNA (eDNA) monitoring in freshwater ponds - Lynsey R. Harper; Andrew S. Buxton; Helen C. Rees; Kat Bruce; Rein Brys; David Halfmaerten; Daniel S. Read; Hayley V. Watson; Carl D. Sayer; Eleanor P. Jones; Victoria Priestley; Elvira Mächler; et al. (Hydrobiologia, 2019)

Influence of the Madden–Julian oscillation on Costa Rican mid‐summer drought timing - Zijie Zhao; Eric C. J. Oliver; Daniel Ballestero; Jose Mauro Vargas‐Hernandez; Neil J. Holbrook (International Journal of Climatology, 2019)
The Central American mid‐summer drought (MSD) is the decline of precipitation during the middle of the wet season (July and August) over Central America and southern Mexico. It affects agriculture and favours the initiation of bushfires in Costa Rica's national parks, particularly during El Niño years. The MSD is a seasonal phenomenon that varies in intensity and timing inter‐annually. The Madden–Julian oscillation (MJO) has been shown to influence Costa Rican rainfall on intra‐seasonal time scales, and therefore may be important to the MSD. In this study we use rainfall data from seven stations in Costa Rica to analyse the MJO's influence on the timing of the onset and end of the MSD. We find that the MSD is more likely to start and end in MJO Phases 1 and 8, respectively. Our findings indicate enhanced MSD predictability on intra‐seasonal time scales, which could be beneficial to agricultural planning in Costa Rica.

Equatorial Pacific gravity lineaments: interpretations with basement topography along seismic reflection lines - Neil C. Mitchell; Huw Davies (Marine Geophysical Research, 2018)

Meta-analysis identifies mitochondrial DNA sequence variants associated with walking speed - Todd M. Manini; Thomas W. Buford; John A. Kairalla; Mary M. McDermott; Carlos A. Vaz Fragoso; Roger A. Fielding; Fang-Chi Hsu; Neil Johannsen; Stephen Kritchevsky; Tamara B. Harris; Anne B. Newman; Steven R. Cummings; et al. (GeroScience, 2018)

Real-World Variability in the Prediction of Intracranial Aneurysm Wall Shear Stress: The 2015 International Aneurysm CFD Challenge - Kristian Valen-Sendstad; Aslak W. Bergersen; Yuji Shimogonya; Leonid Goubergrits; Jan Bruening; Jordi Pallares; Salvatore Cito; Senol Piskin; Kerem Pekkan; Arjan J. Geers; Ignacio Larrabide; Saikiran Rapaka; et al. (Cardiovascular Engineering and Technology, 2018)

In Vivo Predictive Dissolution and Simulation Workshop Report: Facilitating the Development of Oral Drug Formulation and the Prediction of Oral Bioperformance - Yasuhiro Tsume; Sanjaykumar Patel; Nikoletta Fotaki; Christel Bergstrӧm; Gordon L. Amidon; James G. Brasseur; Deanna M. Mudie; Duxin Sun; Marival Bermejo; Ping Gao; Wei Zhu; David C. Sperry; et al. (The AAPS Journal, 2018)

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

Coherent phenomena in photosynthetic light harvesting: part two—observations in biological systems - Harry W. Rathbone; Jeffery A. Davis; Katharine A. Michie; Sophia C. Goodchild; Neil O. Robertson; Paul M. G. Curmi (Biophysical Reviews, 2018)

Coherent phenomena in photosynthetic light harvesting: part one—theory and spectroscopy - Harry W. Rathbone; Jeffery A. Davis; Katharine A. Michie; Sophia C. Goodchild; Neil O. Robertson; Paul M. G. Curmi (Biophysical Reviews, 2018)

Evaluation of the Fao‐56 Methodology For Estimating Maize Water Requirements Under Deficit And Full Irrigation Regimes In Semiarid Northeastern Colorado - Patricio Cid; Saleh Taghvaeian; Neil C. Hansen (Irrigation and Drainage, 2018)
Deficit irrigation (DI), where water is applied in amounts of less than what is required to meet crop water demand, seems to be one of the most effective ways to save irrigation water. However, DI practices are usually associated with higher levels of risk of yield penalizations. To minimize risk, accurate irrigation scheduling must be performed based on reliable soil water content (SWC) and crop water demand information. The goal was to determine whether a modelling approach based on the FAO‐56 routine could be used to quantify maize evapotranspiration under drought and full irrigation conditions during three growing seasons in semiarid northeastern Colorado, USA. Maize ET estimations with FAO‐56 were compared with actual values obtained running a root zone water balance where weather data, irrigation data, and values of SWC were used. Irrigation shortage (50, 54 and 19%) reduced ET in 2008, 2009, and 2010 (27, 34 and 14%). Irrigation water productivity increased as irrigation decreased. FAO‐56 estimations were satisfactory but tended to overestimate ET. Averaged seasonal water use root mean square error never exceeded 0.89 mm day ‐1 for any treatment and season studied. Factors contributing to the performance of the FAO‐56 procedure are also discussed. © 2018 John Wiley & Sons, Ltd.

Methamphetamine Induces Apoptosis of Microglia via the Intrinsic Mitochondrial-Dependent Pathway - Anna V. Sharikova; Elizabeth Quaye; Jun Yong Park; Maxwell C. Maloney; Habben Desta; Ramkumar Thiyagarajan; Kenneth L. Seldeen; Neil U. Parikh; Parteet Sandhu; Alexander Khmaladze; Bruce R. Troen; Stanley A. Schwartz; et al. (Journal of Neuroimmune Pharmacology, 2018)

Predicting potato tuber yield loss due to early blight severity in the Midwestern United States - S. K. R. Yellareddygari; Raymond J. Taylor; Julie S. Pasche; Anqing Zhang; Neil C. Gudmestad (European Journal of Plant Pathology, 2018)

Behavioural responses of an Australian colubrid snake (Dendrelaphis punctulatus) to a novel toxic prey item (the Cane Toad Rhinella marina) - John Llewelyn; Neil C. Choyce; Benjamin L. Phillips; Jonathan K. Webb; David J. Pearson; Lin Schwarzkopf; Richard Shine (Biological Invasions, 2018)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Effect of Soil Temperature, Injection Depth, and Rate of Metam Sodium Efficacy in Fine-Textured Soils with High Organic Matter on the Management of Verticillium Wilt of Potato - S. K. R. Yellareddygari; Neil C. Gudmestad (American Journal of Potato Research, 2018)

“Periderm Disorder Syndrome”: a New Name for the Syndrome Formerly Referred to as Pink Eye - Edward C. Lulai; Robert P. Sabba; Philip Nolte; Neil C. Gudmestad; Gary A. Secor (American Journal of Potato Research, 2018)

Modelling broad‐scale wolverine occupancy in a remote boreal region using multi‐year aerial survey data - Justina C. Ray; Lucy G. Poley; Audrey J. Magoun; Cheryl‐Lesley B. Chetkiewicz; F. Meg Southee; F. Neil Dawson; Chris Chenier (Journal of Biogeography, 2018)
Aim We used data from aerial surveys of wolverine tracks collected in seven winters over a 10‐year period (2003–2012) within a 574,287 km 2 study area to evaluate the broad‐scale pattern of wolverine occurrence across a remote northern boreal forest region, identifying areas of high and low occupancy. Location Northern Ontario, Canada. Taxon Wolverine ( Gulo gulo Linnaeus, 1758). Methods We collected wolverine tracks and observations in 100‐km 2 hexagonal survey units, making a total of 6,664 visits to 3,039 units, visiting each 1–9 times. We used hierarchical Bayesian occupancy modelling to model wolverine occurrence, and included covariates with the potential to affect detection and/or occupancy probability of wolverines. Results we detected wolverines on 946 visits, 14.2% of total visits. Probability of detecting a wolverine varied among years and between the two ecozones in the study area. Wolverine occupancy was negatively related to two important covariates, the geographical coordinate Easting and thawing degree‐days. A site occupancy probability map indicated that wolverine occupancy probabilities were highest, and standard error lowest, in the western and northern portions of the study area. Main conclusions The occupancy framework enabled us to use observation data from tracks of this elusive, wide‐ranging carnivore over a vast, remote area while explicitly considering detectability and spatial autocorrelation, yielding a map of probable wolverine distribution in northern Ontario that would not be possible using other methods of detection across a large region. With resource development pressures increasing in this globally significant region in the face of a changing climate, it is important to monitor changes in distribution of species like wolverines that have low population growth rates, large spatial requirements and sensitivity to human disturbance. This study demonstrates a relatively cost‐effective and non‐invasive alternative to monitoring based on wolverine harvest records, which have not been available since 2009 in Ontario due to changes in the provincial regulatory regime for this threatened species.

Investigating Anthropogenic and Geogenic Sources of Groundwater Contamination in a Semi-Arid Alluvial Basin, Goshen Valley, UT, USA - Brian J. Selck; Gregory T. Carling; Stefan M. Kirby; Neil C. Hansen; Barry R. Bickmore; David G. Tingey; Kevin Rey; Janae Wallace; J. Lucy Jordan (Water, Air, & Soil Pollution, 2018)

Feeder-cell-independent culture of the pig embryonic stem cell-derived exocrine pancreatic cell line, PICM-31 - Neil C. Talbot; Amy E. Shannon; Caitlin E. Phillips; Wesley M. Garrett (In Vitro Cellular & Developmental Biology - Animal, 2018)

Trajectories of change in Mediterranean Holocene vegetation through classification of pollen data - Ralph M. Fyfe; Jessie Woodbridge; C. Neil Roberts (Vegetation History and Archaeobotany, 2018)

Effects of caffeine on reaction time are mediated by attentional rather than motor processes - Christopher W. N. Saville; H. M. de Morree; Neil M. Dundon; S. M. Marcora; C. Klein (Psychopharmacology, 2018)

Carotenoid to bacteriochlorophyll energy transfer in the RC–LH1–PufX complex from Rhodobacter sphaeroides containing the extended conjugation keto-carotenoid diketospirilloxanthin - Václav Šlouf; Gürkan Keşan; Radek Litvín; David J. K. Swainsbury; Elizabeth C. Martin; C. Neil Hunter; Tomáš Polívka (Photosynthesis Research, 2018)

The use of historical environmental monitoring data to test predictions on cross-scale ecological responses to alterations in river flows - Matthew J. Colloff; Ian C. Overton; Brent L. Henderson; Jane Roberts; Julian R. W. Reid; Roderick L. Oliver; Anthony D. Arthur; Tanya M. Doody; Neil C. Sims; Qifeng Ye; Susan M. Cuddy (Aquatic Ecology, 2018)

Optical types of inland and coastal waters - Evangelos Spyrakos; Ruth O'Donnell; Peter D. Hunter; Claire Miller; Marian Scott; Stefan G. H. Simis; Claire Neil; Claudio C. F. Barbosa; Caren E. Binding; Shane Bradt; Mariano Bresciani; Giorgio Dall'Olmo; et al. (Limnology and Oceanography, 2018)
Inland and coastal waterbodies are critical components of the global biosphere. Timely monitoring is necessary to enhance our understanding of their functions, the drivers impacting on these functions and to deliver more effective management. The ability to observe waterbodies from space has led to Earth observation (EO) becoming established as an important source of information on water quality and ecosystem condition. However, progress toward a globally valid EO approach is still largely hampered by inconsistences over temporally and spatially variable in‐water optical conditions. In this study, a comprehensive dataset from more than 250 aquatic systems, representing a wide range of conditions, was analyzed in order to develop a typology of optical water types (OWTs) for inland and coastal waters. We introduce a novel approach for clustering in situ hyperspectral water reflectance measurements ( n = 4045) from multiple sources based on a functional data analysis. The resulting classification algorithm identified 13 spectrally distinct clusters of measurements in inland waters, and a further nine clusters from the marine environment. The distinction and characterization of OWTs was supported by the availability of a wide range of coincident data on biogeochemical and inherent optical properties from inland waters. Phylogenetic trees based on the shapes of cluster means were constructed to identify similarities among the derived clusters with respect to spectral diversity. This typification provides a valuable framework for a globally applicable EO scheme and the design of future EO missions.

Breaking Resilience for a Sustainable Future: Thoughts for the Anthropocene - Marion Glaser; Jeremiah G. Plass-Johnson; Sebastian C. A. Ferse; Muhammad Neil; Dewi Y. Satari; Mirta Teichberg; Hauke Reuter (Frontiers in Marine Science, 2018)

PpORS, an ancient type III polyketide synthase, is required for integrity of leaf cuticle and resistance to dehydration in the moss, Physcomitrella patens - Li Li; Misbah Aslam; Fazle Rabbi; Mark C. Vanderwel; Neil W. Ashton; Dae-Yeon Suh (Planta, 2018)

Links between parental life histories of wild salmon and the telomere lengths of their offspring - Darryl McLennan; John D. Armstrong; David C. Stewart; Simon McKelvey; Winnie Boner; Pat Monaghan; Neil B. Metcalfe (Molecular Ecology, 2018)
The importance of parental contributions to offspring development and subsequent performance is self‐evident at a genomic level; however, parents can also affect offspring fitness by indirect genetic and environmental routes. The life history strategy that an individual adopts will be influenced by both genes and environment; and this may have important consequences for offspring. Recent research has linked telomere dynamics (i.e., telomere length and loss) in early life to future viability and longevity. Moreover, a number of studies have reported a heritable component to telomere length across a range of vertebrates, although the effects of other parental contribution pathways have been far less studied. Using wild Atlantic salmon with different parental life histories in an experimental split‐brood in vitro fertilization mating design and rearing the resulting families under standardized conditions, we show that there can be significant links between parental life history and offspring telomere length (studied at the embryo and fry stage). Maternal life history traits, in particular egg size, were most strongly related to offspring telomere length at the embryonic stage, but then became weaker through development. In contrast, paternal life history traits, such as the father's growth rate in early life, had a greater association in the later stages of offspring development. However, offspring telomere length was not significantly related to either maternal or paternal age at reproduction, nor to paternal sperm telomere length. This study demonstrates both the complexity and the importance of parental factors that can influence telomere length in early life.

Nutrients from salmon parents alter selection pressures on their offspring - Sonya K. Auer; Graeme J. Anderson; Simon McKelvey; Ronald D. Bassar; Darryl McLennan; John D. Armstrong; Keith H. Nislow; Helen K. Downie; Lynn McKelvey; Thomas A.J. Morgan; Karine Salin; Danielle L. Orrell; et al. (Ecology Letters, 2018)
Organisms can modify their surrounding environment, but whether these changes are large enough to feed back and alter their evolutionary trajectories is not well understood, particularly in wild populations. Here we show that nutrient pulses from decomposing Atlantic salmon ( Salmo salar ) parents alter selection pressures on their offspring with important consequences for their phenotypic and genetic diversity. We found a strong survival advantage to larger eggs and faster juvenile metabolic rates in streams lacking carcasses but not in streams containing this parental nutrient input. Differences in selection intensities led to significant phenotypic divergence in these two traits among stream types. Stronger selection in streams with low parental nutrient input also decreased the number of surviving families compared to streams with high parental nutrient levels. Observed effects of parent‐derived nutrients on selection pressures provide experimental evidence for key components of eco‐evolutionary feedbacks in wild populations.

A synthesis of European seahorse taxonomy, population structure, and habitat use as a basis for assessment, monitoring and conservation - Lucy C. Woodall; Francisco Otero-Ferrer; Miguel Correia; Janelle M. R. Curtis; Neil Garrick-Maidment; Paul W. Shaw; Heather J. Koldewey (Marine Biology, 2018)

Somatic mutations of the coding microsatellites within the beta-2-microglobulin gene in mismatch repair-deficient colorectal cancers and adenomas - Mark Clendenning; Alvin Huang; Harindra Jayasekara; Marie Lorans; Susan Preston; Neil O’Callaghan; Bernard J. Pope; Finlay A. Macrae; Ingrid M. Winship; Roger L. Milne; Graham G. Giles; Dallas R. English; et al. (Familial Cancer, 2018)

Postnatal nutrition influences male attractiveness and promotes plasticity in male mating preferences - José C. Noguera; Neil B. Metcalfe; Pat Monaghan (The Science of Nature, 2017)

Developing an empirical approach to optimal camera-trap deployment at mammal resting sites: evidence from a longitudinal study of an otter Lutra lutra holt - Melanie A. Findlay; Robert A. Briers; Neil Diamond; Patrick J. C. White (European Journal of Wildlife Research, 2017)

Analysis of Potato Mop-Top Virus Survival Probability in Post-Harvest Storage - S. K. R. Yellareddygari; Owusu Domfeh; Francisco G. Bittara; Neil C. Gudmestad (American Journal of Potato Research, 2017)

Leaf temperature of maize and Crop Water Stress Index with variable irrigation and nitrogen supply - David A. Carroll; Neil C. Hansen; Bryan G. Hopkins; Kendall C. DeJonge (Irrigation Science, 2017)

A climatological model of North Indian Ocean tropical cyclone genesis, tracks and landfall - Mohammad Wahiduzzaman; Eric C. J. Oliver; Simon J. Wotherspoon; Neil J. Holbrook (Climate Dynamics, 2017)

Review of the ecosystem service implications of mangrove encroachment into salt marshes - Jeffrey J. Kelleway; Kyle Cavanaugh; Kerrylee Rogers; Ilka C. Feller; Emilie Ens; Cheryl Doughty; Neil Saintilan (Global Change Biology, 2017)
Salt marsh and mangrove have been recognized as being among the most valuable ecosystem types globally in terms of their supply of ecosystem services and support for human livelihoods. These coastal ecosystems are also susceptible to the impacts of climate change and rising sea levels, with evidence of global shifts in the distribution of mangroves, including encroachment into salt marshes. The encroachment of woody mangrove shrubs and trees into herbaceous salt marshes may represent a substantial change in ecosystem structure, although resulting impacts on ecosystem functions and service provisions are largely unknown. In this review, we assess changes in ecosystem services associated with mangrove encroachment. While there is quantitative evidence to suggest that mangrove encroachment may enhance carbon storage and the capacity of a wetland to increase surface elevation in response to sea‐level rise, for most services there has been no direct assessment of encroachment impact. On the basis of current understanding of ecosystem structure and function, we theorize that mangrove encroachment may increase nutrient storage and improve storm protection, but cause declines in habitat availability for fauna requiring open vegetation structure (such as migratory birds and foraging bats) as well as the recreational and cultural activities associated with this fauna (e.g., birdwatching and/or hunting). Changes to provisional services such as fisheries productivity and cultural services are likely to be site specific and dependent on the species involved. We discuss the need for explicit experimental testing of the effects of encroachment on ecosystem services in order to address key knowledge gaps, and present an overview of the options available to coastal resource managers during a time of environmental change.

Phytodetoxification of TNT by transplastomic tobacco (Nicotiana tabacum) expressing a bacterial nitroreductase - Long Zhang; Elizabeth L. Rylott; Neil C. Bruce; Stuart E. Strand (Plant Molecular Biology, 2017)

Patterns of divergence across the geographic and genomic landscape of a butterfly hybrid zone associated with a climatic gradient - Sean F. Ryan; Michael C. Fontaine; J. Mark Scriber; Michael E. Pfrender; Shawn T. O'Neil; Jessica J. Hellmann (Molecular Ecology, 2017)
Hybrid zones are a valuable tool for studying the process of speciation and for identifying the genomic regions undergoing divergence and the ecological (extrinsic) and nonecological (intrinsic) factors involved. Here, we explored the genomic and geographic landscape of divergence in a hybrid zone between Papilio glaucus and Papilio canadensis . Using a genome scan of 28,417 dd RAD SNP s, we identified genomic regions under possible selection and examined their distribution in the context of previously identified candidate genes for ecological adaptations. We showed that differentiation was genomewide, including multiple candidate genes for ecological adaptations, particularly those involved in seasonal adaptation and host plant detoxification. The Z chromosome and four autosomes showed a disproportionate amount of differentiation, suggesting genes on these chromosomes play a potential role in reproductive isolation. Cline analyses of significantly differentiated genomic SNP s, and of species‐diagnostic genetic markers, showed a high degree of geographic coincidence (81%) and concordance (80%) and were associated with the geographic distribution of a climate‐mediated developmental threshold (length of the growing season). A relatively large proportion (1.3%) of the outliers for divergent selection were not associated with candidate genes for ecological adaptations and may reflect the presence of previously unrecognized intrinsic barriers between these species. These results suggest that exogenous (climate‐mediated) and endogenous (unknown) clines may have become coupled and act together to reinforce reproductive isolation. This approach of assessing divergence across both the genomic and geographic landscape can provide insight about the interplay between the genetic architecture of reproductive isolation and endogenous and exogenous selection.

Drought-Tolerant Brassica rapa Shows Rapid Expression of Gene Networks for General Stress Responses and Programmed Cell Death Under Simulated Drought Stress - Yi Ming Guo; Birgit Samans; Sheng Chen; Kidist B. Kibret; Sarah Hatzig; Neil C. Turner; Matthew N. Nelson; Wallace A. Cowling; Rod J. Snowdon (Plant Molecular Biology Reporter, 2017)

Dynamics of direct inter-pack encounters in endangered African wild dogs - Neil R Jordan; Christopher Buse; Alan M Wilson; Krystyna A Golabek; Peter J Apps; John C Lowe; Leanne K Van der Weyde; J Weldon McNutt (Behavioral Ecology and Sociobiology, 2017)

Corrigendum: Flow and Coral Morphology Control Coral Surface pH: Implications for the Effects of Ocean Acidification - Neil C. S. Chan; Daniel Wangpraseurt; Michael Kühl; Sean R. Connolly (Frontiers in Marine Science, 2017)

Emergent climate and CO 2 sensitivities of net primary productivity in ecosystem models do not agree with empirical data in temperate forests of eastern North America - Christine R. Rollinson; Yao Liu; Ann Raiho; David J. P. Moore; Jason McLachlan; Daniel A. Bishop; Alex Dye; Jaclyn H. Matthes; Amy Hessl; Thomas Hickler; Neil Pederson; Benjamin Poulter; et al. (Global Change Biology, 2017)
Ecosystem models show divergent responses of the terrestrial carbon cycle to global change over the next century. Individual model evaluation and multimodel comparisons with data have largely focused on individual processes at subannual to decadal scales. Thus far, data‐based evaluations of emergent ecosystem responses to climate and CO 2 at multidecadal and centennial timescales have been rare. We compared the sensitivity of net primary productivity ( NPP ) to temperature, precipitation, and CO 2 in ten ecosystem models with the sensitivities found in tree‐ring reconstructions of NPP and raw ring‐width series at six temperate forest sites. These model‐data comparisons were evaluated at three temporal extents to determine whether the rapid, directional changes in temperature and CO 2 in the recent past skew our observed responses to multiple drivers of change. All models tested here were more sensitive to low growing season precipitation than tree‐ring NPP and ring widths in the past 30 years, although some model precipitation responses were more consistent with tree rings when evaluated over a full century. Similarly, all models had negative or no response to warm‐growing season temperatures, while tree‐ring data showed consistently positive effects of temperature. Although precipitation responses were least consistent among models, differences among models to CO 2 drive divergence and ensemble uncertainty in relative change in NPP over the past century. Changes in forest composition within models had no effect on climate or CO 2 sensitivity. Fire in model simulations reduced model sensitivity to climate and CO 2 , but only over the course of multiple centuries. Formal evaluation of emergent model behavior at multidecadal and multicentennial timescales is essential to reconciling model projections with observed ecosystem responses to past climate change. Future evaluation should focus on improved representation of disturbance and biomass change as well as the feedbacks with moisture balance and CO 2 in individual models.

Surveying employment listings to inform curricula of environmental science degree programs - Mackenzie Wood; Stephen Taylor; Alex Carroll; Neil C. Hansen (Journal of Environmental Studies and Sciences, 2017)

Vulnerability of aquaculture‐related livelihoods to changing climate at the global scale - Neil Handisyde; Trevor C Telfer; Lindsay G Ross (Fish and Fisheries, 2017)
There is now a strong consensus that during the 20th century, and especially during recent decades, the earth has experienced a significant warming trend with projections suggesting additional further warming during the 21st century. Associated with this warming trend are changes in climate that are expected to show substantial spatial variability across the earth's surface. Globally, fish production has continued to increase during recent years at a rate exceeding that of human population growth. However, the contribution from capture fisheries has remained largely static since the late 1980s with the increase in production being accounted for by dramatic growth in the aquaculture sector. In this study, the distribution of vulnerability of aquaculture‐related livelihoods to climate change was assessed at the global scale based on the concept of vulnerability as a function of sensitivity to climate change, exposure to climate change and adaptive capacity. Use was made of national‐level statistics along with gridded climate and population data. Climate change scenarios were supplied using the MAGICC / SCENGEN climate modelling tools. Analysis was conducted for aquaculture in freshwater, brackish and marine environments with outputs represented as a series of raster images. A number of Asian countries (Vietnam, Bangladesh, Laos and China) were indicated as most vulnerable to impacts on freshwater production. Vietnam, Thailand, Egypt and Ecuador stood out in terms of brackish water production. Norway and Chile were considered most vulnerable to impacts on marine production while a number of Asian countries (China, Vietnam and the Philippines) also ranked highly.

Crop health and its global impacts on the components of food security - S. Savary; S. Bregaglio; L. Willocquet; D. Gustafson; D. Mason D’Croz; A. Sparks; N. Castilla; A. Djurle; C. Allinne; Mamta Sharma; V. Rossi; L. Amorim; et al. (Food Security, 2017)

Strong isolation by distance argues for separate population management of endangered blue duck (Hymenolaimus malacorhynchos) - Stefanie Grosser; Jawad Abdelkrim; Janine Wing; Bruce C. Robertson; Neil J. Gemmell (Conservation Genetics, 2017)

Seasonal spatial patterns of projected anthropogenic warming in complex terrain: a modeling study of the western US - David E. Rupp; Sihan Li; Philip W. Mote; Karen M. Shell; Neil Massey; Sarah N. Sparrow; David C. H. Wallom; Myles R. Allen (Climate Dynamics, 2017)

Chloropicrin Soil Fumigation Reduces Spongospora subterranea Soil Inoculum Levels but Does Not Control Powdery Scab Disease on Roots and Tubers of Potato - Francisco G. Bittara; Gary A. Secor; Neil C. Gudmestad (American Journal of Potato Research, 2017)

Genomic epidemiology of Cryptococcus yeasts identifies adaptation to environmental niches underpinning infection across an African HIV / AIDS cohort - Mathieu Vanhove; Mathew A. Beale; Johanna Rhodes; Duncan Chanda; Shabir Lakhi; Geoffrey Kwenda; Sile Molloy; Natasha Karunaharan; Neil Stone; Thomas S. Harrison; Tihana Bicanic; Matthew C. Fisher (Molecular Ecology, 2017)
Emerging infections caused by fungi have become a widely recognized global phenomenon and are causing an increasing burden of disease. Genomic techniques are providing new insights into the structure of fungal populations, revealing hitherto undescribed fine‐scale adaptations to environments and hosts that govern their emergence as infections. Cryptococcal meningitis is a neglected tropical disease that is responsible for a large proportion of AIDS ‐related deaths across Africa; however, the ecological determinants that underlie a patient's risk of infection remain largely unexplored. Here, we use genome sequencing and ecological genomics to decipher the evolutionary ecology of the aetiological agents of cryptococcal meningitis, Cryptococcus neoformans and Cryptococcus gattii , across the central African country of Zambia. We show that the occurrence of these two pathogens is differentially associated with biotic (macroecological) and abiotic (physical) factors across two key African ecoregions, Central Miombo woodlands and Zambezi Mopane woodlands. We show that speciation of Cryptococcus has resulted in adaptation to occupy different ecological niches, with C. neoformans found to occupy Zambezi Mopane woodlands and C. gattii primarily recovered from Central Miombo woodlands. Genome sequencing shows that C. neoformans causes 95% of human infections in this region, of which over three‐quarters belonged to the globalized lineage VNI . We show that VNI infections are largely associated with urbanized populations in Zambia. Conversely, the majority of C. neoformans isolates recovered in the environment belong to the genetically diverse African‐endemic lineage VNB , and we show hitherto unmapped levels of genomic diversity within this lineage. Our results reveal the complex evolutionary ecology that underpins the reservoirs of infection for this, and likely other, deadly pathogenic fungi.

2,5-diketopiperazines in food and beverages: Taste and bioactivity - Alan D. Borthwick; Neil C. Da Costa (Critical Reviews in Food Science and Nutrition, 2017)

New insights into the photochemistry of carotenoid spheroidenone in light-harvesting complex 2 from the purple bacterium Rhodobacter sphaeroides - Dariusz M. Niedzwiedzki; Preston L. Dilbeck; Qun Tang; Elizabeth C. Martin; David F. Bocian; C. Neil Hunter; Dewey Holten (Photosynthesis Research, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

A multicenter assessment of single-cell models aligned to standard measures of cell health for prediction of acute hepatotoxicity - Rowena L. Sison-Young; Volker M. Lauschke; Esther Johann; Eliane Alexandre; Sébastien Antherieu; Hélène Aerts; Helga H. J. Gerets; Gilles Labbe; Delphine Hoët; Martina Dorau; Christopher A. Schofield; Cerys A. Lovatt; et al. (Archives of Toxicology, 2017)

Bat collisions with civil aircraft in the Republic of Ireland over a decade suggest negligible impact on aviation safety - Thomas C. Kelly; D. Paddy Sleeman; Neil E. Coughlan; Eileen Dillane; Michael J.A. O’Callaghan (European Journal of Wildlife Research, 2017)

“Step by step”: high frequency short-distance epizoochorous dispersal of aquatic macrophytes - Neil E. Coughlan; Thomas C. Kelly; Marcel A. K. Jansen (Biological Invasions, 2017)

Expansion of mossy fibers and CA3 apical dendritic length accompanies the fall in dendritic spine density after gonadectomy in male, but not female, rats - Ari L. Mendell; Sarah Atwi; Craig D. C. Bailey; Dan McCloskey; Helen E. Scharfman; Neil J. MacLusky (Brain Structure and Function, 2017)

An assessment of ectomycorrhizal fungal communities in Tasmanian temperate high-altitude Eucalyptus delegatensis forest reveals a dominance of the Cortinariaceae - Bryony M. Horton; Morag Glen; Neil J. Davidson; David A. Ratkowsky; Dugald C. Close; Tim J. Wardlaw; Caroline Mohammed (Mycorrhiza, 2017)

Ecosystem effects of invertebrate fisheries - Tyler D Eddy; Heike K Lotze; Elizabeth A Fulton; Marta Coll; Cameron H Ainsworth; Júlio Neves de Araújo; Catherine M Bulman; Alida Bundy; Villy Christensen; John C Field; Neil A Gribble; Mejs Hasan; et al. (Fish and Fisheries, 2017)
Since the 1950s, invertebrate fisheries catches have rapidly expanded globally to more than 10 million tonnes annually, with twice as many target species, and are now significant contributors to global seafood provision, export, trade and local livelihoods. Invertebrates play important and diverse functional roles in marine ecosystems, yet the ecosystem effects of their exploitation are poorly understood. Using 12 ecosystem models distributed worldwide, we analysed the trade‐offs of various invertebrate fisheries and their ecosystem effects as well as ecological indicators. Although less recognized for their contributions to marine food webs, our results show that the magnitude of trophic impacts of invertebrates on other species of commercial and conservation interest is comparable with those of forage fish. Generally, cephalopods showed the strongest ecosystem effects and were characterized by a strong top‐down predatory role. Lobster, and to a lesser extent, crabs, shrimp and prawns, also showed strong ecosystem effects, but at lower trophic levels. Benthic invertebrates, including epifauna and infauna, also showed considerable ecosystem effects, but with strong bottom‐up characteristics. In contrast, urchins, bivalves, and gastropods showed generally lower ecosystem effects in our simulations. Invertebrates also strongly contributed to benthic–pelagic coupling, with exploitation of benthic invertebrates impacting pelagic fishes and vice versa. Finally, on average, invertebrates produced maximum sustainable yield at lower levels of depletion (~45%) than forage fish (~65%), highlighting the need for management targets that avoid negative consequences for target species and marine ecosystems as a whole.

Comment on: “The spatial extent of the Deep Western Boundary Current into the Bounty Trough: new evidence from parasound sub-bottom profiling” by Horn and Uenzelmann-Neben - Neil C. Mitchell (Marine Geophysical Research, 2016)

Aquatic food security: insights into challenges and solutions from an analysis of interactions between fisheries, aquaculture, food safety, human health, fish and human welfare, economy and environment - Simon Jennings; Grant D Stentiford; Ana M Leocadio; Keith R Jeffery; Julian D Metcalfe; Ioanna Katsiadaki; Neil A Auchterlonie; Stephen C Mangi; John K Pinnegar; Tim Ellis; Edmund J Peeler; Tiziana Luisetti; et al. (Fish and Fisheries, 2016)
Fisheries and aquaculture production, imports, exports and equitability of distribution determine the supply of aquatic food to people. Aquatic food security is achieved when a food supply is sufficient, safe, sustainable, shockproof and sound: sufficient, to meet needs and preferences of people; safe, to provide nutritional benefit while posing minimal health risks; sustainable, to provide food now and for future generations; shock‐proof, to provide resilience to shocks in production systems and supply chains; and sound, to meet legal and ethical standards for welfare of animals, people and environment. Here, we present an integrated assessment of these elements of the aquatic food system in the United Kingdom, a system linked to dynamic global networks of producers, processors and markets. Our assessment addresses sufficiency of supply from aquaculture, fisheries and trade; safety of supply given biological, chemical and radiation hazards; social, economic and environmental sustainability of production systems and supply chains; system resilience to social, economic and environmental shocks; welfare of fish, people and environment; and the authenticity of food. Conventionally, these aspects of the food system are not assessed collectively, so information supporting our assessment is widely dispersed. Our assessment reveals trade‐offs and challenges in the food system that are easily overlooked in sectoral analyses of fisheries, aquaculture, health, medicine, human and fish welfare, safety and environment. We highlight potential benefits of an integrated, systematic and ongoing process to assess security of the aquatic food system and to predict impacts of social, economic and environmental change on food supply and demand.

Natural hazards in Australia: sea level and coastal extremes - Kathleen L. McInnes; Christopher J. White; Ivan D. Haigh; Mark A. Hemer; Ron K. Hoeke; Neil J. Holbrook; Anthony S. Kiem; Eric C. J. Oliver; Roshanka Ranasinghe; Kevin J. E. Walsh; Seth Westra; Ron Cox (Climatic Change, 2016)

Tree-ring reconstructed May–June precipitation in the Caucasus since 1752 CE - Dario Martin-Benito; Caroline C. Ummenhofer; Nesibe Köse; Hüseyin Tuncay Güner; Neil Pederson (Climate Dynamics, 2016)

Quantifying system disturbance and recovery from historical mining-derived metal contamination at Brotherswater, northwest England - Daniel N. Schillereff; Richard C. Chiverrell; Neil Macdonald; Janet M. Hooke; Katharine E. Welsh (Journal of Paleolimnology, 2016)

Chemical contamination of soils in the New York City area following Hurricane Sandy - Amy C. Mandigo; Dana J. DiScenza; Alison R. Keimowitz; Neil Fitzgerald (Environmental Geochemistry and Health, 2016)

Influence of tropical wind on global temperature from months to decades - Oleg A. Saenko; John C. Fyfe; Neil C. Swart; Warren G. Lee; Matthew H. England (Climate Dynamics, 2016)

Field Evaluation of Potato Genotypes for Resistance to Powdery Scab on Tubers and Root Gall Formation Caused by Spongospora subterranea - Francisco G. Bittara; Asunta L. Thompson; Neil C. Gudmestad; Gary A. Secor (American Journal of Potato Research, 2016)

Projected impacts of 21st century climate change on diapause in Calanus finmarchicus - Robert J. Wilson; Neil S. Banas; Michael R. Heath; Douglas C. Speirs (Global Change Biology, 2016)
Diapause plays a key role in the life cycle of high latitude zooplankton. During diapause, animals avoid starving in winter by living in deep waters where metabolism is lower and met by lipid reserves. Global warming is therefore expected to shorten the maximum potential diapause duration by increasing metabolic rates and by reducing body size and lipid reserves. This will alter the phenology of zooplankton, impact higher trophic levels and disrupt biological carbon pumps. Here, we project the impacts of climate change on the key North Atlantic copepod Calanus finmarchicus under IPCC RCP 8.5. Potential diapause duration is modelled in relation to body size and overwintering temperature. The projections show pronounced geographic variations. Potential diapause duration reduces by more than 30% in the Western Atlantic, whereas in the key overwintering centre of the Norwegian Sea it changes only marginally. Surface temperature rises, which reduce body size and lipid reserves, will have a similar impact to deep‐water changes on diapause in many regions. Because deep‐water warming lags that at the surface, animals in the Labrador Sea could offset warming impacts by diapausing in deeper waters. However, the ability to control diapause depth may be limited.

Persulfate Interaction with Tropical Soils - Fernanda C. Oliveira; Juliana G. Freitas; Sheila A. C. Furquim; Renata M. Rollo; Neil R. Thomson; Luís R. F. Alleoni; Claudio A. O. Nascimento (Water, Air, & Soil Pollution, 2016)

αv integrins: key regulators of tissue fibrosis - Kylie P. Conroy; Laura J. Kitto; Neil C. Henderson (Cell and Tissue Research, 2016)

Is risk consistent across tier‐based harvest control rule management systems? A comparison of four case‐studies - Catherine M Dichmont; André E Punt; Natalie Dowling; José A A De Oliveira; Lorne R Little; Miriana Sporcic; Elizabeth Fulton; Rebecca Gorton; Neil Klaer; Malcolm Haddon; David C Smith (Fish and Fisheries, 2016)
There can be substantial differences in data quality and quantity among fished species. Consequently, the quality and type of assessments can also vary substantially. However, all species, especially those that are targeted, need to be managed. Several jurisdictions have developed hierarchical tier systems that categorize stocks based on, for example, the data available for assessment purposes and/or the extent to which quantities on which management advice is based can be estimated. Four case‐studies (Australia's Southern and Eastern Scalefish and Shark Fishery, the USA west coast groundfishery, the USA Alaskan crab fishery and EU fisheries) are used to contrast the types of hierarchical tier systems available, and to assess the extent to which each system constrains risk to be equivalent among the tiers (termed risk equivalency). Only the Australian system explicitly aims to achieve risk equivalency. However, this intent has not been fully operationalized. Our review reveals that best practice is not to define tiers simply on data availability, but also on what the assessments based on those data are capable of estimating. In addition, clearly differentiating the quantification of uncertainty from how decision‐makers wish to address that uncertainty would simplify justification of buffers (the gap between the assessment‐produced target catch or effort and the final management decision that accounts for uncertainty and risk). Risk equivalency can be achieved using management strategy evaluation to select the values for control variables, which determine the buffer given the uncertainty associated with the assessment.

Land cover change and carbon emissions over 100 years in an A frican biodiversity hotspot - Simon Willcock; Oliver L. Phillips; Philip J. Platts; Ruth D. Swetnam; Andrew Balmford; Neil D. Burgess; Antje Ahrends; Julian Bayliss; Nike Doggart; Kathryn Doody; Eibleis Fanning; Jonathan M. H. Green; et al. (Global Change Biology, 2016)
Agricultural expansion has resulted in both land use and land cover change ( LULCC ) across the tropics. However, the spatial and temporal patterns of such change and their resulting impacts are poorly understood, particularly for the presatellite era. Here, we quantify the LULCC history across the 33.9 million ha watershed of Tanzania's Eastern Arc Mountains, using geo‐referenced and digitized historical land cover maps (dated 1908, 1923, 1949 and 2000). Our time series from this biodiversity hotspot shows that forest and savanna area both declined, by 74% (2.8 million ha) and 10% (2.9 million ha), respectively, between 1908 and 2000. This vegetation was replaced by a fivefold increase in cropland, from 1.2 million ha to 6.7 million ha. This LULCC implies a committed release of 0.9 Pg C (95% CI : 0.4–1.5) across the watershed for the same period, equivalent to 0.3 Mg C ha −1 yr −1 . This is at least threefold higher than previous estimates from global models for the same study area. We then used the LULCC data from before and after protected area creation, as well as from areas where no protection was established, to analyse the effectiveness of legal protection on land cover change despite the underlying spatial variation in protected areas. We found that, between 1949 and 2000, forest expanded within legally protected areas, resulting in carbon uptake of 4.8 (3.8–5.7) Mg C ha −1 , compared to a committed loss of 11.9 (7.2–16.6) Mg C ha −1 within areas lacking such protection. Furthermore, for nine protected areas where LULCC data are available prior to and following establishment, we show that protection reduces deforestation rates by 150% relative to unprotected portions of the watershed. Our results highlight that considerable LULCC occurred prior to the satellite era, thus other data sources are required to better understand long‐term land cover trends in the tropics.

Winter precipitation and snow accumulation drive the methane sink or source strength of Arctic tussock tundra - Elena Blanc‐Betes; Jeffrey M. Welker; Neil C. Sturchio; Jeffrey P. Chanton; Miquel A. Gonzalez‐Meler (Global Change Biology, 2016)
Arctic winter precipitation is projected to increase with global warming, but some areas will experience decreases in snow accumulation. Although Arctic CH 4 emissions may represent a significant climate forcing feedback, long‐term impacts of changes in snow accumulation on CH 4 fluxes remain uncertain. We measured ecosystem CH 4 fluxes and soil CH 4 and CO 2 concentrations and 13 C composition to investigate the metabolic pathways and transport mechanisms driving moist acidic tundra CH 4 flux over the growing season (Jun–Aug) after 18 years of experimental snow depth increases and decreases. Deeper snow increased soil wetness and warming, reducing soil %O 2 levels and increasing thaw depth. Soil moisture, through changes in soil %O 2 saturation, determined predominance of methanotrophy or methanogenesis, with soil temperature regulating the ecosystem CH 4 sink or source strength. Reduced snow (RS) increased the fraction of oxidized CH 4 (Fox) by 75–120% compared to Ambient, switching the system from a small source to a net CH 4 sink (21 ± 2 and −31 ± 1 mg CH 4 m −2 season −1 at Ambient and RS). Deeper snow reduced Fox by 35–40% and 90–100% in medium‐ (MS) and high‐ (HS) snow additions relative to Ambient, contributing to increasing the CH 4 source strength of moist acidic tundra (464 ± 15 and 3561 ± 97 mg CH 4 m −2 season −1 at MS and HS). Decreases in Fox with deeper snow were partly due to increases in plant‐mediated CH 4 transport associated with the expansion of tall graminoids. Deeper snow enhanced CH 4 production within newly thawed soils, responding mainly to soil warming rather than to increases in acetate fermentation expected from thaw‐induced increases in SOC availability. Our results suggest that increased winter precipitation will increase the CH 4 source strength of Arctic tundra, but the resulting positive feedback on climate change will depend on the balance between areas with more or less snow accumulation than they are currently facing.

Comparison of abdominal adiposity and overall obesity in relation to risk of small intestinal cancer in a European Prospective Cohort - Yunxia Lu; Amanda J. Cross; Neil Murphy; Heinz Freisling; Ruth C. Travis; Pietro Ferrari; Verena A. Katzke; Rudolf Kaaks; Åsa Olsson; Ingegerd Johansson; Frida Renström; Salvatore Panico; et al. (Cancer Causes & Control, 2016)

Genetic diversity of Colletotrichum coccodes in the United States using amplified fragment length polymorphism analysis - Kholoud M. Alananbeh; Neil C. Gudmestad (Journal of General Plant Pathology, 2016)

The value of crossdating to retain high‐frequency variability, climate signals, and extreme events in environmental proxies - Bryan A. Black; Daniel Griffin; Peter van der Sleen; Alan D. Wanamaker; James H. Speer; David C. Frank; David W. Stahle; Neil Pederson; Carolyn A. Copenheaver; Valerie Trouet; Shelly Griffin; Bronwyn M. Gillanders (Global Change Biology, 2016)
High‐resolution biogenic and geologic proxies in which one increment or layer is formed per year are crucial to describing natural ranges of environmental variability in Earth's physical and biological systems. However, dating controls are necessary to ensure temporal precision and accuracy; simple counts cannot ensure that all layers are placed correctly in time. Originally developed for tree‐ring data, crossdating is the only such procedure that ensures all increments have been assigned the correct calendar year of formation. Here, we use growth‐increment data from two tree species, two marine bivalve species, and a marine fish species to illustrate sensitivity of environmental signals to modest dating error rates. When falsely added or missed increments are induced at one and five percent rates, errors propagate back through time and eliminate high‐frequency variability, climate signals, and evidence of extreme events while incorrectly dating and distorting major disturbances or other low‐frequency processes. Our consecutive Monte Carlo experiments show that inaccuracies begin to accumulate in as little as two decades and can remove all but decadal‐scale processes after as little as two centuries. Real‐world scenarios may have even greater consequence in the absence of crossdating. Given this sensitivity to signal loss, the fundamental tenets of crossdating must be applied to fully resolve environmental signals, a point we underscore as the frontiers of growth‐increment analysis continue to expand into tropical, freshwater, and marine environments.

The impacts of increasing drought on forest dynamics, structure, and biodiversity in the United States - James S. Clark; Louis Iverson; Christopher W. Woodall; Craig D. Allen; David M. Bell; Don C. Bragg; Anthony W. D'Amato; Frank W. Davis; Michelle H. Hersh; Ines Ibanez; Stephen T. Jackson; Stephen Matthews; et al. (Global Change Biology, 2016)
We synthesize insights from current understanding of drought impacts at stand‐to‐biogeographic scales, including management options, and we identify challenges to be addressed with new research. Large stand‐level shifts underway in western forests already are showing the importance of interactions involving drought, insects, and fire. Diebacks, changes in composition and structure, and shifting range limits are widely observed. In the eastern US , the effects of increasing drought are becoming better understood at the level of individual trees, but this knowledge cannot yet be confidently translated to predictions of changing structure and diversity of forest stands. While eastern forests have not experienced the types of changes seen in western forests in recent decades, they too are vulnerable to drought and could experience significant changes with increased severity, frequency, or duration in drought. Throughout the continental United States, the combination of projected large climate‐induced shifts in suitable habitat from modeling studies and limited potential for the rapid migration of tree populations suggests that changing tree and forest biogeography could substantially lag habitat shifts already underway. Forest management practices can partially ameliorate drought impacts through reductions in stand density, selection of drought‐tolerant species and genotypes, artificial regeneration, and the development of multistructured stands. However, silvicultural treatments also could exacerbate drought impacts unless implemented with careful attention to site and stand characteristics. Gaps in our understanding should motivate new research on the effects of interactions involving climate and other species at the stand scale and how interactions and multiple responses are represented in models. This assessment indicates that, without a stronger empirical basis for drought impacts at the stand scale, more complex models may provide limited guidance.

Bacterial sensing underlies artificial sweetener‐induced growth of gut L actobacillus - Kristian Daly; Alistair C. Darby; Neil Hall; Mark C. Wilkinson; Pisut Pongchaikul; David Bravo; Soraya P. Shirazi‐Beechey (Environmental Microbiology, 2016)
Summary Disruption in stable establishment of commensal gut microbiota by early weaning is an important factor in susceptibility of young animals to enteric disorders. The artificial sweetener SUCRAM [consisting of neohesperidin dihydrochalcone ( NHDC ) and saccharin] included in piglets' feed reduces incidence of enteric disease. Pyrosequencing of pig caecal 16S r RNA gene amplicons identified 25 major families encompassing seven bacterial classes with B acteroidia , C lostridia and B acilli dominating the microbiota. There were significant shifts in microbial composition in pigs maintained on a diet containing SUCRAM , establishing SUCRAM as a major influence driving bacterial community dynamics. The most notable change was a significant increase of Lactobacillaceae population abundance, almost entirely due to a single phylotype, designated L actobacillus 4228. The sweetener‐induced increase in L actobacillaceae was observed in two different breeds of pigs signifying a general effect. We isolated Lactobacillus 4228, sequenced its genome and found it to be related to L actobacillus amylovorus . In vitro analyses of L actobacillus 4228 growth characteristics showed that presence of NHDC significantly reduces the lag phase of growth and enhances expression of specific sugar transporters, independently of NHDC metabolism. This study suggests that sensing of NHDC by a bacterial plasma membrane receptor underlies sweetener‐induced growth of a health promoting gut bacterium.

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

The canalized parental roles of a Eudyptes penguin constrain provisioning and growth of chicks during nutritional stress - Kyle W. Morrison; Neil C. Morrison; Raymond M. Buchheit; Rob Dunn; Phil F. Battley; David R. Thompson (Behavioral Ecology and Sociobiology, 2016)

Ecosystem services in managing residential landscapes: priorities, value dimensions, and cross-regional patterns - K. L. Larson; K. C. Nelson; S. R. Samples; S. J. Hall; N. Bettez; J. Cavender-Bares; P. M. Groffman; M. Grove; J. B. Heffernan; S. E. Hobbie; J. Learned; J. L. Morse; et al. (Urban Ecosystems, 2016)

Establishment and characterization of feeder cell-dependent bovine fetal liver cell lines - Neil C. Talbot; Ling Wang; Wesley M. Garrett; Thomas J. Caperna; Young Tang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Alcelaphine herpesvirus 1 glycoprotein B: recombinant expression and antibody recognition - Inga Dry; Helen Todd; David Deane; Ann Percival; Kevin Mclean; Neil F. Inglis; Erin D. T. Manson; David M. Haig; Shilpa Nayuni; Lindsey M. Hutt-Fletcher; Dawn M. Grant; Kathryn Bartley; et al. (Archives of Virology, 2016)

Flow and Coral Morphology Control Coral Surface pH: Implications for the Effects of Ocean Acidification - Neil C. S. Chan; Daniel Wangpraseurt; Michael Kühl; Sean R. Connolly (Frontiers in Marine Science, 2016)

Supramolecular organization of photosynthetic complexes in membranes of Roseiflexus castenholzii - Erica L.-W. Majumder; John D. Olsen; Pu Qian; Aaron M. Collins; C. Neil Hunter; Robert E. Blankenship (Photosynthesis Research, 2016)

Patterns of soil water repellency in response to coarse woody debris and fire: implications for eucalypt regeneration in dry forests - Tanya G. Bailey; Neil J. Davidson; Dugald C. Close (Plant and Soil, 2015)

Climate change, climate justice and the application of probabilistic event attribution to summer heat extremes in the California Central Valley - Roberto Mera; Neil Massey; David E. Rupp; Philip Mote; Myles Allen; Peter C. Frumhoff (Climatic Change, 2015)

Oxygen stable isotope ratios from British oak tree-rings provide a strong and consistent record of past changes in summer rainfall - Giles H. F. Young; Neil J. Loader; Danny McCarroll; Roderick J. Bale; Joanne C. Demmler; Daniel Miles; Nigel T. Nayling; Katja T. Rinne; Iain Robertson; Camilla Watts; Matthew Whitney (Climate Dynamics, 2015)

Determinants of the t(14;18) translocation and their role in t(14;18)-positive follicular lymphoma - Rachel S. Kelly; Sandrine Roulland; Ester Morgado; Stéphanie Sungalee; Nathalie Jouve; Rosario Tumino; Vittorio Krogh; Salvatore Panico; Silvia Polidoro; Giovanna Masala; María-José Sánchez; Maria-Dolores Chirlaque; et al. (Cancer Causes & Control, 2015)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

The mineralogy and fabric of ‘Brickearths’ in Kent, UK and their relationship to engineering behaviour - Antoni E. Milodowski; Kevin J. Northmore; Simon J. Kemp; David C. Entwisle; David A. Gunn; Peter D. Jackson; David I. Boardman; Aris Zoumpakis; Christopher D. F. Rogers; Neil Dixon; Ian Jefferson; Ian J. Smalley; et al. (Bulletin of Engineering Geology and the Environment, 2015)

A mouse informatics platform for phenotypic and translational discovery - Natalie Ring; Terrence F. Meehan; Andrew Blake; James Brown; Chao-Kung Chen; Nathalie Conte; Armida Di Fenza; Tanja Fiegel; Neil Horner; Julius O. B. Jacobsen; Natasha Karp; Thomas Lawson; et al. (Mammalian Genome, 2015)

Cellular therapy in combination with cytokines improves survival in a xenograft mouse model of ovarian cancer - Susan B. Ingersoll; Sarfraz Ahmad; Hasina C. McGann; Robert K. Banks; Nicole M. Stavitzski; Milan Srivastava; Ghazanfar Ali; Neil J. Finkler; John R. Edwards; Robert W. Holloway (Molecular and Cellular Biochemistry, 2015)

Evaluating the landscape of fear between apex predatory sharks and mobile sea turtles across a large dynamic seascape - Neil Hammerschlag; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark Dodd; Michael G. Frick; Matthew H. Godfrey; Brendan J. Godley; DuBose B. Griffin; Kyra Hartog; Sally R. Murphy; Thomas M. Murphy; et al. (Ecology, 2015)
The “landscape of fear” model has been proposed as a unifying concept in ecology, describing, in part, how animals behave and move about in their environment. The basic model predicts that as an animal's landscape changes from low to high risk of predation, prey species will alter their behavior to risk avoidance. However, studies investigating and evaluating the landscape of fear model across large spatial scales (tens to hundreds of thousands of square kilometers) in dynamic, open, aquatic systems involving apex predators and highly mobile prey are lacking. To address this knowledge gap, we investigated predator–prey relationships between tiger sharks ( Galeocerdo cuvier ) and loggerhead turtles ( Caretta caretta ) in the North Atlantic Ocean. This included the use of satellite tracking to examine shark and turtle distributions as well as their surfacing behaviors under varying levels of home range overlap. Our findings revealed patterns that deviated from our a priori predictions based on the landscape of fear model. Specifically, turtles did not alter their surfacing behaviors to risk avoidance when overlap in shark–turtle core home range was high. However, in areas of high overlap with turtles, sharks exhibited modified surfacing behaviors that may enhance predation opportunity. We suggest that turtles may be an important factor in determining shark distribution, whereas for turtles, other life history trade‐offs may play a larger role in defining their habitat use. We propose that these findings are a result of both biotic and physically driven factors that independently or synergistically affect predator–prey interactions in this system. These results have implications for evolutionary biology, community ecology, and wildlife conservation. Further, given the difficulty in studying highly migratory marine species, our approach and conclusions may be applied to the study of other predator–prey systems.

Changes in root morphology and physiology to limited phosphorus and moisture in a locally-selected cultivar and an introduced cultivar of Medicago sativa L. growing in alkaline soil - Jing-Wei Fan; Yan-Lei Du; Neil C. Turner; Bing-Ru Wang; Yan Fang; Yue Xi; Xiao-Ran Guo; Feng-Min Li (Plant and Soil, 2015)

The influence of estradiol on muscle damage and leg strength after intense eccentric exercise - Clare Minahan; Sarah Joyce; Andrew C. Bulmer; Neil Cronin; Surendran Sabapathy (European Journal of Applied Physiology, 2015)

Climate remains an important driver of post‐European vegetation change in the eastern United States - Neil Pederson; Anthony W. D'Amato; James M. Dyer; David R. Foster; David Goldblum; Justin L. Hart; Amy E. Hessl; Louis R. Iverson; Stephen T. Jackson; Dario Martin‐Benito; Brian C. McCarthy; Ryan W. McEwan; et al. (Global Change Biology, 2015)

Groundwater movement, recharge, and perchlorate occurrence in a faulted alluvial aquifer in California (USA) - John A. Izbicki; Nicholas F. Teague; Paul B. Hatzinger; J. K. Böhlke; Neil C. Sturchio (Hydrogeology Journal, 2015)

A protocol for eliciting nonmaterial values through a cultural ecosystem services frame - Rachelle K. Gould; Sarah C. Klain; Nicole M. Ardoin; Terre Satterfield; Ulalia Woodside; Neil Hannahs; Gretchen C. Daily; Kai M. Chan (Conservation Biology, 2015)
Stakeholders’ nonmaterial desires, needs, and values often critically influence the success of conservation projects. These considerations are challenging to articulate and characterize, resulting in their limited uptake in management and policy. We devised an interview protocol designed to enhance understanding of cultural ecosystem services (CES). The protocol begins with discussion of ecosystem‐related activities (e.g., recreation, hunting) and management and then addresses CES, prompting for values encompassing concepts identified in the Millennium Ecosystem Assessment (2005) and explored in other CES research. We piloted the protocol in Hawaii and British Columbia. In each location, we interviewed 30 individuals from diverse backgrounds. We analyzed results from the 2 locations to determine the effectiveness of the interview protocol in elucidating nonmaterial values. The qualitative and spatial components of the protocol helped characterize cultural, social, and ethical values associated with ecosystems in multiple ways. Maps and situational, or vignette‐like, questions helped respondents articulate difficult‐to‐discuss values. Open‐ended prompts allowed respondents to express a diversity of ecosystem‐related values and proved sufficiently flexible for interviewees to communicate values for which the protocol did not explicitly probe. Finally, the results suggest that certain values, those mentioned frequently throughout the interview, are particularly salient for particular populations. The protocol can provide efficient, contextual, and place‐based data on the importance of particular ecosystem attributes for human well‐being. Qualitative data are complementary to quantitative and spatial assessments in the comprehensive representation of people's values pertaining to ecosystems, and this protocol may assist in incorporating values frequently overlooked in decision making processes.

Robo4 vaccines induce antibodies that retard tumor growth - Xiaodong Zhuang; Forhad Ahmed; Yang Zhang; Henry J. Ferguson; Jane C. Steele; Neil M. Steven; Zsuzsanna Nagy; Victoria L. Heath; Kai-Michael Toellner; Roy Bicknell (Angiogenesis, 2015)

To cope or to sustain? Eroding long-term sustainability in an Indonesian coral reef fishery - Sebastian C. A. Ferse; Marion Glaser; Muhammad Neil; Kathleen Schwerdtner Máñez (Regional Environmental Change, 2014)

Phenotypic characterization of the Miami World Collection of sugarcane (Saccharum spp.) and related grasses for selecting a representative core - James Todd; Jianping Wang; Barry Glaz; Sushma Sood; Tomas Ayala-Silva; Spurthi N. Nayak; Neil C. Glynn; Osman A. Gutierrez; David N. Kuhn; Mohammad Tahir; Jack C. Comstock (Genetic Resources and Crop Evolution, 2014)

Spatial variability and temporal trends in water‐use efficiency of European forests - Matthias Saurer; Renato Spahni; David C. Frank; Fortunat Joos; Markus Leuenberger; Neil J. Loader; Danny McCarroll; Mary Gagen; Ben Poulter; Rolf T.W. Siegwolf; Laia Andreu‐Hayles; Tatjana Boettger; et al. (Global Change Biology, 2014)
The increasing carbon dioxide (CO 2 ) concentration in the atmosphere in combination with climatic changes throughout the last century are likely to have had a profound effect on the physiology of trees: altering the carbon and water fluxes passing through the stomatal pores. However, the magnitude and spatial patterns of such changes in natural forests remain highly uncertain. Here, stable carbon isotope ratios from a network of 35 tree‐ring sites located across Europe are investigated to determine the intrinsic water‐use efficiency ( iWUE ), the ratio of photosynthesis to stomatal conductance from 1901 to 2000. The results were compared with simulations of a dynamic vegetation model (LPX‐Bern 1.0) that integrates numerous ecosystem and land–atmosphere exchange processes in a theoretical framework. The spatial pattern of tree‐ring derived iWUE of the investigated coniferous and deciduous species and the model results agreed significantly with a clear south‐to‐north gradient, as well as a general increase in iWUE over the 20th century. The magnitude of the iWUE increase was not spatially uniform, with the strongest increase observed and modelled for temperate forests in Central Europe, a region where summer soil‐water availability decreased over the last century. We were able to demonstrate that the combined effects of increasing CO 2 and climate change leading to soil drying have resulted in an accelerated increase in iWUE . These findings will help to reduce uncertainties in the land surface schemes of global climate models, where vegetation–climate feedbacks are currently still poorly constrained by observational data.

Influence of thigh activation on the $$\dot{V}$$ V ˙ O2 slow component in boys and men - Brynmor C. Breese; Alan R. Barker; Neil Armstrong; Jonathan Fulford; Craig A. Williams (European Journal of Applied Physiology, 2014)

Simulating Unstressed Crop Development and Growth Using the Unified Plant Growth Model (UPGM) - Gregory S. McMaster; James C. Ascough; Debora A. Edmunds; Larry E. Wagner; Fred A. Fox; Kendall C. DeJonge; Neil C. Hansen (Environmental Modeling & Assessment, 2014)

Geomorphology of the western Ionian Sea between Sicily and Calabria, Italy - Rajasmita Goswami; Neil C. Mitchell; Andrea Argnani; Simon H. Brocklehurst (Geo-Marine Letters, 2014)

Interrelationships of the durophagous stingrays (Batoidea: Myliobatidae) - Neil C. Aschliman (Environmental Biology of Fishes, 2014)

Hibernation alters the diversity and composition of mucosa‐associated bacteria while enhancing antimicrobial defence in the gut of 13‐lined ground squirrels - Kimberly A. Dill‐McFarland; Katie L. Neil; Austin Zeng; Ryan J. Sprenger; Courtney C. Kurtz; Garret Suen; Hannah V. Carey (Molecular Ecology, 2014)
The gut microbiota plays important roles in animal nutrition and health. This relationship is particularly dynamic in hibernating mammals where fasting drives the gut community to rely on host‐derived nutrients instead of exogenous substrates. We used 16S rRNA pyrosequencing and caecal tissue protein analysis to investigate the effects of hibernation on the mucosa‐associated bacterial microbiota and host responses in 13‐lined ground squirrels. The mucosal microbiota was less diverse in winter hibernators than in actively feeding spring and summer squirrels. UniFrac analysis revealed distinct summer and late winter microbiota clusters, while spring and early winter clusters overlapped slightly, consistent with their transitional structures. Communities in all seasons were dominated by Firmicutes and Bacteroidetes, with lesser contributions from Proteobacteria, Verrucomicrobia, Tenericutes and Actinobacteria. Hibernators had lower relative abundances of Firmicutes, which include genera that prefer plant polysaccharides, and higher abundances of Bacteroidetes and Verrucomicrobia, some of which can survive solely on host‐derived mucins. A core mucosal assemblage of nine operational taxonomic units shared among all individuals was identified with an average total sequence abundance of 60.2%. This core community, together with moderate shifts in specific taxa, indicates that the mucosal microbiota remains relatively stable over the annual cycle yet responds to substrate changes while potentially serving as a pool for ‘seeding’ the microbiota once exogenous substrates return in spring. Relative to summer, hibernation reduced caecal crypt length and increased MUC2 expression in early winter and spring. Hibernation also decreased caecal TLR4 and increased TLR5 expression, suggesting a protective response that minimizes inflammation.

Convergent Surface Water Distributions in U.S. Cities - M. K. Steele; J. B. Heffernan; N. Bettez; J. Cavender-Bares; P. M. Groffman; J. M. Grove; S. Hall; S. E. Hobbie; K. Larson; J. L. Morse; C. Neill; K. C. Nelson; et al. (Ecosystems, 2014)

Asthma exacerbation is associated with particulate matter source factors in children in New York City - Annette C. Rohr; Rima Habre; James Godbold; Erin Moshier; Neil Schachter; Meyer Kattan; Avi Grunin; Amit Nath; Brent Coull; Petros Koutrakis (Air Quality, Atmosphere & Health, 2014)

Gene expression in closely related species mirrors local adaptation: consequences for responses to a warming world - Shawn T. O'Neil; Jason D. K. Dzurisin; Caroline M. Williams; Neil F. Lobo; Jessica K. Higgins; Jillian M. Deines; Rory D. Carmichael; Erliang Zeng; John C. Tan; Grace C. Wu; Scott J. Emrich; Jessica J. Hellmann (Molecular Ecology, 2014)
Local adaptation of populations could preclude or slow range expansions in response to changing climate, particularly when dispersal is limited. To investigate the differential responses of populations to changing climatic conditions, we exposed poleward peripheral and central populations of two L epidoptera to reciprocal, common‐garden climatic conditions and compared their whole‐transcriptome expression. We found evidence of simple population differentiation in both species, and in the species with previously identified population structure and phenotypic local adaptation, we found several hundred genes that responded in a synchronized and localized fashion. These genes were primarily involved in energy metabolism and oxidative stress, and expression levels were most divergent between populations in the same environment in which we previously detected divergence for metabolism. We found no localized genes in the species with less population structure and for which no local adaptation was previously detected. These results challenge the assumption that species are functionally similar across their ranges and poleward peripheral populations are preadapted to warmer conditions. Rather, some taxa deserve population‐level consideration when predicting the effects of climate change because they respond in genetically based, distinctive ways to changing conditions.

Chicks of the Great Spotted Cuckoo May Turn Brood Parasitism into Mutualism by Producing a Foul-Smelling Secretion that Repels Predators - Gregory Röder; Daniela Canestrari; Diana Bolopo; José M. Marcos; Neil Villard; Vittorio Baglione; Ted C. J. Turlings (Journal of Chemical Ecology, 2014)

Phytochemicals as anticancer and chemopreventive topoisomerase II poisons - Adam C. Ketron; Neil Osheroff (Phytochemistry Reviews, 2014)

Evaluating Cenozoic equatorial sediment deposition anomalies for potential paleoceanographic and Pacific plate motion applications - Neil C. Mitchell; Nathalie Dubois (Marine Geophysical Research, 2014)

Metal distribution and spectroscopic analysis after soil washing with chelating agents and humic substances - Daniel C. W. Tsang; Neil R. Hartley (Environmental Science and Pollution Research, 2014)

Erratum to: Genetic Diversity of a Global Population of Colletotrichum Coccodes Using Amplified Fragment Length Polymorphism Markers - Kholoud M. Alananbeh; Leah Tsror Lahkim; Neil C. Gudmestad (American Journal of Potato Research, 2014)

Genetic Diversity of a Global Population of Colletotrichum Coccodes Using Amplified Fragment Length Polymorphism Markers - Kholoud M. Alananbeh; Lee Tsror Lahkim; Neil C. Gudmestad (American Journal of Potato Research, 2014)

Winter cereal root growth and aboveground–belowground biomass ratios as affected by site and tillage system in dryland Mediterranean conditions - Daniel Plaza-Bonilla; Jorge Álvaro-Fuentes; Neil C. Hansen; Jorge Lampurlanés; Carlos Cantero-Martínez (Plant and Soil, 2014)

The distribution of four Caragana species is related to their differential responses to drought stress - Xiang-Wen Fang; Neil C. Turner; Jairo A. Palta; Ming-Xi Yu; Tian-Peng Gao; Feng-Min Li (Plant Ecology, 2014)

Mangrove expansion and salt marsh decline at mangrove poleward limits - Neil Saintilan; Nicholas C. Wilson; Kerrylee Rogers; Anusha Rajkaran; Ken W. Krauss (Global Change Biology, 2014)
Mangroves are species of halophytic intertidal trees and shrubs derived from tropical genera and are likely delimited in latitudinal range by varying sensitivity to cold. There is now sufficient evidence that mangrove species have proliferated at or near their poleward limits on at least five continents over the past half century, at the expense of salt marsh. Avicennia is the most cold‐tolerant genus worldwide, and is the subject of most of the observed changes. Avicennia germinans has extended in range along the USA Atlantic coast and expanded into salt marsh as a consequence of lower frost frequency and intensity in the southern USA . The genus has also expanded into salt marsh at its southern limit in Peru, and on the Pacific coast of Mexico. Mangroves of several species have expanded in extent and replaced salt marsh where protected within mangrove reserves in Guangdong Province, China. In south‐eastern Australia, the expansion of A vicennia marina into salt marshes is now well documented, and R hizophora stylosa has extended its range southward, while showing strong population growth within estuaries along its southern limits in northern New South Wales. Avicennia marina has extended its range southwards in South Africa. The changes are consistent with the poleward extension of temperature thresholds coincident with sea‐level rise, although the specific mechanism of range extension might be complicated by limitations on dispersal or other factors. The shift from salt marsh to mangrove dominance on subtropical and temperate shorelines has important implications for ecological structure, function, and global change adaptation.

Volatile halocarbon emissions by three tropical brown seaweeds under different irradiances - Fiona Seh-Lin Keng; Siew-Moi Phang; Noorsaadah Abd Rahman; Emma C. Leedham; Claire Hughes; Andrew D. Robinson; Neil R. P. Harris; John A. Pyle; William T. Sturges (Journal of Applied Phycology, 2013)

Cloud bands over southern Africa: seasonality, contribution to rainfall variability and modulation by the MJO - Neil C. G. Hart; Chris J. C. Reason; Nicolas Fauchereau (Climate Dynamics, 2013)

A new quantitative real-time PCR assay for Rhizoctonia solani AG3-PT and the detection of AGs of Rhizoctonia solani associated with potato in soil and tuber samples in Great Britain - James W. Woodhall; Ian P. Adams; Jeff C. Peters; Glyn Harper; Neil Boonham (European Journal of Plant Pathology, 2013)

Erratum to: Development of a PCR Assay for the Rapid Detection and Differentiation of ‘Candidatus Liberibacter solanacearum’ Haplotypes and Their Spatiotemporal Distribution in the United States - Aimin Wen; Chris Johnson; Neil C. Gudmestad (American Journal of Potato Research, 2013)

Development of a PCR Assay for the Rapid Detection and Differentiation of ‘Candidatus Liberibacter solanacearum’ Haplotypes and Their Spatiotemporal Distribution in the United States - Aimin Wen; Chris Johnson; Neil C. Gudmestad (American Journal of Potato Research, 2013)

Salinity tolerance and ion accumulation in chickpea (Cicer arietinum L.) subjected to salt stress - Neil C. Turner; Timothy D. Colmer; John Quealy; R. Pushpavalli; L. Krishnamurthy; Jagmeet Kaur; Guriqbal Singh; Kadambot H. M. Siddique; Vincent Vadez (Plant and Soil, 2013)

Mammary gland development is delayed in mice deficient for aminopeptidase N - Andreas F. Kolb; David Sorrell; Caroline Lassnig; Simon Lillico; Ailsa Carlisle; Claire Neil; Claire Robinson; Mathias Müller; C. Bruce A. Whitelaw (Transgenic Research, 2013)

Ecological impacts of an invasive predator explained and predicted by comparative functional responses - Jaimie T. A. Dick; Kevin Gallagher; Suncica Avlijas; Hazel C. Clarke; Susan E. Lewis; Sally Leung; Dan Minchin; Joe Caffrey; Mhairi E. Alexander; Cathy Maguire; Chris Harrod; Neil Reid; et al. (Biological Invasions, 2013)

Complete nucleotide sequence of rose yellow vein virus, a member of the family Caulimoviridae having a novel genome organization - Dimitre Mollov; Ben Lockhart; David C. Zlesak; Neil Olszewski (Archives of Virology, 2013)

Quantification of Field Resistance to Verticillium dahliae in Eight Russet-Skinned Potato Cultivars Using Real-Time PCR - J. S. Pasche; A. L. Thompson; Neil C. Gudmestad (American Journal of Potato Research, 2013)

Polymerisation of a T Cell Epitope with an Immunostimulatory C3d Peptide Sequence Enhances Antigen Specific T Cell Responses - Neil M. O’Brien-Simpson; Troy J. Attard; Baihui Zheng; Katrina A. Walsh; Eric C. Reynolds (International Journal of Peptide Research and Therapeutics, 2013)

Partial heat acclimation of athletes with spinal cord lesion - Paul C. Castle; B. Pasan Kularatne; John Brewer; Alexis R. Mauger; Ross A. Austen; James A. Tuttle; Nick Sculthorpe; Richard W. Mackenzie; Neil S. Maxwell; Anthony D. J. Webborn (European Journal of Applied Physiology, 2013)

Sensitivity of coral calcification to ocean acidification: a meta‐analysis - Neil C. S. Chan; Sean R. Connolly (Global Change Biology, 2013)
To date, meta‐analyses of effects of acidification have focused on the overall strength of evidence for statistically significant responses; however, to anticipate likely consequences of ocean acidification, quantitative estimates of the magnitude of likely responses are also needed. Herein, we use random effects meta‐analysis to produce a systematically integrated measure of the distribution of magnitudes of the response of coral calcification to decreasing Ω Arag . We also tested whether methodological and biological factors that have been hypothesized to drive variation in response magnitude explain a significant proportion of the among‐study variation. We found that the overall mean response of coral calcification is ~15% per unit decrease in Ω Arag over the range 2 Arag Arag ). Neither differences in carbonate chemistry manipulation method, study duration, irradiance level, nor study species growth rate explained a significant proportion of the among‐study variation. However, studies employing buoyant weighting found significantly smaller decreases in calcification per unit Ω Arag (~10%), compared with studies using the alkalinity anomaly technique (~25%). These differences may be due to the greater tendency for the former to integrate over light and dark calcification. If the existing body of experimental work is indeed representative of likely responses of corals in nature, our results imply that, under business as usual conditions, declines in coral calcification by end‐of‐century will be ~22%, on average, or ~15% if only studies integrating light and dark calcification are considered. These values are near the low end of published projections, but support the emerging view that variability due to local environmental conditions and species composition is likely to be substantial.

A Reformulated Spherule-Derived Coccidioidin (Spherusol) to Detect Delayed-Type Hypersensitivity in Coccidioidomycosis - Royce Johnson; Steven M. Kernerman; Bradley G. Sawtelle; Suresh C. Rastogi; H. Stewart Nielsen; Neil M. Ampel (Mycopathologia, 2012)

Cone morphologies associated with shallow marine eruptions: east Pico Island, Azores - Neil C. Mitchell; Rachelle Stretch; Clive Oppenheimer; Daniel Kay; Christoph Beier (Bulletin of Volcanology, 2012)

Climate Change and Population Growth in Timor Leste: Implications for Food Security - Nicholas Molyneux; Gil Rangel da Cruz; Robert L. Williams; Rebecca Andersen; Neil C. Turner (Ambio, 2012)

A new large scale soil DNA extraction procedure and real-time PCR assay for the detection of Sclerotium cepivorum in soil - James W. Woodhall; Kathryn M. Webb; Patricia M. Giltrap; Ian P. Adams; Jeff C. Peters; Giles E. Budge; Neil Boonham (European Journal of Plant Pathology, 2012)

Clusters of genes encoding fructan biosynthesizing enzymes in wheat and barley - Bao-Lam Huynh; Diane E. Mather; Andreas W. Schreiber; John Toubia; Ute Baumann; Zahra Shoaei; Nils Stein; Ruvini Ariyadasa; James C. R. Stangoulis; James Edwards; Neil Shirley; Peter Langridge; et al. (Plant Molecular Biology, 2012)

Reproductive development, GnRHa-induced spawning and egg quality of wild meagre (Argyrosomus regius) acclimatised to captivity - Neil Duncan; Alicia Estévez; Javier Porta; Ignacio Carazo; Fernando Norambuena; Cristobal Aguilera; Ignaci Gairin; Francesco Bucci; Roser Valles; Constantinos C. Mylonas (Fish Physiology and Biochemistry, 2012)

The carbon footprint of maize production as affected by nitrogen fertilizer and maize-legume rotations - B. L. Ma; B. C. Liang; Dilip K. Biswas; Malcolm J. Morrison; Neil B. McLaughlin (Nutrient Cycling in Agroecosystems, 2012)

The effects of restoring a conifer Plantation on an Ancient Woodland Site (PAWS) in the UK on the habitat and local population of the Hazel Dormouse (Muscardinus avellanarius) - R. C. Trout; S. E. Brooks; P. Rudlin; J. Neil (European Journal of Wildlife Research, 2012)

Changes in atmospheric circulation and the Arctic Oscillation preserved within a millennial length reconstruction of summer cloud cover from northern Fennoscandia - Giles H. F. Young; Danny McCarroll; Neil J. Loader; Mary H. Gagen; Andreas J. Kirchhefer; Joanne C. Demmler (Climate Dynamics, 2012)

Towards an integrated global framework to assess the impacts of land use and management change on soil carbon: current capability and future vision - Pete Smith; Christian A. Davies; Stephen Ogle; Giuliana Zanchi; Jessica Bellarby; Neil Bird; Robert M. Boddey; Niall P. McNamara; David Powlson; Annette Cowie; Meine van Noordwijk; Sarah C. Davis; et al. (Global Change Biology, 2012)
I ntergovernmental P anel on C limate C hange ( IPCC ) T ier 1 methodologies commonly underpin project‐scale carbon accounting for changes in land use and management and are used in frameworks for L ife C ycle A ssessment and carbon footprinting of food and energy crops. These methodologies were intended for use at large spatial scales. This can introduce error in predictions at finer spatial scales. There is an urgent need for development and implementation of higher tier methodologies that can be applied at fine spatial scales (e.g. farm/project/plantation) for food and bioenergy crop greenhouse gas (GHG) accounting to facilitate decision making in the land‐based sectors. Higher tier methods have been defined by IPCC and must be well evaluated and operate across a range of domains (e.g. climate region, soil type, crop type, topography), and must account for land use transitions and management changes being implemented. Furthermore, the data required to calibrate and drive the models used at higher tiers need to be available and applicable at fine spatial resolution, covering the meteorological, soil, cropping system and management domains, with quantified uncertainties. Testing the reliability of the models will require data either from sites with repeated measurements or from chronosequences. We review current global capability for estimating changes in soil carbon at fine spatial scales and present a vision for a framework capable of quantifying land use change and management impacts on soil carbon, which could be used for addressing issues such as bioenergy and biofuel sustainability, food security, forest protection, and direct/indirect impacts of land use change. The aim of this framework is to provide a globally accepted standard of carbon measurement and modelling appropriate for GHG accounting that could be applied at project to national scales (allowing outputs to be scaled up to a country level), to address the impacts of land use and land management change on soil carbon.

Sources of groundwater pumpage in a layered aquifer system in the Upper Gulf Coastal Plain, USA - Yun Huang; Bridget R. Scanlon; Jean-Philippe Nicot; Robert C. Reedy; Alan R. Dutton; Van A. Kelley; Neil E. Deeds (Hydrogeology Journal, 2012)

Detection and Differentiation of Potato Virus Y Strains from Potato Using Immunocapture Multiplex RT-PCR - Ipsita Mallik; Nolan R. Anderson; Neil C. Gudmestad (American Journal of Potato Research, 2012)

Control of foliar diseases in barley: towards an integrated approach - Dale R. Walters; Anna Avrova; Ian J. Bingham; Fiona J. Burnett; James Fountaine; Neil D. Havis; Stephen P. Hoad; Gareth Hughes; Mark Looseley; Simon J. P. Oxley; Alan Renwick; Cairistiona F. E. Topp; et al. (European Journal of Plant Pathology, 2012)

A Classification of Floodplains and Wetlands of the Murray-Darling Basin Based on Changes in Flows Following Water Resource Development - Neil C. Sims; Anthony A. Chariton; Huidong Jin; Matthew J. Colloff (Wetlands, 2012)

Effect of daily mixed nutritional supplementation on immune indices in soldiers undertaking an 8-week arduous training programme - Bethany C. Diment; Matthew B. Fortes; Julie P. Greeves; Anna Casey; Ricardo J. S. Costa; Robert Walters; Neil P. Walsh (European Journal of Applied Physiology, 2012)

Is There a Role for Clinical Practice Guidelines in Multidisciplinary Tumor Board Meetings? A Descriptive Study of Knowledge Transfer Between Research and Practice - Xanthoula Kostaras; Melissa A. Shea-Budgell; Emily Malcolm; Jacob C. Easaw; Wilson Roa; Neil A. Hagen (Journal of Cancer Education, 2012)

Assessing landslide movements in volcanic islands using near-shore marine geophysical data: south Pico island, Azores - Neil C. Mitchell; Rui Quartau; José Madeira (Bulletin of Volcanology, 2012)

Genetic diversity of ‘Cadidatus Liberibacter solanacearum’ strains in the United States and Mexico revealed by simple sequence repeat markers - Hong Lin; Md Sajedul Islam; Yang Bai; Amin Wen; Suque Lan; Neil C. Gudmestad; Edwin L. Civerolo (European Journal of Plant Pathology, 2012)

Quantitative and semiquantitative immunoassay of growth factors and cytokines in the conditioned medium of STO and CF-1 mouse feeder cells - Neil C. Talbot; Wendy O. Sparks; Anne M. Powell; Stanislaw Kahl; Thomas J. Caperna (In Vitro Cellular & Developmental Biology - Animal, 2012)

Deception of ambient and body core temperature improves self paced cycling in hot, humid conditions - Paul C. Castle; Neil Maxwell; Alan Allchorn; Alexis R. Mauger; Danny K. White (European Journal of Applied Physiology, 2012)

A specialist root herbivore exploits defensive metabolites to locate nutritious tissues - Christelle A. M. Robert; Nathalie Veyrat; Gaétan Glauser; Guillaume Marti; Gwladys R. Doyen; Neil Villard; Mickaël D. P. Gaillard; Tobias G. Köllner; David Giron; Mélanie Body; Benjamin A. Babst; Richard A. Ferrieri; et al. (Ecology Letters, 2012)
Ecology Letters (2011) 14 : 55–64 Abstract The most valuable organs of plants are often particularly rich in essential elements, but also very well defended. This creates a dilemma for herbivores that need to maximise energy intake while minimising intoxication. We investigated how the specialist root herbivore Diabrotica virgifera solves this conundrum when feeding on wild and cultivated maize plants. We found that crown roots of maize seedlings were vital for plant development and, in accordance, were rich in nutritious primary metabolites and contained higher amounts of the insecticidal 2,4‐dihydroxy‐7‐methoxy‐1,4‐benzoxazin‐3‐one (DIMBOA) and the phenolic compound chlorogenic acid. The generalist herbivores Diabrotica balteata and Spodoptera littoralis were deterred from feeding on crown roots, whereas the specialist D. virgifera preferred and grew best on these tissues. Using a 1,4‐benzoxazin‐3‐one‐deficient maize mutant, we found that D. virgifera is resistant to DIMBOA and other 1,4‐benzoxazin‐3‐ones and that it even hijacks these compounds to optimally forage for nutritious roots.

Does low-intensity surface fire increase water- and nutrient-availability to overstorey Eucalyptus gomphocephala? - Dugald C. Close; Neil J. Davidson; Perry W. Swanborough; Ross Corkrey (Plant and Soil, 2011)

Consequences of transforming narrow leafed lupin (Lupinus angustifolius [L.]) with an ipt gene under control of a flower-specific promoter - Craig A. Atkins; R. J. Neil Emery; Penelope M. C. Smith (Transgenic Research, 2011)

Agricultural ecosystem management in dry areas: challenges and solutions - Neil C. Turner; Feng-Min Li; You-Cai Xiong; Kadambot H. M. Siddique (Plant and Soil, 2011)

Spatial patterns of mercury in biota of Adirondack, New York lakes - Xue Yu; Charles T. Driscoll; Mario Montesdeoca; David Evers; Melissa Duron; Kate Williams; Nina Schoch; Neil C. Kamman (Ecotoxicology, 2011)

Genetic variation in Delonix s.l. (Leguminosae) in Madagascar revealed by AFLPs: fragmentation, conservation status and taxonomy - Malin C. Rivers; Neil A. Brummitt; Eimear Nic Lughadha; Thomas R. Meagher (Conservation Genetics, 2011)

The RNA chaperone, Hfq, controls two luxR ‐type regulators and plays a key role in pathogenesis and production of antibiotics in Serratia sp. ATCC 39006 - Nabil M. Wilf; Neil R. Williamson; Joshua P. Ramsay; Simon Poulter; Kasia J. Bandyra; George P. C. Salmond (Environmental Microbiology, 2011)
Summary Serratia sp. ATCC 39006 (S39006) is a Gram‐negative bacterium that is virulent in plant (potato) and animal ( Caenorhabditis elegans ) models. It produces two secondary metabolite antibiotics, a prodigiosin and a carbapenem, and the exoenzymes, pectate lyase and cellulase. A complex regulatory network that includes quorum sensing (QS) controls production of prodigiosin. While many aspects of the regulation of the metabolites and exoenzymes are well understood, the potential role in this network of the RNA chaperone Hfq and dependent small regulatory RNAs has not been characterized. Hfq is an RNA chaperone involved in post‐transcriptional regulation that plays a key role in stress response and virulence in diverse bacterial species. To explore whether Hfq‐dependent processes might contribute to the regulation of antibiotic production we constructed an S39006 Δ hfq mutant. Production of prodigiosin and carbapenem was abolished in this mutant strain, while production of the QS signalling molecule, butanoyl homoserine lactone (BHL), was unaffected. Using transcriptional fusions, we found that Hfq regulates the QS response regulators, SmaR and CarR. Additionally, exoenzyme production and swimming motility were decreased in a Δ hfq mutant, and virulence was attenuated in potato and C. elegans models. These results suggest that an Hfq‐dependent pathway is involved in the regulation of virulence and secondary metabolite production in S39006.

Neurometabolite Abnormalities in Simian Immunodeficiency Virus-Infected Macaques with Chronic Morphine Administration - Christine C. Cloak; Linda Chang; Shawn P. O’Neil; Thomas M. Ernst; Daniel C. Anderson; Robert M. Donahoe (Journal of Neuroimmune Pharmacology, 2011)

The effect of a carbohydrate beverage on the physiological responses during prolonged load carriage - Sam D. Blacker; Neil C. Williams; Joanne L. Fallowfield; Mark E. T. Willems (European Journal of Applied Physiology, 2011)

Do birds of a feather move together? Group membership and behavioral synchrony - Lynden K. Miles; Joanne Lumsden; Michael J. Richardson; C. Neil Macrae (Experimental Brain Research, 2011)

Characterization of Mitral Valve Annular Dynamics in the Beating Heart - Manuel K. Rausch; Wolfgang Bothe; John-Peder Escobar Kvitting; Julia C. Swanson; Neil B. Ingels; D. Craig Miller; Ellen Kuhl (Annals of Biomedical Engineering, 2011)

Culture of porcine hepatocytes or bile duct epithelial cells by inductive serum-free media - Thomas J. Caperna; Le Ann Blomberg; Wesley M. Garrett; Neil C. Talbot (In Vitro Cellular & Developmental Biology - Animal, 2011)

Acute tryptophan depletion attenuates conscious appraisal of social emotional signals in healthy female volunteers - Felix D. C. C. Beacher; Marcus A. Gray; Ludovico Minati; Richard Whale; Neil A. Harrison; Hugo D. Critchley (Psychopharmacology, 2011)

Drying the surface soil reduces the nitrogen content of faba bean (Vicia faba L.) through a reduction in nitrogen fixation - Magdi T. Abdelhamid; Jairo A. Palta; Erik J. Veneklaas; Craig Atkins; Neil C. Turner; Kadambot H. M. Siddique (Plant and Soil, 2011)

The impact of temperature variability on wheat yields - SENTHOLD ASSENG; IAN FOSTER; NEIL C. TURNER (Global Change Biology, 2011)
With current annual production at over 600 million tonnes, wheat is the third largest crop in the world behind corn and rice, and an essential source of carbohydrates for millions of people. While wheat is grown over a wide range of environments, it is common in the major wheat‐producing countries for grain filling to occur when soil moisture is declining and temperature is increasing. Average global temperatures have increased over the last decades and are predicted to continue rising, along with a greater frequency of extremely hot days. Such events have already been reported for major wheat growing regions in the world. However, the direct impact of past temperature variability and changes in averages and extremes on wheat production has not been quantified. Attributing changes in observed yields over recent decades to a single factor such as temperature is not possible due to the confounding effects of other factors. By using simulation modelling, we were able to separate the impact of temperature from other factors and show that the effect of temperature on wheat production has been underestimated. Surprisingly, observed variations in average growing‐season temperatures of ±2 °C in the main wheat growing regions of Australia can cause reductions in grain production of up to 50%. Most of this can be attributed to increased leaf senescence as a result of temperatures >34 °C. Temperature conditions during grain filling in the major wheat growing regions of the world are similar to the Australian conditions during grain filling. With average temperatures and the frequency of heat events projected to increase world‐wide with global warming, yield reductions due to higher temperatures during the important grain‐filling stage alone could substantially undermine future global food security. Adaptation strategies need to be considered now to prevent substantial yield losses in wheat from increasing future heat stress.

Prevalence of Mefenoxam Resistance Among Phytophthora erythroseptica Pethybridge Isolates in Minnesota and North Dakota - Chapara Venkataramana; Raymond J. Taylor; Julie S. Pasche; Neil. C. Gudmestad (American Journal of Potato Research, 2010)

Phylogenetic relationships of sugarcane rust fungi - Linley J. Dixon; Lisa A. Castlebury; M. Catherine Aime; Neil C. Glynn; Jack C. Comstock (Mycological Progress, 2010)

Feeder-independent continuous culture of the PICM-19 pig liver stem cell line - Neil C. Talbot; Le Ann Blomberg; Wesley M. Garrett; Thomas J. Caperna (In Vitro Cellular & Developmental Biology - Animal, 2010)

Establishment of native Eucalyptus pauciflora and exotic Eucalyptus nitens on former grazing land - Dugald C. Close; Neil J. Davidson; Keith C. Churchill; Ross Corkrey (New Forests, 2010)

Quorum sensing‐controlled Evr regulates a conserved cryptic pigment biosynthetic cluster and a novel phenomycin‐like locus in the plant pathogen, Pectobacterium carotovorum - Neil R. Williamson; Paul M. B. Commander; George P. C. Salmond (Environmental Microbiology, 2010)
Summary Pectobacterium carotovorum SCRI193 is a phytopathogenic Gram‐negative bacterium. In this study, we have identified a novel cryptic pigment biosynthetic locus in P. carotovorum SCRI193 which we have called the Pectobacterium orange pigment ( pop ) cluster. The pop cluster is flanked by two tRNA genes and contains genes that encode non‐ribosomal peptide synthases and polyketide synthase and produces a negatively charged polar orange pigment. Orange pigment production is activated when an adjacent transcriptional activator sharing sequence similarity with the Erwinia virulence regulator (Evr) is overexpressed. Evr was shown to positively activate its own transcription and that of the pigment biosynthetic genes and an unlinked locus encoding a phenomycin homologue. In addition, the expression of Evr and orange pigment production was shown to be regulated by N‐ (3‐oxohexanoyl)‐HSL (OHHL) quorum sensing and have a virulence phenotype in potato. Finally, by comparative genomics and Southern blotting we demonstrate that this pigment biosynthetic cluster is present in multiple P. carotovorum spp., Pectobacterium brasiliensis 1692 and a truncated version of the cluster is present in Pectobacterium atrosepticum . The conserved nature of this cluster in P. carotovorum and P. brasiliensis suggests that the pop cluster has an important function in these broad‐host‐range soft rotting bacteria, which is no longer required in the narrow‐host‐range P. atrosepticum SCRI1043.

The effects of space flight and microgravity on the growth and differentiation of PICM-19 pig liver stem cells - Neil C. Talbot; Thomas J. Caperna; LeAnn Blomberg; Paul G. Graninger; Louis S. Stodieck (In Vitro Cellular & Developmental Biology - Animal, 2010)

Subpopulations, locations and fragmentation: applying IUCN red list criteria to herbarium specimen data - Malin C. Rivers; Steven P. Bachman; Thomas R. Meagher; Eimear Nic Lughadha; Neil A. Brummitt (Biodiversity and Conservation, 2010)

Genome-wide analysis of the chalcone synthase superfamily genes of Physcomitrella patens - P. K. Harshavardhan Koduri; Graeme S. Gordon; Elizabeth I. Barker; Che C. Colpitts; Neil W. Ashton; Dae-Yeon Suh (Plant Molecular Biology, 2010)

Cytochrome P450 expression profile of the PICM-19H pig liver cell line: potential application to rapid liver toxicity assays - Ryan R. Willard; Nancy W. Shappell; John H. Meekin; Neil C. Talbot; Thomas J. Caperna (In Vitro Cellular & Developmental Biology - Animal, 2010)

High-resolution array comparative genomic hybridization analysis reveals unanticipated complexity of genetic deficiencies on chromosome V in Caenorhabditis elegans - Martin R. Jones; Shu Yi Chua; Nigel J. O’Neil; Robert C. Johnsen; Ann M. Rose; David L. Baillie (Molecular Genetics and Genomics, 2009)

Effects of vegetation map change in MM5 simulations of southern Africa's summer climate - Neil C. MacKellar; Mark A. Tadross; Bruce C. Hewitson (International Journal of Climatology, 2009)
A regional climate model is used to assess potential climatic impacts of altering the vegetation map of southern Africa from an estimated natural state to present‐day conditions. The Pennsylvania State University‐National Center for Atmospheric Research Mesoscale Model (MM5) is integrated from 1 August to 28 February for 1988/1989, 1991/1992 and 1995/1996 for two spatial vegetation representations: (1) potential natural vegetation as predicted by the Sheffield Dynamic Global Vegetation Model, and (2) current conditions given by the United States Geological Survey land‐surface classification. Significant impacts on mean September–November (SON) and December–February (DJF) surface climate arise from the change in vegetation, the most notable of which is cooling over large parts of the continent in SON, which gives rise to increased large‐scale subsidence and decreased moisture convergence. Resultant decreases in rainfall causes a hydrological feedback through reduced latent heat flux which mitigates the initial cooling and weakens the positive geopotential height bias in DJF. The increase in geopotential height extends vertically up to 500 hPa, which potentially has important implications for regional moisture transport over southern Africa. Copyright © 2008 Royal Meteorological Society

An Oxidized Ergosterol from Pleurotus cystidiosus Active Against Anthracnose Causing Colletotrichum gloeosporioides - Inoka P. Menikpurage; D. T. U. Abeytunga; Neil E. Jacobsen; R. L. C. Wijesundara (Mycopathologia, 2009)

Identification and Suppression of β-Elimination Byproducts Arising from the Use of Fmoc-Ser(PO3Bzl,H)-OH in Peptide Synthesis - Troy J. Attard; Neil M. O’Brien-Simpson; Eric C. Reynolds (International Journal of Peptide Research and Therapeutics, 2009)

Proteomic and phenotypic profiling of the amphibian pathogen Batrachochytrium dendrobatidis shows that genotype is linked to virulence - MATTHEW C. FISHER; JAIME BOSCH; ZHIKANG YIN; DAVID A. STEAD; JANET WALKER; LAURA SELWAY; ALISTAIR J. P. BROWN; LOUISE A. WALKER; NEIL A. R. GOW; JASON E. STAJICH; TRENTON W. J. GARNER (Molecular Ecology, 2009)
Population genetics of the amphibian pathogen Batrachochytrium dendrobatidis ( Bd ) show that isolates are highly related and globally homogenous, data that are consistent with the recent epidemic spread of a previously endemic organism. Highly related isolates are predicted to be functionally similar due to low levels of heritable genetic diversity. To test this hypothesis, we took a global panel of Bd isolates and measured (i) the genetic relatedness among isolates, (ii) proteomic profiles of isolates, (iii) the susceptibility of isolates to the antifungal drug caspofungin, (iv) the variation among isolates in growth and phenotypic characteristics, and (v) the virulence of isolates against the European common toad Bufo bufo . Our results show (i) genotypic differentiation among isolates, (ii) proteomic differentiation among isolates, (iii) no significant differences in susceptibility to caspofungin, (iv) differentiation in growth and phenotypic/morphological characters, and (v) differential virulence in B. bufo . Specifically, our data show that Bd isolates can be profiled by their genotypic and proteomic characteristics, as well as by the size of their sporangia. Bd genotypic and phenotypic distance matrices are significantly correlated, showing that less‐related isolates are more biologically unique. Mass spectrometry has identified a set of candidate genes associated with inter‐isolate variation. Our data show that, despite its rapid global emergence, Bd isolates are not identical and differ in several important characters that are linked to virulence. We argue that future studies need to clarify the mechanism(s) and rate at which Bd is evolving, and the impact that such variation has on the host–pathogen dynamic.

Genome-wide distribution of ancestry in Mexican Americans - Analabha Basu; Hua Tang; Xiaofeng Zhu; C. Charles Gu; Craig Hanis; Eric Boerwinkle; Neil Risch (Human Genetics, 2008)

Effects of nicotine on sensorimotor gating impairment induced by long-term treatment with neurotoxic NMDA antagonism - Bruce A. Rasmussen; David C. Perry; Jahn O’Neil; Kebreten F. Manaye; Yousef Tizabi (Neurotoxicity Research, 2008)

A landscape theory for food web architecture - Neil Rooney; Kevin S. McCann; John C. Moore (Ecology Letters, 2008)
Ecologists have long searched for structures and processes that impart stability in nature. In particular, food web ecology has held promise in tackling this issue. Empirical patterns in food webs have consistently shown that the distributions of species and interactions in nature are more likely to be stable than randomly constructed systems with the same number of species and interactions. Food web ecology still faces two fundamental challenges, however. First, the quantity and quality of food web data required to document both the species richness and the interaction strengths among all species within food webs is largely prohibitive. Second, where food webs have been well documented, spatial and temporal variation in food web structure has been ignored. Conversely, research that has addressed spatial and temporal variation in ecosystems has generally ignored the full complexity of food web architecture. Here, we incorporate empirical patterns, largely from macroecology and behavioural ecology, into a spatially implicit food web structure to construct a simple landscape theory of food web architecture. Such an approach both captures important architectural features of food webs and allows for an exploration of food web structure across a range of spatial scales. Finally, we demonstrated that food webs are hierarchically organized along the spatial and temporal niche axes of species and their utilization of food resources in ways that stabilize ecosystems.

The Pea Nodulation Mutant R50 (sym16) Displays Altered Activity and Expression Profiles for Cytokinin Dehydrogenase - Mark Held; Alicia N. Pepper; Johny Bozdarov; Matthew D. Smith; R. J. Neil Emery; Frédérique C. Guinel (Journal of Plant Growth Regulation, 2008)

NADPH oxidase involvement in cellular integrity - Neil Macpherson; Seiji Takeda; Zhonglin Shang; Adeeba Dark; Jennifer C. Mortimer; Colin Brownlee; Liam Dolan; Julia M. Davies (Planta, 2008)

A sedimentary record of the rise and fall of the metal industry in Bergslagen, south central Sweden - Dan Hammarlund; Anson W. Mackay; David M. J. Fallon; Gemma Pateman; Luisa C. Tavio; Melanie J. Leng; Neil L. Rose (Journal of Paleolimnology, 2008)

Integrated regulation involving quorum sensing, a two‐component system, a GGDEF/EAL domain protein and a post‐transcriptional regulator controls swarming and RhlA‐dependent surfactant biosynthesis in Serratia - Neil R. Williamson; Peter C. Fineran; Wakano Ogawa; Louise R. Woodley; George P. C. Salmond (Environmental Microbiology, 2008)
Summary Serratia sp. ATCC 39006 ( Serratia 39006) is a Gram‐negative bacterium which produces the secondary metabolite antibiotics, prodigiosin and 1‐carbapen‐2‐em‐3‐carboxylic acid and secretes plant cell wall degrading enzymes. In this study we have identified mutations in the genes, pigX , rap and rsmA , which caused increased production of a previously unidentified surfactant and flagella‐dependent swarming phenotype in Serratia 39006. Analysis of both the biosynthesis and regulation of surfactant production and swarming, revealed FlhC, quorum sensing, a GGDEF/EAL domain protein (PigX), a GacAS two‐component system, an Rsm system and Rap as key regulators. In addition, surfactant biosynthesis required a protein similar to RhlA, involved in rhamnolipid synthesis in Pseudomonas aeruginosa . Homologues of RhlA have not previously been identified in members of the Enterobacteriaceae . Furthermore, we provide evidence that the surfactant may be responsible for dispersal of the antimicrobial pigment, prodigiosin. This study demonstrates the complex regulatory inputs into the coordinated multicellular swarming phenotype in Serratia .

Identification of elderly fallers by muscle strength measures - Mirjam Pijnappels; (Petra) J. C. E. van der Burg; Neil D. Reeves; Jaap H. van Dieën (European Journal of Applied Physiology, 2008)

NE-11 represents a new strain variant class of Potato virus Y - Jim Lorenzen; Phil Nolte; Darren Martin; Julie S. Pasche; Neil C. Gudmestad (Archives of Virology, 2008)

Global diversity of crabs (Crustacea: Decapoda: Brachyura) in freshwater - Darren C. J. Yeo; Peter K. L. Ng; Neil Cumberlidge; Célio Magalhães; Savel R. Daniels; Martha R. Campos (Hydrobiologia, 2008)

Using the aquatic macrophyte Vallisneria americana (wild celery) as a nutrient bioindicator - Emily R. Benson; Judith M. O’Neil; William C. Dennison (Hydrobiologia, 2008)

Synthesis of Phosphopeptides in the Fmoc Mode - Troy J. Attard; Neil O’Brien-Simpson; Eric C. Reynolds (International Journal of Peptide Research and Therapeutics, 2007)

The Role of Multiphosphorylated Peptides in Mineralized Tissue Regeneration - Keith J. Cross; N. Laila Huq; Neil M. O’Brien-Simpson; John W. Perich; Troy J. Attard; Eric C. Reynolds (International Journal of Peptide Research and Therapeutics, 2007)

Synthesis and Characterisation of a Multiphosphorylated Phosphophoryn Repeat Motif; H-[Asp-(Ser(P))2]3-Asp-OH - Neil M. O’Brien-Simpson; Troy J. Attard; Ashwini Loganathan; N. Laila Huq; Keith J. Cross; Peter F. Riley; Eric C. Reynolds (International Journal of Peptide Research and Therapeutics, 2007)

Dakota crisp: A new high-yielding, cold-chipping potato cultivar with tablestock potential - Asunta L. Thompson; Bryce L. Farnsworth; Gary A. Secor; Neil C. Gudmestad; Duane Preston; Joseph R. Sowokinos; Marty Glynn; Harlene Hatterman-Valenti (American Journal of Potato Research, 2007)

Modelling adaptive management strategies for coping with the impacts of climate variability and change on riverine algal blooms - NEIL R. VINEY; BRYSON C. BATES; STEPHEN P. CHARLES; IAN T. WEBSTER; MYRIAM BORMANS (Global Change Biology, 2007)
The impact of climate change on hydrology and water resources is one of the most critical issues facing the world in the next few decades. In particular, there is a need to quantify the risks associated with maintaining the security of resource quantity and quality, and to assess the effectiveness of potential management strategies. In this paper, we assess the impacts of climate variability and change on one aspect of river health. A simple model of Anabaena algal bloom occurrence at a weir pool in the lower Murrumbidgee River, Australia, has been coupled to a catchment model that is used to simulate streamflow, irrigation demand and diversions, dam water storage and releases, and decision‐making by both irrigators and managers. Long‐term climate data are obtained from a statistical downscaling algorithm, which, when applied to global climate model predictions can provide climate data suitable for driving the coupled model under a variety of climatic scenarios. The coupled model is then used to assess the impact of climate variability and projected climate change on the frequency, duration and magnitude of Anabaena blooms. The impact of two management strategies for bloom control are also assessed and it is shown that even a single, quite simple, resource‐neutral, adaptive management strategy has the potential to substantially reduce the occurrence and impact of algal blooms and to more than compensate for the deleterious impacts of climate change. This result supports the notion that planning for the future can lead to positive outcomes in the present.

Phylogeography of the New Zealand blue duck (Hymenolaimus malacorhynchos): implications for translocation and species recovery - Bruce C. Robertson; Tammy E. Steeves; Katherine P. McBride; Sharyn J. Goldstien; Murray Williams; Neil J. Gemmell (Conservation Genetics, 2007)

Interactions between iron-deficiency chlorosis and soybean cyst nematode in Minnesota soybean fields - Senyu Chen; James E. Kurle; Salliana R. Stetina; Daniel R. Miller; Lee D. Klossner; George A. Nelson; Neil C. Hansen (Plant and Soil, 2007)

RL-SAGE and microarray analysis of the rice transcriptome after Rhizoctonia solani infection - R. C. Venu; Yulin Jia; Malali Gowda; Melissa H. Jia; Chatchawan Jantasuriyarat; Eric Stahlberg; Huameng Li; Andrew Rhineheart; Prashanth Boddhireddy; Pratibha Singh; Neil Rutger; David Kudrna; et al. (Molecular Genetics and Genomics, 2007)

Transgenic embryos and mice produced from low titre lentiviral vectors - William A. Ritchie; Clare Neil; Tim King; C. Bruce A. Whitelaw (Transgenic Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Differential effects of the d- and l- isomers of amphetamine on pharmacological MRI BOLD contrast in the rat - Neil Easton; Fiona Marshall; Kevin C. F. Fone; Charles A. Marsden (Psychopharmacology, 2007)

Responses of estuarine intertidal microphytobenthic algal assemblages to enhanced ultraviolet B radiation - JEN WARING; NEIL R. BAKER; GRAHAM J. C. UNDERWOOD (Global Change Biology, 2007)
As a result of ozone depletion, ground doses of ultraviolet B (UVB) radiation in the mid latitudes of the Northern Hemisphere have increased since the 1980s, and current predictions indicate no possible alleviation until at least post 2020. Mudflats and sandflats are important coastal‐zone habitats, and support extensive biofilms of benthic microalgae (microphytobenthos). In intertidal situations, these assemblages are exposed to high levels of UVB radiation during periods of tidal exposure. Exposure of intertidal biofilms dominated by epipelic (mud‐inhabiting) diatoms to 0, 0.18 or 0.35 W m −2 UVB radiation for between 4 and 10 days resulted in no significant decreases in the maximum PSII quantum efficiency ( F v / F m ) throughout diel exposure periods. Although the quantum efficiency of electron transport ( F q ′/ F m ′) showed significant reductions early in some experiments, the major response was an increase in F q ′/ F m ′ in UVB exposed biofilms. This increase in F q ′/ F m ′ was suggestive of a protective vertical migration down into the sediment. Single‐cell and whole biofilm fluorescence imaging demonstrated, for the first time, that motile diatoms are able to detect UVB radiation independently of UVA or photosynthetically active radiation (PAR) and migrate rapidly down (within 15 min) into the sediments to avoid it. This behavioural acclimation mechanism appears to prevent significant accumulation of UVB induced damage to the algae. UVB exposure had no significant effect of biofilm photosynthesis (measured by 14 C carbon fixation), but did alter organic carbon allocation patterns, with significantly less new carbon allocated to intracellular storage (glucan) and extracellular colloidal carbohydrate fractions. Significant reductions in the sediment standing stocks of chlorophyll a (Chl a ), colloidal carbohydrates, extracellular polymeric substances (EPS) were seen after 7 days of UVB exposure. This study showed that marine intertidal benthic diatoms use a behavioural strategy to avoid exposure to UVB and that this response is effective as a short‐term protection mechanism against UVB damage. However, altered carbon allocation patterns feed forward over time into changes in biofilm biomass and sediment carbohydrate dynamics. This suggests that continual long‐term exposure to UVB may impact on sediment carbon cycling and trophic interactions and on the stabilization of sediments by microalgal biofilms through their production of extracellular carbohydrates.

Comparison between PIT and radio telemetry to evaluate winter habitat use and activity patterns of juvenile Atlantic salmon and brown trout - Eva C. Enders; Keith D. Clarke; Curtis J. Pennell; L. M. Neil Ollerhead; David A. Scruton (Hydrobiologia, 2007)

Relation between phylogenetic position, lipid metabolism and butyrate production by different Butyrivibrio-like bacteria from the rumen - Delphine Paillard; Nest McKain; Lal C. Chaudhary; Nicola D. Walker; Florian Pizette; Ingrid Koppova; Neil R. McEwan; Jan Kopečný; Philip E. Vercoe; Petra Louis; R. John Wallace (Antonie van Leeuwenhoek, 2007)

Idiopathic muscle necrosis in the Norway lobster, Nephrops norvegicus (L.): aetiology, pathology and progression to bacteraemia - I D Ridgway; G D Stentiford; A C Taylor; R J A Atkinson; T H Birkbeck; D M Neil (Journal of Fish Diseases, 2007)
The pathology and progression of idiopathic muscle necrosis (IMN) in Nephrops norvegicus and possible aetiologies have been investigated. Trawl capture, aerial exposure and handling initiate IMN, and the condition can be induced through periods of aerial exposure alone, in the absence of trawling. Within 24–48 h after trawl capture IMN progresses to a multi‐species bacterial septicaemia, with moribund animals exhibiting clinical signs. The aetiology of this condition has been examined using molecular (16S rRNA gene sequencing) and biochemical (standard taxonomic assays, Biolog TM ) criteria to characterize bacterial isolates from moribund and healthy animals. Histopathology of the IMN phase reveals a loss of sarcomeric structure with necrotic lesions containing pyknotic nuclei, fragments of myofibrils and connective tissue elements. In the bacterial phase there is extensive loss of abdominal muscle structure, and the presence of rod‐shaped Gram‐negative bacteria in the degrading tissues. The results demonstrate that the IMN condition is connected to stressful conditions imposed on N. norvegicus , but involves no pathogenic agents. This is followed by an opportunistic bacterial infection that causes further tissue spoilage. It is believed that the primary cause of both IMN and bacteraemia is imposed stress, but they are expressed in different time courses.

Establishment of a bovine blastocyst-derived cell line collection for the comparative analysis of embryos created in vivo and by in vitro fertilization, somatic cell nuclear transfer, or parthenogenetic activation - Neil C. Talbot; Anne M. Powell; Mary Camp; Alan D. Ealy (In Vitro Cellular & Developmental Biology - Animal, 2007)

Isolation and characterization of porcine visceral endoderm cell lines derived from in vivo 11-day blastocysts - Neil C. Talbot; Le Ann Blomberg; Ayesha Mahmood; Thomas J. Caperna; Wesley M. Garrett (In Vitro Cellular & Developmental Biology - Animal, 2007)

Resistance to phytophthora erythroseptica and pythium ultimum in a potato clone derived from s. berthaultii and s. etuberosum - Asunta L. Thompson; Raymond J. Taylor; Julie S. Pasche; Richard G. Novy; Neil C. Gudmestad (American Journal of Potato Research, 2007)

Patterns of cytokinins and leaf gas exchange among canopy layers of a mature sugar maple (Acer saccharum) stand - Ian Reeves; Scott C. Farrow; R. J. Neil Emery (Trees, 2007)

Biotechnologies in new high-throughput food allergy tests: why we need them - Neil K. Renault; Luciana Mirotti; Marcos J. C. Alcocer (Biotechnology Letters, 2007)

Long-term effects of developmental PCP administration on sensorimotor gating in male and female rats - Bruce A. Rasmussen; Jahn O’Neil; Kebreten F. Manaye; David C. Perry; Yousef Tizabi (Psychopharmacology, 2007)

Fatty acid synthase effects on bovine adipose fat and milk fat - Chris A. Morris; Neil G. Cullen; Belinda C. Glass; Dianne L. Hyndman; Tim R. Manley; Sharon M. Hickey; John C. McEwan; Wayne S. Pitchford; Cynthia D.K. Bottema; Michael A.H. Lee (Mammalian Genome, 2007)

Guanfacine produces differential effects in frontal cortex compared with striatum: assessed by phMRI BOLD contrast - Neil Easton; Yasmene B. Shah; Fiona H. Marshall; Kevin C. Fone; Charles A. Marsden (Psychopharmacology, 2006)

Differential gene expression of wheat progeny with contrasting levels of transpiration efficiency - Gang-Ping Xue; C. Lynne McIntyre; Scott Chapman; Neil I. Bower; Heather Way; Antonio Reverter; Bryan Clarke; Ray Shorter (Plant Molecular Biology, 2006)

Molecular Discrimination of Perna (Mollusca: Bivalvia) Species Using the Polymerase Chain Reaction and Species-Specific Mitochondrial Primers - D. Blair; M. Waycott; L. Byrne; G. Dunshea; C. Smith-Keune; K. M. Neil (Marine Biotechnology, 2006)

Nature of allelic sequence polymorphism at the KIR3DL3 locus - Des C. Jones; Susan E. Hiby; Ashley Moffett; John Trowsdale; Neil T. Young (Immunogenetics, 2006)

Racial admixture and its impact on BMI and blood pressure in African and Mexican Americans - Hua Tang; Eric Jorgenson; Maya Gadde; Sharon L. R. Kardia; D. C. Rao; Xiaofeng Zhu; Nicholas J. Schork; Craig L. Hanis; Neil Risch (Human Genetics, 2006)

Nitrogen, phosphorus, silica, and carbon in Moreton Bay, Queensland, Australia: Differential limitation of phytoplankton biomass and production - Patricia M. Glibert; Cynthia A. Heil; Judith M. O'Neil; William C. Dennison; Mark J. H. O'Donohue (Estuaries and Coasts, 2006)

PCR-based sexing in conservation biology: Wrong answers from an accurate methodology? - Bruce C. Robertson; Neil J. Gemmell (Conservation Genetics, 2006)

The Maize Oil Yellow1 (Oy1) Gene Encodes the I Subunit of Magnesium Chelatase - Ruairidh J. H. Sawers; Joanne Viney; Phyllis R. Farmer; Rhiannon R. Bussey; Gregory Olsefski; Katya Anufrikova; C. Neil Hunter; Thomas P. Brutnell (Plant Molecular Biology, 2006)

ACTIVATION OF ACTIVATOR PROTEIN-1 IN MOUSE BRAIN REGIONS EXPOSED TO SIMULATED MICROGRAVITY - SHUBHASHISH SARKAR; KIMBERLY C. WISE; SUNIL K. MANNA; VANI RAMESH; KEIKO YAMAUCHI; RENARD L. THOMAS; BOBBY L. WILSON; ANIL D. KULKARNI; NEIL. R. PELLIS; GOVINDARAJAN. T. RAMESH (In Vitro Cellular & Developmental Biology - Animal, 2006)

Population stratification confounds genetic association studies among Latinos - Shweta Choudhry; Natasha E. Coyle; Hua Tang; Keyan Salari; Denise Lind; Suzanne L. Clark; Hui-Ju Tsai; Mariam Naqvi; Angie Phong; Ngim Ung; Henry Matallana; Pedro C. Avila; et al. (Human Genetics, 2006)

Band Structure and Local Dynamics of Excitons in Bacterial Light-harvesting Complexes Revealed by Spectrally Selective Spectroscopy - Margus Rätsep; C. Neil Hunter; John D. Olsen; Arvi Freiberg (Photosynthesis Research, 2005)

Influence of tillage and method of metam sodium application on distribution and survival ofVerticillium dahliae in the soil and the development of verticillium wilt of potato - Raymond J. Taylor; Julie S. Pasche; Neil C. Gudmestad (American Journal of Potato Research, 2005)

A Coupled Calibration and Modelling Approach to the Understanding of Dry-Land Lake Oxygen Isotope Records - Matthew D. Jones; Melanie J. Leng; C. Neil Roberts; Murat Türkeş; Rana Moyeed (Journal of Paleolimnology, 2005)

A Small Family of Sushi-Class Retrotransposon-Derived Genes in Mammals and Their Relation to Genomic Imprinting - Neil A. Youngson; Sylvia Kocialkowski; Nina Peel; Anne C. Ferguson-Smith (Journal of Molecular Evolution, 2005)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Major gaps in the distribution of protected areas for threatened and narrow range Afrotropical plants - Neil Burgess; Wolfgang KÜper; Jens Mutke; Joanna Brown; Sally Westaway; Susie Turpie; Charles Meshack; James Taplin; Colin McClean; Jon C. Lovett (Biodiversity and Conservation, 2005)

Mercury and other Contaminants in Common Loons Breeding in Atlantic Canada - Neil M. Burgess; David C. Evers; Joseph D. Kaplan (Ecotoxicology, 2005)

Patterns of Hg Bioaccumulation and Transfer in Aquatic Food Webs Across Multi-lake Studies in the Northeast US - Celia Y. Chen; Richard S. Stemberger; Neil C. Kamman; Brandon M. Mayes; Carol L. Folt (Ecotoxicology, 2005)

Physical Controls on Total and Methylmercury Concentrations in Streams and Lakes of the Northeastern USA - James B. Shanley; Neil C. Kamman; Thomas A. Clair; Ann Chalmers (Ecotoxicology, 2005)

Factors Influencing Mercury in Freshwater Surface Sediments of Northeastern North America - Neil C Kamman; Ann Chalmers; Thomas A. Clair; Andrew Major; Richard B. Moore; Stephen A. Norton; James B. Shanley (Ecotoxicology, 2005)

Deconstruction of Historic Mercury Accumulation in Lake Sediments, Northeastern United States - Ethan Perry; Stephen A. Norton; Neil C. Kamman; P. M. Lorey; Charles T. Driscoll (Ecotoxicology, 2005)

Patterns and Interpretation of Mercury Exposure in Freshwater Avian Communities in Northeastern North America - David C. Evers; Neil M. Burgess; Louise Champoux; Bart Hoskins; Andrew Major; Wing M. Goodale; Robert J. Taylor; Robert Poppenga; Theresa Daigle (Ecotoxicology, 2005)

Mercury in Freshwater Fish of Northeast North America ? A Geographic Perspective Based on Fish Tissue Monitoring Databases - Neil C Kamman; Neil M. Burgess; Charles T. Driscoll; Howard A. Simonin; Wing Goodale; Janice Linehan; Robert Estabrook; Michael Hutcheson; Andrew Major; Anton M. Scheuhammer; David A. Scruton (Ecotoxicology, 2005)

Estimation and Mapping of Wet and Dry Mercury Deposition Across Northeastern North America - Eric K. Miller; Alan Vanarsdale; Gerald J. Keeler; Ann Chalmers; Laurier Poissant; Neil C. Kamman; Raynald Brulotte (Ecotoxicology, 2005)

Inheritance of mefenoxam resistance in selfed populations of the homothallic oomycetePhytophthora erythroseptica (Pethybr.), cause of pink rot of potato - Firas M. Abu-El Samen; Kirin Oberoi; Raymond J. Taylor; Gary A. Secor; Neil C. Gudmestad (American Journal of Potato Research, 2005)

Sedimentary record of radiolarian biogeography, offshore eastern New Zealand - C. J. Hollis; H. L. Neil (New Zealand Journal of Marine and Freshwater Research, 2005)
Examination of 38 surface sediment samples from offshore eastern New Zealand, between 33°S and 54°S, yielded 100 radiolarian taxa, which are common to abundant in sediments deposited at > 1000 m water depth but rare at shallower depths. In general, radiolarians are most abundant, most diverse, and best preserved in assemblages north of the Subtropical Front (STF). Multivariate analysis of census data for 29 radiolarian‐rich samples identifies six sample groups and eight species groups. The STF forms a major biogeographic barrier, separating three transitional zone (TR) and three subantarctic zone (SA) sample groups. The three primary sample groups (TR1, TR2, SA1) record a southward latitudinal trend of decreasing abundance of subtropical‐tropical or warm‐water taxa (species group 4) and increasing abundance of subantarctic ‐Antarctic or cool‐water taxa (species groups 7 and 8). Two secondary sample groups (TR3 and SA2) may record the influence of shallow‐water processes or strong surface currents on either side of the STF. A distinctive sample group (SA3), characterised by low abundance and diversity, records relatively shallow, stratified, and silica‐limited conditions of the central Campbell Plateau.

Relative Importance of Environmental Stress and Herbivory in Reducing Litter Fall in a Semiarid Woodland - Thomas D. Schuster; Neil S. Cobb; Thomas G. Whitham; Stephen C. Hart (Ecosystems, 2005)

ISOLATION AND CHARACTERIZATION OF A BOVINE VISCERAL ENDODERM CELL LINE DERIVED FROM A PARTHENOGENETIC BLASTOCYST - NEIL C. TALBOT; THOMAS J. CAPERNA; ANNE M. POWELL; ALAN D. EALY; LE ANN BLOMBERG; WESLEY M. GARRETT (In Vitro Cellular & Developmental Biology - Animal, 2005)

ACTIVATION OF NUCLEAR TRANSCRIPTION FACTOR–κB IN MOUSE BRAIN INDUCED BY A SIMULATED MICROGRAVITY ENVIRONMENT - KIMBERLY C. WISE; SUNIL K. MANNA; KEIKO YAMAUCHI; VANI RAMESH; BOBBY L. WILSON; RENARD L. THOMAS; SHUBHASHISH SARKAR; ANIL D. KULKARNI; NEIL R. PELLIS; GOVINDARAJAN T. RAMESH (In Vitro Cellular & Developmental Biology - Animal, 2005)

Trifluralin-mediated polyploidization of Rosa chinensis minima (Sims) Voss seedlings - David C. Zlesak; Christian A. Thill; Neil O. Anderson (Euphytica, 2005)

Sequence and expression of C-type lectin receptors in Atlantic salmon (Salmo salar) - Kelly H. Soanes; Kevin Figuereido; Robert C. Richards; Neil R. Mattatall; K. Vanya Ewart (Immunogenetics, 2004)

Purification and characterisation of lipoglycan macroamphiphiles from Propionibacterium acnes - Gary A. Whale; Iain C. Sutcliffe; Andrew R. Morrisson; Emma L. Pretswell; Neil Emmison (Antonie van Leeuwenhoek, 2004)

Physical, chemical, and biotic effects on arctic zooplankton communities and diversity - W. John O'Brien; Michael Barfield; Neil D. Bettez; Gretchen M. Gettel; Anne E. Hershey; Michael E. McDonald; Michael C. Miller; Howard Mooers; John Pastor; Carl Richards; Jeff Schuldt (Limnology and Oceanography, 2004)
We examined how physical and chemical factors and fish populations affected the presence and density of zooplankton species in 104 Alaskan arctic lakes. Five fish species and nine zooplankters were sampled from the lakes. Lake depth was related to the distribution of zooplankton in that smaller zooplankton species were found in deep lakes and large species in shallow lakes. Neither ionic strength nor chlorophyll was a major factor in zooplankton presence or absence. When fish were present, few, if any, very large zooplankton occurred together. However, the relationship between the presence and density of smaller‐sized zooplankton species and the presence of specific species of fish was complex and did not fit anticipated patterns. The diversity of zooplankton in these arctic lakes was not related to chemistry or fish distribution, but species richness increased with increasing lake area and depth. For a few zooplankters (notably Holopedium gibberum ), the fraction of lakes containing the zooplankter varied by region.

It never rains on Sunday: the prevalence and implications of untagged multi‐day rainfall accumulations in the Australian high quality data set - Neil R. Viney; Bryson C. Bates (International Journal of Climatology, 2004)
The perception prevalent in the literature that Australian rainfall records are reasonably uncontaminated by untagged weekend accumulations is reassessed. An objective probabilistic test for untagged accumulations is developed and applied to 181 gauges that have previously been identified as having high‐quality data suitable for long‐term analyses of climate change. As many as 102 of these gauges are found to contain hidden, untagged accumulations, and the overall prevalence of untagged accumulations in the high‐quality data set is shown to be only slightly less than that of tagged accumulations. A simple study simulating the effects of accumulations in the records of the high‐quality data set shows that, in records (or parts of records) with frequent accumulations, rainfall probability, mean wet‐spell length and mean dry‐spell length can be underestimated by as much as 24%, 34% and 18% respectively, and that the magnitude of the potential prediction error in these variables (and also in indices of rainfall intensity extremes) at a site shows strong dependence on the rainfall probability. Selected published studies on climate change are reanalysed to account for the presence of untagged accumulations and to show that significant changes in long‐term trends can be obtained for individual locations. Copyright © 2004 Royal Meteorological Society

Antioxidant enzyme activity and mRNA expression in the islets of Langerhans from the BB/S rat model of type 1 diabetes and an insulin-producing cell line - Louise A. Sigfrid; James M. Cunningham; Neil Beeharry; L. A. Hkan Borg; Alma L. Rosales Hernandez; Carina Carlsson; Adrian J. Bone; Irene C. Green (Journal of Molecular Medicine, 2004)

CD45 variant alleles: possibly increased frequency of a novel exon 4 CD45 polymorphism in HIV seropositive Ugandans - Tara Stanton; Sally Boxall; Andrea Bennett; Pontiano Kaleebu; Christine Watera; Jimmy Whitworth; Neil French; Ritu Dawes; Adrian V. S. Hill; Walter Bodmer; Peter C. L. Beverley; Elma Z. Tchilian (Immunogenetics, 2004)

Combining Landsat ETM+ and Reef Check classifications for mapping coral reefs: a critical assessment from the southern Great Barrier Reef, Australia - K. E. Joyce; S. R. Phinn; C. M. Roelfsema; D. T. Neil; W. C. Dennison (Coral Reefs, 2004)

Influence of Oat Kernel Size and Size Distributions on Test Weight - Douglas C. Doehlert; Michael S. McMullen; Jean-Luc Jannink; Surangan Panigrahi; Huanzhong Gu; Neil Riveland (Cereal Research Communications, 2004)

MACROPHAGE POPULATION DYNAMICS WITHIN FETAL MOUSE FIBROBLAST CULTURES DERIVED FROM C57BL/6, CD-1, CF-1 MICE AND INTERLEUKIN-6 AND GRANULOCYTE COLONY STIMULATING FACTOR KNOCKOUT MICE - NEIL C. TALBOT; MAX PAAPE; EUN JUNG SOHN; WESLEY M. GARRETT (In Vitro Cellular & Developmental Biology - Animal, 2004)

The sterol modifying enzyme LET-767 is essential for growth, reproduction and development in Caenorhabditis elegans - L. M. Kuervers; C. L. Jones; N. J. O'Neil; D. L. Baillie (Molecular Genetics and Genomics, 2003)

Selecting plants to minimise radiocaesium in the food chain - Philip J. White; Kamal Swarup; Abraham J. Escobar-Gutiérrez; Helen C. Bowen; Neil J. Willey; Martin R. Broadley (Plant and Soil, 2003)

Temporal sensitivity ofAlternaria solani to foliar fungicides - Amy L. Holm; Viviana V. Rivera; Gary A. Secor; Neil C. Gudmestad (American Journal of Potato Research, 2003)

Water column interleaving: A new physical mechanism determining protist communities and bacterial states - Connie Lovejoy; Eddy C. Carmack; Louis Legendre; Neil M. Price (Limnology and Oceanography, 2002)
During a spring‐summer bloom in a large Arctic polynya, vertically distinct protist communities (phytoplankton and protozoa) occurred within layers caused by interleaving and entrainment of different water masses. We developed a ternary community distance index to quantify the variability in protist community structure in these heterogeneous surface layers. This index was highly correlated ( r = 0.984, n = 6) with the extent of physical interleaving (quantified as the root mean square deviations in temperature between measured and smoothed profiles) indicating a high degree of physical‐biotic coupling within water columns of the polynya. Water mass layering created favorable conditions for ciliate blooms. These blooms were associated with distinct temperature‐salinity layers. These layers might act as processing traps for particulate organic matter, with highest concentrations of viruses and bacteria (specifically cells with open or leaky membranes, suggesting microbial grazing pressure) occurring in highly interleaved water columns. In contrast, viral and bacterial concentrations were lowest at a noninterleaved station where protist biomass was dominated by flagellates and small dinoflagellates that were evenly distributed down the water column. Water mass interleaving is likely to contribute to microbial biodiversity, community structure and vertical segmentation of biogeochemical processes in the upper ocean.

Near-infrared spectral imaging for quality assurance of pharmaceutical products: Analysis of tablets to assess powder blend homogeneity - Robbe C. Lyon; David S. Lester; E. Neil Lewis; Eunah Lee; Lawrence X. Yu; Everett H. Jefferson; Ajaz S. Hussain (AAPS PharmSciTech, 2002)

Stable chlorine intramolecular kinetic isotope effects from the abiotic dehydrochlorination of DDT - Christopher M. Reddy; Nicholas J. Drenzek; Timothy I. Eglinton; Linnea J. Heraty; Neil C. Sturchio; Vernon J. Shiner (Environmental Science and Pollution Research, 2002)

Factors influencing PVY development and disease expression in three potato cultivars - Martin D. Draper; Julie S. Pasche; Neil C. Gudmestad (American Journal of Potato Research, 2002)

Abscisic acid concentration, root pH and anatomy do not explain growth differences of chickpea (Cicer arietinum L.) and lupin (Lupinus angustifolius L.) on acid and alkaline soils - Wolfram Hartung; Laurent Leport; R. George Ratcliffe; Angela Sauter; Regina Duda; Neil C. Turner (Plant and Soil, 2002)

SPONTANEOUS DIFFERENTIATION OF PORCINE AND BOVINE EMBRYONIC STEM CELLS (EPIBLAST) INTO ASTROCYTES OR NEURONS - NEIL C. TALBOT; ANNE M. POWELL; WESLEY M. GARRETT (In Vitro Cellular & Developmental Biology - Animal, 2002)

Virus‐like particle distribution and abundance in sediments and overlying waters along eutrophication gradients in two subtropical estuaries - Ian Hewson; Judith M. O'Neil; Jed A. Fuhrman; William C. Dennison (Limnology and Oceanography, 2001)
Viruses are recognized as ubiquitous components of marine ecosystems; however, there has been limited study of viral abundance and its ecological role in sediments. Viral abundance was determined in both the water column and sediments of a eutrophic (Brisbane River/Moreton Bay; 27°25′S, 153°5′E) and oligotrophic (Noosa River; 26°15′S, 153°0′E) estuary in subtropical Queensland, Australia. Viruses, bacteria, and microalgae from both water column and extracted sediment samples were enumerated using SYBR Green I staining and epifluorescence microscopy. Sediment viral abundance ranged from 10 7 to 10 9 particles cm −3 of sediment, bacterial abundance ranged from 10 7 to 10 8 cells cm −3 of sediment, and microalgal abundance ranged from 10 4 to 10 5 cells cm −3 sediment. Pelagic abundances for all microorganisms were 10–1,000‐fold lower than sediment abundances. Correlations between viral abundances and suspended solids suggest that viruses sorbed to suspended material in the water column may settle out and contribute to the benthic viral population. Virus production was measured by a time course increase of viral abundance in seawater using a dilution technique. Virus production was highest in eutrophic waters of the Brisbane River, and addition of inorganic nutrients (NO 3 − + NH 4 + + PO 4 3− + SiO 3 ) stimulated viral production rates at all stations by 14–52% above ambient, suggesting that inorganic nutrient availability may play a key role in aquatic viral abundance.

Repetitive Sequence-derived PCR Profiling Using the BOX-A1R Primer for Rapid Identification of the Plant Pathogen Clavibacter Michiganensis Subspecies Sepedonicus - Neil C. Smith; Judy Hennessy; David E. Stead (European Journal of Plant Pathology, 2001)

PCR detection ofclavibacter michiganensis subsp.sepedonicus- infected tuber samples in a plate capture assay - Debra Baer; Emily Mitzel; Julie Pasche; Neil C. Gudmestad (American Journal of Potato Research, 2001)

Gene flow on the ice: genetic differentiation among Adélie penguin colonies around Antarctica - Amy D. Roeder; Richelle K. Marshall; Amanda J. Mitchelson; Thungar Visagathilagar; Peter A. Ritchie; Donald R. Love; Trevor J. Pakai; Helen C. McPartlan; Neil D. Murray; Nick A. Robinson; Knowles R. Kerry; David M. Lambert (Molecular Ecology, 2001)
Each summer Adélie penguins breed in large disjunct colonies on ice‐free areas around the Antarctic continent. Comprising > 10 million birds, this species represents a dominant feature of the Antarctic ecosystem. The patchy distribution within a large geographical range, natal philopatry and a probable history of refugia, suggest that this species is likely to exhibit significant genetic differentiation within and among colonies. We present data from seven microsatellite DNA loci for 442 individuals from 13 locations around the Antarctic continent. With the exception of one locus, there was no significant genic or genotypic heterogeneity across populations. Pairwise F ST values were low with no value > 0.02. When all colonies were compared in a single analysis, the overall F ST value was 0.0007. Moreover, assignment tests were relatively ineffective at correctly placing individuals into their respective collection sites. These data reveal a lack of genetic differentiation between Adélie penguin colonies around the Antarctic continent, despite substantial levels of genetic variation. We consider this homogeneity in terms of the dispersal of individuals among colonies and the size of breeding groups and discuss our results in terms of the glacial history of Antarctica.

Engineering plants for the phytodetoxification of explosives - Susan J. Rosser; Christopher E. French; Neil C. Bruce (In Vitro Cellular & Developmental Biology - Plant, 2001)

Phytoplankton distribution and survival in the thermocline - Jonathan Sharples; Mark C. Moore; Tom P. Rippeth; Patrick M. Holligan; David J. Hydes; Neil R. Fisher; John H. Simpson (Limnology and Oceanography, 2001)
Observations of the vertical structure of density, concentrations of chlorophyll a and nitrate, and turbulent dissipation rates were made over a period of 25 h in a well‐stratified shelf region in the Western English Channel, between neap and spring tides. Maximum turbulent dissipation at the base of the thermocline occurred almost 5 h after maximum tidal currents. This turbulence aids phytoplankton growth by supplying bottom‐layer nutrients into the subsurface chlorophyll maximum but reduces phytoplankton concentrations in the thermocline by mixing cells from the base of the subsurface maximum into the bottom mixed layer. The turbulent dissipation observations were used to estimate an average nitrate flux into the thermocline of 2.0 (0.8‐3.2, 95% confidence interval) mmol m −2 d −1 , which is estimated to have been capable of supporting new phytoplankton growth at a rate of 160 (64–256) mg C m −2 d −1 . Turbulent entrainment of carbon from the base of the subsurface biomass maximum into the bottom mixed layer was observed to be 290 (120–480) mg C m −2 d −1 . This apparent excess export from the chlorophyll maximum is suggested to be a feature of the spring‐neap cycle, with export dominating as the tidal turbulence increases toward spring tides and erodes the base of the thermocline. The observed rate of carbon export into the bottom mixed layer could account for as much as 25% of the gross annual primary production in stratifying shelf seas. Such turbulent losses, combined with grazing losses and low light levels, suggest that phytoplankton need to be highly adapted to environmental conditions within the thermocline in order to survive.

Changes in Tissue Cellularity Are Associated with Growth Enhancement in Genetically Modified Arctic Char (Salvelinus alpinus L.) Carrying Recombinant Growth Hormone Gene - Tiina I. Pitkänen; Sheila Q. Xie; Aleksei Krasnov; Paul S. Mason; Hannu Mölsä; Neil C. Stickland (Marine Biotechnology, 2001)

Tree roots: conduits for deep recharge of soil water - Stephen S.O. Burgess; Mark A. Adams; Neil C. Turner; Don A. White; Chin K. Ong (Oecologia, 2001)

Deletion of The Gene Encoding H-FABP/MDGI has no Overt Effects in The Mammary Gland - A.J. Clark; C. Neil; B. Gusterson; J. McWhir; B. Binas (Transgenic Research, 2000)

Cloning, sequencing and analysis of the pucC genes from Rubrivivax gelatinosus strain 151 and Rhodopseudomonas acidophila strain 10050 - Adrian E. Simmons; Stuart J. Barrett; C. Neil Hunter; Richard J.R. Cogdell (Photosynthesis Research, 2000)

Genotype and phenotype of cytochrome P 450 2D6 in human immunodeficiency virus-positive patients and patients with acquired immunodeficiency syndrome - W. M. O'Neil; B. M. Gilfix; N. Markoglou; A. Di Girolamo; C. M. Tsoukas; I. W. Wainer (European Journal of Clinical Pharmacology, 2000)

Species differences in response to diethylhexylphthalate: suppression of apoptosis, induction of DNA synthesis and peroxisome proliferator activated receptor alpha-mediated gene expression - Susan C. Hasmall; Neil H. James; Neil Macdonald; Anthony R. Soames; Ruth A. Roberts (Archives of Toxicology, 2000)

Suppression of apoptosis and induction of DNA synthesis in vitro by the phthalate plasticizers monoethylhexylphthalate (MEHP) and diisononylphthalate (DINP): a comparison of rat and human hepatocytes in vitro - Susan C. Hasmall; Neil H. James; Neil Macdonald; Douglas West; Stephan Chevalier; Sabina C. Cosulich; Ruth A. Roberts (Archives of Toxicology, 1999)

Prostate-specific Membrane Antigen (PSMA)-specific Monoclonal Antibodies in the Treatment of Prostate and Other Cancers - Michael C. Gong; Sam S. Chang; Michel Sadelain; Neil H. Bander; Warren D.W. Heston (Cancer and Metastasis Reviews, 1999)

Effects of microgravity on the embryonic pancreas - Michael I. Rose; Dale C. Brown; Neil R. Pellis; Christopher A. Crisera; Kari L. Colen; Michael T. Longaker; George K. Gittes (In Vitro Cellular & Developmental Biology - Animal, 1999)

Minimal requirements for in vitro reconstitution of the structural subunit of light-harvesting complexes of photosynthetic bacteria - John B. Todd; Paul A. Recchia; Pamela S. Parkes-Loach; John D. Olsen; Gregory J. S. Fowler; Peter McGlynn; C. Neil Hunter; Paul A. Loach (Photosynthesis Research, 1999)

Long‐term dynamics of algal and invertebrate communities in a small, fluctuating tropical soda lake - Dirk Verschuren; Christine Cocquyt; John Tibby; C. Neil Roberts; Peter R. Leavitt (Limnology and Oceanography, 1999)
Lake Sonachi, Kenya, is a small alkaline‐saline crater lake that over the past 175 years has experienced considerable fluctuations in lake depth (Zmax = 3–18 m) and an alternation of meromictic and holomictic episodes lasting from a few years to several decades. Paleolimnological methods were used to reconstruct the long‐term dynamics of algal and invertebrate communities in Lake Sonachi in relation to the historical evolution of their physical and chemical environment. Multivariate statistical analysis revealed only weak correlation between the stratigraphic distributions of fossil algal pigments, diatoms, and chironomid larvae in 210Pb‐dated sediment cores and the documented or reconstructed variation in lake depth, mixing regime, and surface‐water conductivity. The eventful biological history of Lake Sonachi exemplifies the complexity of long‐term community dynamics in tropical African soda lakes and reveals how phytoplankton community structure can exert direct control on benthic and planktonic invertebrate communities. The modest phytoplankton abundance and photosynthetic activity of Lake Sonachi when compared with other tropical African soda lakes represent recent lake conditions, resulting from a dramatic decline of filamentous cyanobacteria (e.g., Spirulina platensis) between the 1930s and 1970s and incomplete replacement by the small coccoid cyanobacteria (e.g., Synechococcus bacillaris), which are dominant today. This reduction in algal biomass favored benthic and planktonic invertebrates by reducing the prevalence of complete water‐column anoxia associated with intense nighttime respiration of cyanobacterial blooms. Anoxia‐intolerant halobiont chironomids expanded during an episode of low lake level (Zmax 9,000 µS cm −1 ) in the late 1940s and 1950s, whereas they had failed to do so under similar conditions in the late 19th century when algal abundance was high. Planktonic cladocerans developed high population densities only during two short meromictic phases in the 1970s when conductivity was modest (3,000–6,000 µS cm −1 ) and algal abundance was low. The decline of filamentous cyanobacteria also increased water‐column transparency but apparently did not increase benthic diatom abundance.

The fit-1 common integration locus in human and mouse is closely linked to MYB - N.I. Barr; M. Stewart; C. Tsatsanis; R. Fulton; M. Hu; H. Tsujimoto; J.C. Neil (Mammalian Genome, 1999)

The peroxisome proliferator nafenopin does not suppress hepatocyte apoptosis in guinea-pig liver in vivo nor in human hepatocytes in vitro - Susan C. Hasmall; Neil H. James; Anthony R. Soames; Ruth A. Roberts (Archives of Toxicology, 1998)

Selective and organotypic culture of intrahepatic bile duct cells from adult pig liver - Neil C. Talbot; Thomas J. Caperna (In Vitro Cellular & Developmental Biology - Animal, 1998)

Homogeneity adjustments ofin situ atmospheric climate data: a review - Thomas C. Peterson; David R. Easterling; Thomas R. Karl; Pavel Groisman; Neville Nicholls; Neil Plummer; Simon Torok; Ingeborg Auer; Reinhard Boehm; Donald Gullett; Lucie Vincent; Raino Heino; et al. (International Journal of Climatology, 1998)

CO2 Mitigation by Agriculture: An Overview - Keith Paustian; C. Vernon Cole; Dieter Sauerbeck; Neil Sampson (Climatic Change, 1998)

The redistribution of soil water by tree root systems - Stephen S. O. Burgess; Mark A. Adams; Neil C. Turner; Chin K. Ong (Oecologia, 1998)

Fault scarp statistics at the Galapagos spreading centre from Deep Tow data - Neil C. Mitchell; Roger C. Searle (Marine Geophysical Research, 1998)

NorValley: A white-skinned chipping cultivar with cold-sweetening resistance - Richard G. Novy; Gary A. Secor; Bryce L. Farnsworth; Jim H. Lorenzen; Edna T. Holm; Duane A. Preston; Neil C. Gudmestad; Joseph R. Sowokinos (American Journal of Potato Research, 1998)

Effect of exercise-induced muscle damage on the blood lactate response to incremental exercise in humans - Michael Gleeson; Andrew K. Blannin; Neil P. Walsh; Christine N. E. Field; Jeanette C. Pritchard (European Journal of Applied Physiology, 1998)

Kinetics of continuous fermentation and stripping of ethanol - Frank Taylor; Michael J. Kurantz; Neil Goldberg; James C. Craig (Biotechnology Letters, 1998)

Chemical communication in heliothine moths. VII. Correlation between diminished responses to point-source plumes and single filaments similarly tainted with a behavioral antagonist - Neil J. Vickers; Thomas C. Baker (Journal of Comparative Physiology A, 1997)

A seismic study of salt dissolution in the Stettler area south-central Alberta, Canada - Neil L. Anderson; Ronald C. Hinds (Carbonates and Evaporites, 1997)

Glacial loading and unloading: a possible cause of rock salt dissolution in the Western Canada Basin - Neil L. Anderson; Ronald C. Hinds (Carbonates and Evaporites, 1997)

Nordonna: A red-skinned potato cultivar with wide adaptability - Richard G. Novy; Robert H. Johansen; Gary A. Secor; Bryce L. Farnsworth; Jim H. Lorenzen; Neil C. Gudmestad; Edna T. Holm (American Journal of Potato Research, 1997)

Goldrush: A new high quality russet-skinned potato cultivar - Robert H. Johansen; Bryce Farnsworth; Gary A. Secor; Neil C. Gudmestad; Asunta Thompson-Johns; Edna T. Holm (American Journal of Potato Research, 1994)

The Potato Association of America 75th Annual Meeting Spokane, Washington, U.S.A. - David Curwen; Pete Weingartner; Ronald Knight; Therese M. Work; Hugh J. Murphy; Steven B. Johnson; Richard Zink; Leigh Morrow; A. R. Mosley; Rod Davidson; Thoms Owings; Don Halseth; et al. (American Journal of Potato Research, 1991)

A historical perspective to pathogen testing in seed potato certification - Neil C. Gudmestad (American Journal of Potato Research, 1991)

Microbial degradation of the morphine alkaloids: identification of morphinone as an intermediate in the metabolism of morphine by Pseudomonas putida M10 - Neil C. Bruce; Clare J. Wilmot; Keith N. Jordan; Anna E. Trebilcock; Lauren D. Gray Stephens; Christopher R. Lowe (Archives of Microbiology, 1990)

Hydroaromatic metabolism in Rhodococcus rhodochrous: purification and characterisation of its NAD-dependent quinate dehydrogenase - Neil C. Bruce; Ronald B. Cain (Archives of Microbiology, 1990)

The effect of ethylene and abscisic acid on symptom expression of bacterial ring rot in eggplant and potato - Chester J. Kurowski; Neil C. Gudmestad (American Journal of Potato Research, 1990)

s of additional papers presented - Steven A. Slack; Andrew L. Bishop; Gary A. Secor; Lynda DeBuhr; Neil C. Gudmestad; Gene D. Easton; Michael E. Nagle; Marcus D. Seymour; B. D. Mogen; A. E. Oleson; N. C. Gudmestad (American Journal of Potato Research, 1987)

Recommendations of the National Task Force for the eradication of bacterial ring rot - Neil C. Gudmestad (American Journal of Potato Research, 1987)

Wound healing, decay and chemical treatment of cut potato tuber tissue - Phillip Nolte; Gary A. Secor; Neil C. Gudmestad (American Journal of Potato Research, 1987)

The bionomics ofErwinia carotovora in North Dakota - Neil C. Gudmestad; Gary A. Secor (American Journal of Potato Research, 1983)

The effect of harvest date and tuber-borne sclerotia on the severity ofRhizoctonia disease of potato - Neil C. Gudmestad; Richard T. Zink; J. E. Huguelet (American Journal of Potato Research, 1979)